Prendre soin de sa santé psychologique en culture avec Florence Morin-Parent, psychologue (Le répondeur de l'industrie musicale, 2024)
25 septembre 2024
Keywords: Bibliographie; Nettoyer

Cultive, la plateforme du développement professionnel en culture (Cultive, 2024)
Plateforme qui rassemble les offres de formation, les outils et les références pour le développement de votre carrière en culture au Québec.
Keywords: Bibliographie; Nettoyer

Safia Nolin répond à la haine par la musique - Caillou, Annabelle (Le Devoir, 2024)
Se gardant de tout révéler, l’artiste explique qu’elle sera sur scène avec pour seules armes sa guitare et sa voix.
Keywords: Bibliographie; Nettoyer

Condamnation pour agression sexuelle: Goûchy Boy lance sa marchette sur les journalistes avant de recevoir sa peine - Perron, Louis-Samuel (La Presse, 2024)
Deux heures après avoir attaqué un photographe de presse en lui lançant sa marchette en plein palais de justice, le comédien Goûchy Boy a été condamné à 21 mois d’emprisonnement, mercredi, pour avoir agressé sexuellement une femme qu’il traitait comme son « objet sexuel ».

High time to enhance dancer welfare: a call to action to improve safeguarding and abuse prevention in dance - Cumming, Jennifer; Nordin-Bates, Sanna M.; Johnson, Carrie; Sanchez, Erin N.; Karageanes, Steven J. (BMJ Open Sport & Exercise Medicine, 2024)
While there is a lack of research into abuse in elite dance, numerous allegations of emotional, sexual and physical abuse of dancers can be found anecdotally in the media, legal convictions and personal accounts. As more dancers speak out, the scale of the problem within preprofessional schools and professional companies is becoming apparent. Accordingly, effective safeguarding mechanisms for preventing, identifying and reporting abuse are urgently needed. This viewpoint is intended to raise health professionals’ awareness of factors contributing to abusive practices found in dance environments and the potential clinical implications of abuse to dancers’ health and well-being. We also call for research and policy engagement on safeguarding and abuse prevention designed and implemented in partnership with stakeholders, aiming to promote safe and positive dance environments for all.
Publisher: BMJ Specialist Journals Section: Viewpoint

Le Centre psychologique pour artistes, un nouvel outil pour le milieu culturel - Renaud, Philippe (Le Devoir, 2024)
Keywords: Bibliographie; Nettoyer

“Quelque chose a changé dans cette si masculine République des Lettres”. Tribune - d'Academia, L'équipe des rédacteurs (Academia, 2024)
Academia reproduit un tribune publiée dans Le Monde daté du 8 mars 2024 sous le titre Violences sexuelles. « Ce qui se passe dans le milieu du cinéma se passe aussi ailleurs, à l’université, dans les écoles, dans l’édition ». Plusieurs membres … Continuer la lecture →
ISSN: 2265-2434

Centre d'aide aux victimes d'actes criminels (CAVAC, 2024)
«Le Réseau des CAVAC est présent dans toutes les régions du Québec. Plus de 185 portes qui vous donnent accès à des professionnel(le)s formé(e)s en intervention ».
https://cavac.qc.ca/
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Californie: Un professeur de musique de McGill poursuivi pour agression sexuelle - Siag, Jean (La Presse, 2024)
Un professeur de musique de l’Université McGill est poursuivi au civil aux États-Unis par deux anciennes étudiantes disant avoir été agressées sexuellement à l’époque où il enseignait en Californie. Des allégations que le professeur nie vigoureusement.
Keywords: Bibliographie; Nettoyer

Mémoire présenté à la Commission de l’économie et du travail Dans le cadre des consultations particulières et des auditions publiques sur le projet de loi n° 42 - Loi visant à prévenir et à combattre le harcèlement psychologique et la violence à caractère sexuel en milieu de travail - Juripop (2024)
Keywords: Bibliographie; Nettoyer

Les agressions sexuelles : de quoi parle-t-on? - INSPQ (Institut national de santé publique du Québec, 2024)
Il n’existe pas de définition universelle de l’agression sexuelle, et différentes perspectives peuvent être utilisées pour la définir (p. ex. politique, légale, clinique ou scientifique). Un élément commun à toutes les formes d’agression sexuelle est l’absence de consentement, c’est-à-dire que la personne victime n’a pas consenti à l’activité sexuelle ou à la poursuite de celle‑ci, qu’elle était incapable d’y consentir ou de la refuser ou qu’elle n’avait pas l’âge de consentir.
Keywords: Coffre à outils; À ajouter

Rethinking sexual violence labels: exploring the impact of ‘victim’ and ‘survivor’ discourse - O’Shea, Brittany; Feicht, Rebecca; Brown, Marion; Numer, Matthew (European Journal of Psychotraumatology, 2024)
Background: Universities’ responses to sexual violence have faced scrutiny for their lack of proactiveness and their failure to address campus socio-cultural norms that contribute to rape myth acceptance. The labels victim and survivor play a crucial role in shaping attitudes toward sexual violence, but there is limited research on how university students perceive these labels. Objective: This paper explores sexual violence labels and their role in perpetuating rape culture. Undergraduate university students’ beliefs on using the label survivor instead of victim to describe someone who has experienced sexual violence were examined to consider how these labels create societal discourse on sexual violence. Method: The study draws on qualitative data collected from undergraduate students in Canada and the United States through open-response questions in an interactive textbook. Data were analysed and interpreted using a multi-method approach that combined principles of Critical Discourse Analysis and Feminist Poststructuralism. Direct quotes and word clouds from participants’ responses are used as evidence and to visually display discourse. Results: Findings revealed that participants recognised the negative societal discourses associated with the label victim and supported using survivor to challenge perceptions of sexual violence. Despite this, participants expressed hesitancy to adopt the label survivor because of the potential negative implications, such as the label promoting the allocation of individual blame, increasing barriers to justice, and reducing the perceived severity of sexual violence. Conclusions: This study underscores the complexities of sexual violence labels, the influence of language in shaping societal perceptions, and the need for a more comprehensive and equitable approach to responding to sexual violence. Dichotomy of Labels and Nuanced Perceptions: Sexual violence labels shape identity perceptions. Participants dichotomised the labels victim and survivor, associating one with negative attributes and the other with positive attributes. However, nuanced views of how people perceive and identify with these labels challenge distinct categories. Victims being negatively perceived, while survivors are admired for their resiliency highlights complexities in societal expectations that may not fully address the underlying determinants of sexual violence.Role of Language in Reproduction of Rape Culture: Poststructuralist theories emphasise the role of language in the production and maintenance of discourse. The study shows that victim discourse is steeped in rape myths. The historical discourse surrounding the label may contribute to the perpetuation of negative attitudes and behaviours toward victims of sexual violence. The emergence of the label survivor reflects a societal shift, but findings suggest this may lead to societal complacency towards sexual violence.Spectrum of Severity and Societal Empathy: Participants’ understanding of sexual violence as a spectrum of severity may lead to unequal levels of empathy and support. This discourse creates positions of dominance and oppression, potentially marginalising certain groups who are disproportionately affected by sexual violence. The study highlights how severity discourse can influence institutional agendas and may result in political and institutional neglect of sexual violence. Dichotomy of Labels and Nuanced Perceptions: Sexual violence labels shape identity perceptions. Participants dichotomised the labels victim and survivor, associating one with negative attributes and the other with positive attributes. However, nuanced views of how people perceive and identify with these labels challenge distinct categories. Victims being negatively perceived, while survivors are admired for their resiliency highlights complexities in societal expectations that may not fully address the underlying determinants of sexual violence. Role of Language in Reproduction of Rape Culture: Poststructuralist theories emphasise the role of language in the production and maintenance of discourse. The study shows that victim discourse is steeped in rape myths. The historical discourse surrounding the label may contribute to the perpetuation of negative attitudes and behaviours toward victims of sexual violence. The emergence of the label survivor reflects a societal shift, but findings suggest this may lead to societal complacency towards sexual violence. Spectrum of Severity and Societal Empathy: Participants’ understanding of sexual violence as a spectrum of severity may lead to unequal levels of empathy and support. This discourse creates positions of dominance and oppression, potentially marginalising certain groups who are disproportionately affected by sexual violence. The study highlights how severity discourse can influence institutional agendas and may result in political and institutional neglect of sexual violence.
Publisher: Taylor & Francis _eprint: https://doi.org/10.1080/20008066.2023.2296329
Keywords: Bibliographie; Nettoyer

Code de conduite [Affiche] (2024)
18 x 24 harcèlement affiche WEB
https://site.uda.ca/media/code-de-conduite-harcelement-18x24_web
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Déclaration pour un environnement de travail exempt de harcèlement dans le milieu culturel québécois (Regroupement des arts interdisciplinaires du Québec, 2024)
ATTENDU QUE des associations d’artistes et des associations de producteurs (ci-après collectivement les « Associations ») ainsi que les regroupements du milieu culturel (ci-après collectivement les « Regroupements »), conviennent que toutes les personnes œuvrant dans le milieu culturel québécois, quel que ce soit leur rôle ou leurs responsabilités, devraient être en mesure d’exercer [...]
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Dénoncez un incident sur le plateau (ACTRA Montreal, 2024)
Grâce aux rapports anonymes, nous sommes informés des problèmes au fur et à mesure qu’ils surviennent. Il est possible de rester anonyme, mais il est préférable de laisser vos coordonnées pour que nous puissions vous contacter. Nous ne donnerons jamais suite à une réclamation sans votre consentement!
Keywords: Bibliographie; Nettoyer

En mouvement vers une culture du consentement (RQCALACS, 2024)
Les CALACS offrent des services de soutien aux victimes d’agressions à caractère sexuel. Trouvez de l’aide, partout à travers le Québec.
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

J'ai besoin d'un avocat - Services offerts aux organismes (Juripop, 2024)

le relationnel (le relationnel, 2024)
Ressource suggéré par REPAIRE : « Le relationnel, service de thérapie en relation d'aide. Nos thérapeutes vous accompagnent sur le chemin de votre développement personnel, à votre rythme. »

Léa et Loïc (Parminou: Théâtre socialement engagé, 2024)
Keywords: Bibliographie; Nettoyer

Services (Divergenres, 2024)
Keywords: Coffre à outils; À ajouter

Tous les spectacles (Parminou: Théâtre socialement engagé, 2024)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Violences conjugales et sexuelles: Formations gratuites (Juripop, 2024)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Coordonnateur·rice·s de l'intimité - ACTRA Montréal (ACTRA Montreal, 2024)
Les coordonnateurs d'intimité sont des spécialistes de la production qui planifient, supervisent et coordonnent les scènes intimes filmées.
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Contribuer à une culture exempte de harcèlement (SST) - AQTIS 514 IATSE (L'Alliance québécoise des techniciens et techniciennes de l'image et du son, section locale 514, 2024)
« Parce que la sécurité au travail est une responsabilité collective, luttons ensemble pour éliminer le harcèlement ! Votre syndicat a fait de cet enjeu sa priorité. Notre industrie, atypique et fortement compétitive, peut engendrer de nombreux abus et freiner la dénonciation. La précarité d'emploi, la hiérarchisation des fonctions, le taux de rendement exigé, le niveau de stress et la crainte de représailles en sont les principaux facteurs. L'AQTIS 514 IATSE met à votre disposition une formation gratuite et interactive pour vous aider à travailler dans un environnement sécuritaire. OBJECTIFS : Reconnaître les situations qui s’apparentent à du harcèlement psychologique ou sexuel au travail; Savoir adopter une posture d’affirmation face à des conduites d’incivilité, d’intimidation ou de harcèlement en vue de les faire cesser; Connaître les mécanismes pour signaler ou dénoncer les conduites s’apparentant à de l’intimidation ou du harcèlement.»
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

L'intimidation et la cyberintimidation au Québec: portrait à partir de l'Étude québécoise sur les rapports sociaux dans un contexte scolaire, de travail et dans la communauté 2022 - Aranibar Zeballos, Daniela; Paquette, Jesseca (Institut de la statistique du Québec, 2024)
OCLC: 1439227761
Keywords: Bibliographie; Nettoyer

Violence sexuelle - Bureau de la médiation et du signalement (Université McGill, 2024)
Tous les membres de McGill ont droit au soutien sans équivoque du Bureau d’intervention, de prévention et d’éducation en matière de violence sexuelle (OSVRSE – Office for Sexual Violence Response, Support, and Education), que ces membres déposent ou non un signalement officiel. L’OSVRSE peut vous fournir des services de soutien, vous aider à obtenir des accommodements scolaires ou professionnels et vous expliquer les différents processus de signalement — que vous envisagiez de faire un signalement dans le cadre de la Politique contre la violence sexuelle de McGill ou à l’extérieur — afin que vous puissiez décider ce qui vous convient le mieux. Il n’est pas nécessaire de déposer un signalement officiel pour accéder à du soutien, demander des accommodements possibles ou obtenir de l’information auprès de l’OSVRSE. Vous pouvez prendre rendez-vous directement avec l’OSVRSE ici. Si vous souhaitez déposer un signalement en vertu de la Politique contre la violence sexuelle de McGill ou en apprendre davantage au sujet des processus offerts (médiation/enquête), veuillez communiquer avec le Bureau de la médiation et du signalement (OMR). Visitez notre page Demander une consultation pour en savoir plus. Tous les membres de la communauté universitaire ont le droit de travailler et d’apprendre dans un environnement exempt de violence sexuelle. L’Université reconnaît que, même si la violence sexuelle touche tous les membres de la société, ce type de maltraitance et ses conséquences peuvent atteindre de manière disproportionnée des membres de groupes sociaux aux prises avec des formes intersectionnelles de discrimination systémique ou d’obstacles (fondés notamment sur l’identité et l’expression sexuelles, l’orientation sexuelle, la race, la religion, l’appartenance à un groupe autochtone, l’ethnicité, l’invalidité ou la classe sociale). Qu’est-ce que la violence sexuelle ? La violence sexuelle est un terme générique qui désigne un continuum d’actes de nature sexuelle qui sont menacés, tentés ou commis à l’encontre d’une personne sans son consentement. Elle peut être dirigée vers l’orientation sexuelle, l’expression sexuelle ou de genre ou l’identité de genre d’une personne. Cela inclut l’agression sexuelle, le harcèlement sexuel, le harcèlement criminel, la cyberviolence, la distribution non consensuelle d’images sexuelles, le voyeurisme, etc. L’OSVRSE de McGill présente de plus amples renseignements sur la violence sexuelle sur son site Web. Définition dans la politique La définition officielle de la violence sexuelle adoptée à McGill se trouve à l’alinéa 7k) de la Politique contre la violence sexuelle de McGill : « Violence sexuelle » s’entend d’un ou de plusieurs actes sexuels, commis ou tentés, qui ciblent la sexualité, l’identité ou l’expression sexuelle d’une personne, ou toute menace de commettre de tels actes contre une personne sans son consentement. La violence sexuelle peut se manifester en personne, au téléphone ou en ligne. Elle englobe : i) l’agression sexuelle qui désigne un contact sexuel avec une autre personne sans son consentement; ii) le harcèlement sexuel, qui désigne une conduite de nature sexuelle A) selon laquelle l’activité sexuelle : est établie comme modalité ou condition explicite ou implicite d’emploi d’une personne ou de statut dans un cours, un programme ou une activité; ou est utilisée comme motif sous-tendant une décision en matière d’emploi ou d’éducation qui a des incidences sur une personne; OU, B) qui a pour effet de nuire au travail ou au rendement universitaire d’une personne quand il est reconnu, ou devrait être reconnu, que cette conduite est importune; iii) « traquer » qui désigne la surveillance ou le fait de suivre indûment une autre personne alors que cette personne, déposant une divulgation ou un signalement, a l’impression que cette traque a un lien avec le sexe ou l’identité sexuelle; iv) « exhibitionnisme » qui désigne l’exposition de ses organes sexuels à une autre personne dans un lieu public ou de manière menaçante ou choquante pour cette personne; v) « voyeurisme » qui désigne l’observation furtive ou l’enregistrement d’une personne au moyen d’un dispositif mécanique ou électronique; vi) « diffusion d’images sexuelles » qui désigne la distribution d’une image, photo ou vidéo de nature sexuelle d’une personne sans son consentement; et vii) « exploitation sexuelle » qui désigne l’abus ou l’exploitation de la sexualité d’une autre personne aux fins d’une gratification sexuelle, d’un gain pécuniaire, d’un avantage personnel ou à tout autre fin non légitime.
Keywords: Bibliographie; Nettoyer

Impact de la violence sexuelle sur la santé mentale - Centre d’Innovation en Santé Mentale sur les campus (2024)
Keywords: Bibliographie; Nettoyer

Salut ça va ? Dialoguer pour prévenir les violences sexuelles - Clermont-Dion, Léa (Cardinal, 2024)
Dans cet essai coup-de-poing, Léa Clermont-Dion s’adresse d’abord aux adolescents et aux jeunes adultes, à leurs parents et à leurs professeur.es, pour ouvrir la discussion sur les violences à caractère sexuel. Son but : éduquer et sensibiliser pour parvenir à des rapports humains respectueux et égalitaires, toujours en évitant de blâmer qui que ce soit. L’autrice vulgarise les concepts de consentement, de culture du viol, de masculinité toxique et explore la portée du mouvement #MeToo. Elle échange aussi avec des acteurs-clé du monde du sport, dont Laurent Duvernay-Tardif, ainsi qu’avec des intervenants du système de justice et recueille de bouleversants témoignages de victimes.
Keywords: Bibliographie; Nettoyer

Modèle de politique en matière de harcèlement psychologique ou sexuel au travail et de traitement des plaintes - Commission des normes de l'équité de la santé et de la sécurité du travail (CNESST) (2024)
Notre modèle de politique est présentement en cours de révision pour tenir compte des nouvelles dispositions prévues par la Loi visant à prévenir et à combattre le harcèlement psychologique et la violence à caractère sexuel en milieu de travail
Keywords: Bibliographie; Nettoyer

Justice réparatrice en matière de violence conjugale : Enjeux et recommandations - Conseil du statut de la femme (2024)
Keywords: Bibliographie; Nettoyer

Accueil - CRIPCAS (2024)
Centre de recherche interdisciplinaire sur les problèmes conjugaux et les agressions sexuelles
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Intermittents du spectacle - France Travail (2024)
Keywords: Bibliographie; Nettoyer

GRIP-Prévention - Groupe de recherche et d'intervention psychosociale (GRIP, 2024)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Collections - Groupe de recherche et d'intervention psychosociale (GRIP) (GRIP, 2024)
Le GRIP intervient en milieu festif (rave, festival) afin de réduire les méfaits associés à la consommation de drogues et de prévenir ses usages problématiques.
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Il était une fois... de trop - Institut national de l'image et du son. (2024)
Une formation pour prévenir le harcèlement en culture.
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Les professions de la culture et des communications au Québec en 2021 - Lubin, Marc-Ancy (Institut de la statistique du Québec, 2024)
Keywords: Bibliographie; Nettoyer

Michel Venne devra finalement prendre le chemin de la prison - Marin, Stéphanie (Le Devoir, 2024)
Keywords: Bibliographie; Nettoyer

Faire justice. Moralisme progressiste et pratiques punitives dans la lutte contre les violences sexistes - Marsault, Elsa Deck (Les Éditions du remue-ménage, 2024)

#UsToo: how Jewish, Muslim, and Christian women changed our communities - McGinity, Keren R. (Routledge, Taylor & Francis Group, 2024)
"#UsToo: How Jewish, Muslim, and Christian Women Changed Our Communities examines the relationship between sexual harassment, gender, and multiple religions, highlighting the voices of women of different faiths who found their voices and used them for the betterment of their communities. Through personal interviews and other research, this book explores the actions of American Jewish, Muslim, and Christian women who broke the silence about sexual misconduct and abuse of power by male co-religionists. Using a three-dimensional, ethnoreligious approach that examines gender, ethnicity, and religion, it addresses the relationship between religion and women's experiences and examines both historical contexts and present-day experiences of sexual misconduct within faith communities. This book will be of key interest to students within Gender Studies, History, Religion, and Sociology, clergy and lay religious leaders, and human rights advocates. Keren"–
Keywords: Christian women; Jewish women; MeToo movement; Muslim women; Sexual harassment of women; Social conditions; Women and religion

Sans consentement : trente scandales sexuels qui ont changé le Québec - Morin, Michel (2024)
Depuis l'arrivée de #MoiAussi et des autres mouvements de libération de la parole, on a assisté au Québec à une succession de scandales sexuels impliquant des personnalités publiques, figures respectées et influentes qui avaient abusé de leur pouvoir, parfois des décennies durant. Michel Morin fait un pas de côté pour revisiter ces histoires encore sensibles, en portant une attention particulière à leur traitement médiatique. Avocat de formation, il se penche aussi sur le fonctionnement du système judiciaire et son impact sur le processus de dénonciation. Sans s'ériger en juge, l'auteur laisse parler les faits, bien souvent accablants, dans un essai qui permet de prendre la mesure de ce qui a été trop longtemps ignoré, voire toléré, et du chemin qui reste à parcourir.
Keywords: Bibliographie; Nettoyer

Accueil - Opération cocon (2024)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Pour des milieux de travail exempts de harcèlement - Ordre des conseillers en ressources humaines et en relations industrielles agréés du Québec. (Carrefour RH, 2024)
Guide pour améliorer ses pratiques de prévention, d'intervention et de soutien dans des situations de harcèlement au travail.
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Les artistes remettent en question la distribution de l’argent public en culture - Paré, Étienne (Le Devoir, 2024)
Keywords: Bibliographie; Nettoyer

RÉZO - Rezo Santé (2024)
RÉZO est un organisme communautaire sans but lucratif montréalais actif depuis 1991 qui offre des services d’éducation et de prévention du VIH et des autres ITSS dans un contexte de promotion de la santé globale, notamment sexuelle, mentale, physique et sociale auprès des hommes GBQ, des autres hommes, et des personnes trans ayant des relations sexuelles avec des hommes.
Keywords: Coffre à outils; À ajouter

Les règlements officiels - Théâtre de la LNI - Théâtre de la LNI (2024)
Il est important de noter qu'il s'agit ici des règles d'origine du Match d'impro. La forme du Match d’impro a évolué et a fait l’objet de certains aménagements au fil des ans. Vous constaterez donc que certaines de ces règles ne correspondent pas à ce que vous avez pu voir lors des plus récents matchs

Mission et historique - Théâtre de la LNI - Théâtre de la LNI (2024)
Mission Réaliser l’impossible Innovation - Collaboration - Dépassement Le Théâtre de la Ligue Nationale d’Improvisation, qui est à la fois un laboratoire et une compagnie phare du théâtre québécois, se consacre à la recherche, la création et la transmission en improvisation théâtrale. La compagnie opte résolument pour une diversité de paroles et d’univers, cherchant avec

Soutien - TransEstrie (TransEstrie, 2024)
Keywords: Coffre à outils; À ajouter

Politique sur le respect des personnes, la prévention et l’intervention en matière de harcèlement - Université du Québec à Montréal (2024)
Keywords: Bibliographie; Nettoyer

Recenser, soutenir, agir - Alix (Alix, 2023)
Alix est là pour te soutenir ainsi que toutes les personnes qui interviennent auprès des personnes LGBTQ+ victimes de violence. Alix t’offre aussi des outils d’informations et de sensibilisation…
Keywords: Coffre à outils; À ajouter

Accounting For the Limited Success of #MeToo in the Popular Music and Stand-Up Comedy Industries - Worden, Chris; Gjika, Anna (Cultural Sociology, 2023)
Despite several high-profile cases and years of #MeToo activism, a lack of systemic change and consistent consequences for many alleged offenders has led journalists and fans to wonder when the popular music and stand-up comedy industries will truly have their ‘MeToo moment.’ In this article, we explain that this moment has already arrived, but has produced inconsistent results in these industries due to the unique cultural and structural obstacles they share, and which frustrate civil sphere actors’ attempts at civil repair. Our analysis draws on Jeffrey C. Alexander’s (2018, 2019) theory of societalization – the process by which institutional crises come to be seen as social problems that demand the intervention of civil sphere actors. We argue that where #MeToo and the popular music and stand-up comedy industries are concerned, the process of societalization has been (and will likely continue to be) ‘blocked’ or ‘stalled’ (Alexander, 2018, 2019). We suggest that the potential for societalization is reduced due to a combination of the arts sphere’s anti-civil values and weak institutionalization in the popular music and stand-up comedy industries.
Publisher: SAGE Publications
Keywords: Bibliographie

Capsule sur le GRIP, projet Spotlight (YouTube, 2023)
https://www.youtube.com/watch?v=vYWMiz8TISY
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Capsule Collectif Social (YouTube, 2023)
https://www.youtube.com/watch?v=w1m4Q65aRF8
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

L'Aparté - Formation ADISQ (2023)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Publicizing transgender ballet dancers: a pas de deux of inclusion and reiterative gender norms - Mandradjieff, Mara; Alterowitz, Gretchen (Feminist Media Studies, 2023)
Over the last decade, mainstream media sources from the US and UK have shown an increased interest in topics involving transgender and non-binary populations. Yet, their portrayals of such individuals tend to reaffirm rather than challenge cisnormative ideas surrounding bodies and gender. In this article, we consider this ongoing trend within the highly body-centric, traditionally-gendered artform—classical ballet. With a transgender studies and dance studies lens, we analyze current discourse surrounding the recent move for classical ballet companies and schools to adapt casting and training curricula to better include non-binary dancers. Through these analyses we reveal ways media sensationalizes the transgender body by focusing on information regarding hormone therapy and surgeries, and with the topic of ballet in mind, how this transphobic move becomes intertwined with ballet-specific processes of reshaping the body. We claim that although these popular press pieces contribute to a greater awareness of the lived experiences of transgender and non-binary dancers, they simultaneously reiterate ongoing balletic gender tropes that mark the artform as feminine and designate particular body types and movements to specific binarized genders.
Publisher: Routledge _eprint: https://doi.org/10.1080/14680777.2022.2149599
Keywords: Ballet; Bibliographie; Nettoyer; gender; media; non-binary; transgender

Accueil (Centre pour les victimes d’agression sexuelle de Montréal, 2023)
Le CVASM offre un soutien essentiel aux personnes touchées par la violence sexuelle depuis 1980. Trouvez de l'aide dès maintenant.
Keywords: Coffre à outils; À ajouter

Prévenir et gérer le harcèlement - Formations AQPM (Formations : Des classes de perfectionnement pour les professionnel-(le)s de l'industrie audiovisuel, 2023)
« Cette formation permettra aux producteurs et à leurs représentants de reconnaître les situations de harcèlement ou celles qui sont à risque de le devenir afin de comprendre les rôles et responsabilités qui leur reviennent. Les particularités propres à notre industrie y seront également abordées. Formateur: Me Frédéric Massé Borden, Ladner, Gervais »
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Écouter, informer, soutenir - Info-aide violence sexuelle (2023)
De l'écoute, du soutien et des références pour les victimes d’agression sexuelle, d’exploitation sexuelle et de toute autre forme de violence sexuelle.

Violences sexuelles: Le plan d’action des festivals - Trépanier, Marilou Bayard (La Presse, 2023)
Les allégations d’intoxication au GHB au Festi-Plage de Cap-d’Espoir, l’an dernier en Gaspésie, ont secoué les festivals partout au Québec. Elles ont aussi servi de bougie d’allumage : alors que les services sont implantés depuis quelques années à Montréal, le milieu festif en région se mobilise pour soutenir les victimes d’agressions et de harcèlement sexuels.

Accusations d’agression sexuelle et de diffamation: Jasmin Roy réplique et poursuit en diffamation Jean-François Robillard - Dussault, Lila (La Presse, 2023)
Un duel de poursuites en diffamation est en cours entre l’acteur Jasmin Roy et un homme qui l’accuse d’agression sexuelle, Jean-François Robillard. L’affaire a pris racine dans la foulée du mouvement #metoo, en 2020. Elle remonte à une soirée dans un bar d’Abitibi-Témiscamingue, 20 ans plus tôt.
Keywords: Bibliographie; Nettoyer

The art of Jane Orleman: childhood trauma and the discourse of sexual violence - Kwon, Hyunji (Journal of Gender Studies, 2023)
Jane Orleman (American, born 1942) is an artist and a survivor of child sexual abuse. Through paintings she created during therapy, Orleman rejects the gendered and patriarchal binaries between therapeutic art and professional art, which pit the private, feminine, and intuitive against the public, masculine, and intellectual. By analysing selected artworks from Orleman that embody her child self, young woman self, and alternative self, I propose that Orleman reflects on and challenges the pathology of sexual trauma along with the discourse of sexual violence as a political statement. Therefore, I argue that her art deserves to be part of a larger, counternarrative, anti-rape and anti-incest cycle in contemporary American art.
Publisher: Routledge _eprint: https://doi.org/10.1080/09589236.2022.2064838
Keywords: Sexual violence; art; survivor; therapy; trauma

Le délicat retour d’Éric Lapointe - Lemieux, Marc-André (La Presse, 2023)
Tapis rouge, apparition télé, concerts, nouvelle chanson, sortie d’album… Trois ans après avoir plaidé coupable pour voies de fait contre une femme et s’être éclipsé des grands circuits, Éric Lapointe retrouve, lentement mais sûrement, les projecteurs en 2023. Une opération fragile et non sans écueils possibles.

Un projet pilote pour réduire les risques d’intoxication et pour prévenir la consommation excessive (Éduc'alcool, 2023)
Montréal, le 21 avril 2023 – Éduc’alcool et le Service de police de la Ville de Montréal (SPVM) ont lancé hier le projet pilote Touche pas à mon verre* en présence du ministre de la Sécurité publique du Québec, M. François Bonnardel. Cette initiative prend la forme d’une distribution gratuite de 10 000 protège-verres afin de, notamment, […]
Keywords: Bibliographie; Dans le rapport; Nettoyer

The sound of misogyny: sexual harassment and sexual violence in the music industry - McCarry, Melanie; Käkelä, Emmaleena; Jones, Cassandra; Manoussaki, Kallia (Journal of Gender-Based Violence, 2023)
The cultural and creative industries are the fastest growing industries in the UK (). Stakeholder engagement, media reporting, anecdotal evidence and emerging research suggests that there are endemic levels of sexual harassment and sexualised violence within the music industry that can be described as widespread, systemic and normalised. This article reviews the literature on sexual harassment and sexualised violence in the music industry, examining gender stratifications and inequalities within the music industry with a focus on UK, Australian and US studies. The music industry is not a singular entity but instead, is an agglomeration of many different sub-sectors predominantly consisting of three interconnected spheres of music recording and distribution, music publishing and licensing, and live performance. This paper references Kelly’s (; ; ) theorisations on conducive contexts and the continuum of violence to argue that historical and entrenched misogyny and sexism along with the lack of regulation, process and governing frameworks create conditions for both the maintenance of gender inequality and the perpetuation of sexual harassment and sexualised violence within the music industry. Consequently, both the cultural context and the practice of misogyny (in this case sexual harassment and sexualised violence) within the music industry are mutually supporting and reinforcing.
Publisher: Policy Press Section: Journal of Gender-Based Violence
Keywords: Misogyny; Music; Myriam

Analyse critique du discours en ligne sur les dénonciations de violences à caractère sexuel : le cas de la liste de potentiels agresseurs, Dis son nom - Pelletier, Michela (Université du Québec à Montréal, 2023)
Les fils de commentaires sur Facebook permettent aux internautes de s’exprimer sur différents enjeux. Dans le cadre de ce mémoire, les fils de commentaires sous des articles médiatiques provenant de trois journaux (Journal de Montréal, Le Devoir et La Presse) trainant de la liste de présumés agresseurs Dis son nom ont été analysés. À partir d’une analyse critique de discours, 201 commentaires en réaction à 13 articles médiatiques ont été étudiés afin de répondre à la question de recherche suivante : « Quelles sont les représentations dominantes des dénonciations de violences à caractère sexuel sur les réseaux sociaux dans les commentaires Facebook en réaction aux publications d’articles médiatiques concernant la liste de potentiels agresseurs Dis son nom ? ». De ce fait, l’analyse critique de discours a permis l’étude des représentations dominantes au sein des commentaires Facebook au sujet des dénonciations de violences sexuelles sur les réseaux sociaux. Les résultats de la recherche ont relevé que les discours ont des perspectives davantage négatives au sujet des dénonciations en ligne et que la majorité de ces commentaires ont été partagés par des internautes identifiés comme hommes. L’analyse a illustré que certains commentaires soulignent une transformation et une déconstruction des discours hégémoniques en matière de genre, en permettant notamment une prise de parole émancipatrice. Néanmoins, la plupart des commentaires reproduisent ces discours hégémoniques. L’analyse a également permis de saisir les rapports de pouvoir présents dans les discours, de relever les implicites, les non-dits et les paradoxes, en plus de certains stéréotypes de genre liés aux violences sexuelles au sein des commentaires. _____________________________________________________________________________ MOTS-CLÉS DE L’AUTEUR : Dis son nom, Facebook, commentaire(s), réseaux sociaux, violences à caractère sexuel, violence(s) de genre, victime(s), #MoiAussi, culture du viol, Analyse critique de discours

Au-delà des « vagues » #moiaussi : cinq ans de mobilisation féministe en musique au Québec (2017–2022) - Blais-Tremblay, Vanessa; Champagne, Lysandre (Intersections, 2023)
Cet article dresse le portrait de cinq organisations qui militent pour l’équité en musique au Québec depuis 2017 : MTL Women in Music, Femmes* en Musique, Lotus collective MTL Coop, shesaid.so MTL et le réseau DIG! Différences et inégalités de genre dans la musique au Québec. En s’inscrivant d’abord dans la longue lignée des travaux critiques en historiographie féministe, l’article rend compte de la pluralité des mobilisations féministes et ce, au-delà des « vagues » #moiaussi qui ont ponctué l’actualité musicale québécoise au cours des cinq dernières années (2017–2022). Dans la seconde partie, les autrices détaillent les travaux du réseau D!G , lancé en avril 2021 par Vanessa Blais-Tremblay, et présentent des retombées initiales prometteuses à la fois pour le milieu universitaire et pour les milieux de pratique en ce qui concerne l’épistémologie et les méthodologies de la « musicologie partenariale collaborative féministe ». , This article profiles five organizations that have been advocating for equity in Quebec music since 2017 : MTL Women in Music, Femmes* en Musique, Lotus collective MTL Coop, shesaid.so MTL and D!G Différences et inégalités de genre dans la musique au Québec. In line with a long tradition of critical work in feminist historiography, the authors first account for the diversity of feminist mobilizations in Quebec music beyond the #metoo “waves” which have received significant media attention over the past five years (2017–2022). In the second part, the authors detail the development of the D!G network, a feminist collaborative research partnership launched in April 2021 by Vanessa Blais-Tremblay, and its contributions to both Quebec’s music industry and to feminist partnership research epistemologies and methodologies.
Keywords: Bibliographie; Nettoyer

Unsettling homocolonial frames of remembrance: Two-Spirit and Indigiqueer interventions at the museum - Failler, Angela (Memory Studies, 2023)
This article considers a Two-Spirit and Indigiqueer protest at the Canadian Museum for Human Rights as a flashpoint that exposes problems with how memory-making institutions are incorporating lesbian, gay, bisexual, trans and queer issues into their programming and/or collections. The protest brings into relief the museum’s investment in a homocolonial framing of remembrance for the way in which the telling of lesbian, gay, bisexual, trans and queer ‘progress’ is entangled with a settler colonial political economy wherein the tokenistic inclusion of some queers into the sexual citizenry happens alongside the dispossession, devaluing and criminalizing of others. I then undertake some preliminary ‘curatorial dreaming’ upon two other interventions–commentaries uploaded to a digital story bank by a Two-Spirit and an Indigenous queer museumgoer, and the short film Woman Dress by Plains Cree artist TJ Cuthand. Along with the protest, the commentaries and the film unsettle homocolonial frames of remembrance and provide critical openings towards decolonial queer memory work at the museum.
Keywords: Bibliographie; Nettoyer

Plus jamais silencieuses : essai d'activisme social contre l'oppression de genre par la réalisation d'une oeuvre vidéographique documentaire et participative - Pierret, Caroline (Université du Québec à Montréal, 2023)
Tenant compte de l’émergence de la parole et de l’écoute libérées par les médias sociaux lors des mouvements MeToo et de la séquence de dénonciations d’agression à caractère sexuel qui s’ensuivit au Québec comme ailleurs en Occident, comment aujourd’hui un projet artistique peut-il participer à l’affranchissement de la parole et du visage des femmes? Ce mémoire-création explore les notions de silenciation et d’invisibilisation des femmes, en même temps que les possibilités pour elles de s’en libérer en reprenant contact avec leur puissance, notamment par un usage conscient des instruments médiatiques que sont le cinéma, la vidéo, la photographie et la transmission audio. Il décrit différentes méthodologies testées par la réalisation de projets au cours du programme de maîtrise, tous cherchant à comprendre comment, par la captation de voix et de visages, il est possible d’offrir aux femmes une opportunité de réappropriation de leur pouvoir individuel et collectif. Cette recherche-création culmine dans une installation vidéographique documentaire réalisée en collaboration avec dix-neuf Montréalaises originaires de dix pays différents, qui permet de faire vivre aux personnes spectatrices une expérience de rencontre et de leur faire prendre conscience du trouble qui habite l’intérieur des femmes, et ainsi possiblement le leur. Ce faisant, l’oeuvre pose la question cruciale de ce que nous ne voyons pas, n’entendons pas, ne ressentons pas ou n’avons jamais voulu voir, entendre ou ressentir. _____________________________________________________________________________ MOTS-CLÉS DE L’AUTEUR : vidéo, documentaire, femmes, silence, parole, écoute, metoo, féminisme, activisme, agentivité.
Place: Montréal (Québec, Canada) Publisher: Université du Québec à Montréal
Keywords: À ajouter

Diversity, Equity, Inclusion & Belonging Committee (ACTRA National, 2023)
ACTRA National’s Diversity, Equity, Inclusion & Belonging Committee promotes the principles concerning the casting of People of Colour, Indigenous Peoples and people with disabilities. The best initiatives are driven by members. We can better shape initiatives to support you by getting to know our membership and understanding your experiences. We welcome your input and your […]
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Entente collective 2023-2026 entre la Guilde des musiciens et musiciennes du Québec et l'Orchestre l'Agora (2023)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Entente collective 2023 - 2027 entre la Guilde des musiciens et musiciennes du Québec et l’Orchestre symphonique du Saguenay-Lac-Saint-Jean (2023)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Plan d'action pour les ressources humaines en culture 2023-2028 (Compétence Culture, 2023)

Progress Pride Committee (ACTRA National, 2023)
ACTRA National is proud to be launching the ACTRA National Progress Pride Committee. The inaugural Committee meeting took place on Friday, May 26th, 2023. Mandate The mandate of the committee is to address issues that impact the Queer ACTRA membership across the country, and to build a National community through the sharing of relevant information […]
Keywords: Bibliographie; Dans le rapport

Rebâtir (2023)
Consultation juridique sans frais pour les personnes victimes de violence sexuelle et de violence conjugale.
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Réseau d'aide aux hommes pour une société sans violence (À coeur d'homme, 2023)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Women's Committee (ACTRA National, 2023)
The best initiatives are driven by members. By getting to know the membership and listening to your experiences, we can better shape initiatives that support you. Does your ACTRA Branch have a Women’s Committee? Find out by contacting your Branch office or contact the National Women’s Committee if you would like to get one started. […]
Keywords: Bibliographie; Dans le rapport

ACTRA By-Laws - ACTRA (2023)
Keywords: Coffre à outils; À ajouter

Harcèlement et inconduites dans le milieu artistique. Quel est mon rôle ? - ADISQ; RIDEAU (2023)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Code d'éthique - Association nationale des éditeurs de livres (ANEL) (2023)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Code d'éthique - Association québécoise de l'indusstrie du disque, du spectacle et de la vidéo (ADISQ) (2023)
Keywords: Bibliographie; Nettoyer

Believability: sexual violence, media, and the politics of doubt - Banet-Weiser, Sarah; Higgins, Kathryn Claire (Polity Press, 2023)

Unsafe words: queering consent in the #MeToo era - Buggs, Shantel Gabrieal; Hoppe, Trevor (Rutgers University Press, 2023)
"What can the #MeToo moment teach queers about consent? And what can queers teach the rest of the world about ethical sex? This radical book brings together academics, activists, artists, and sex workers to tackle dangerous questions about sex, power, consent, and harm.While the authors in this volume are committed to promoting consensual, pleasurable sex, we reject heteronormative, one-size-fits-all models of consent and sexual ethics.#MeToo ushered in an era of reckoning and accountability for one powerful man after another. But too often it has defined sex and harm in starkly heterosexual-and often white and wealthy-terms."Unsafe Words" tells a queerer side of the #MeToo story. Not all of us seek safety in sex. Nor do we all believe "enthusiastic" models of consent are practical or appropriate for some queer communities. We look instead to the tools queer communities have developed themselves to practice ethical sex-from the sex worker negotiating with her client to the gay man having anonymous sex in the backroom. We also consider how queers can better respond to sexual violence. How can our communities do better at responding to and preventing sexual violence?This challenge is especially daunting in a world where the only recourse made available is typically law enforcement, a pillar of American racism, transmisogyny, and homophobia.How can our communities imagine different responses to sexual violence that do not depend on the law to serve justice?The "unsafe words" in this volume challenge dogmatic assumptions about sex and consent while exploring tools and language to promote better, more ethical, and more pleasurable sex for everyone"– Provided by publisher

3 M$ à Juripop pour venir en aide aux victimes de harcèlement et de violence dans le milieu culturel - Cabinet du ministre de la Culture et des Communications et ministre responsable de la Jeunesse (Gouvernement du Québec, 2023)
Keywords: Bibliographie; Dans le rapport; Nettoyer

The other #metoos - Cheema, Iqra Shagufta (Oxford University Press, 2023)
"To bring more awareness to the revolutionary international impact of #MeToo, The Other #MeToos brings together chapters that look at specific iterations of the #MeToo movement across multiple communities, cultures, and countries. Going beyond gender, the book takes into account the intersectional assemblage of location, history, religion, ethnicity, race, class, and neoliberal aspects that inform #MeToo and its place in local and transnational feminisms. From Egypt, Lebanon, Iran, Tunisia, and Morocco to India, Pakistan, Bangladesh, Nepal, and Sri Lanka to South Africa to Latin America to South Korea, Japan, and China to Czech Republic - #MeToo has inspired local movements and hashtag trends as well as transnational and collective hashtags like #MosqueMeToo. Therefore, by making feminism mainstream, it has rendered possible international feminist solidarities unlike any other feminist movement that precedes it. It is critical to document this defining feminist moment of #MeToo and its variants to acknowledge the diversity and multidimensionality of transnational feminisms, along with looking at the various ways they have been changed by the #MeToo, internationally. To that argument, the contributions in this collection examine, analyze, and interrogate the reception, translation, and adaptation of #MeToo in their local, indigenous, minoritized, othered, and/or postcolonial contexts. Overall, The Other #MeToos highlights the adaptation, translation, and impact of #MeToo in non-Western, postcolonial, minoritized, and othered locales to expand the larger discourse and praxes of the #MeToo movement beyond its Americentric focus to explore other feminist possibilities that the movement has enabled"–
Keywords: Feminism; MeToo movement; Sexual harassment of women

Porter plainte: récit - Clermont-Dion, Léa (Le Cheval d'août, 2023)
"Agressée sexuellement par son patron à l'âge de dix-sept ans, Léa Clermont-Dion décide, près d'une décennie plus tard, de poursuivre l'agresseur en justice. Elle consignera son expérience dans son journal jusqu'au procès. Pendant ce temps, l'affaire Harvey Weinstein déclenche le mouvement #MeToo, et des millions de femmes dénoncent la culture du viol à visage découvert. La déposition criante de vérité de Porter plainte témoigne de la froide autorité du droit et des luttes des victimes de crimes sexuels, qui reprennent la parole qu'on leur a soustraite"–Back cover
Keywords: Bibliographie; Nettoyer

Les premier·ères coordonnateurs et coordonnatrices d’intimité certifié·es du Québec - Coordination d'intimité Québec (ICCQ, 2023)
Les coordonnateurs et coordonnatrices d'intimité pour le cinéma et la télévision. Formé·e·s par les programmes de certification qui ont établi le standard du rôle à l'international et ailleurs au Canada, Mo Matton, Stephanie Breton et Mimi Côté représentent la branche du Québec d'Intimacy Coordinato
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Mettre fin au harcèlement sexuel dans le cadre du travail : Se donner les moyens pour agir - Cox, Rachel; Gesualdi-Fecteau, Dalia; Laflamme, Anne-Marie (Comité chargé d'analyser les recours en matière de harcèlement sexuel et d'agressions sexuelles au travail, 2023)
Keywords: Bibliographie; Nettoyer

Challenging gendered power: How sexual harassment perpetrators respond to victim confrontation - Crowley, Jocelyn Elise (Gender, Work & Organization, 2023)
Sexual harassment is a problem that continues to plague mostly women in the American workforce today. One tool that victims can use in these situations is confrontation, either through verbal or physical means. Yet, understudied to this point is how perpetrators respond to confrontation, which is highly salient as to whether this is an effective tool for victims. This study uses grounded theory methods to analyze 31 accounts of sexual harassment from within the fashion industry that recorded perpetrators' responses to victim confrontation to clearly unwanted, abusive behavior. I argue that specific features of the fashion industry, or a “display work culture,” embolden perpetrators to effectively thwart any type of confrontation. Indeed, this study finds that these predominantly male perpetrators of sexual harassment moved to reassert their dominant position over their female victims in the moment of confrontation, immediately after being confronted, and even later, well beyond confrontation, as they aimed to reestablish normal business practices as usual. This research thus dispels a significant sexual harassment myth that victims working within this culture are able to stop perpetrators simply by speaking up and/or fighting back and points to the need for the development of sexual harassment theory to incorporate work culture-related risk factors and remedies.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/gwao.12906
Keywords: Bibliographie; Myriam; Nettoyer; confrontation; display work culture; fashion industry; perpetrators; sexual harassment

Faire justice: moralisme progressiste et pratiques punitives dans la lutte contre les violences sexistes - Deck Marsault, Elsa (La Fabrique éditions, 2023)
Keywords: Bibliographie; Nettoyer; Restorative justice; Sexual minorities; Violence against; Women

Bureau d'intervention et de prévention - École nationale de cirque - Montréal (École nationale de cirque, 2023)
Le BIP de l'ÉNC vise à prévenir et intervenir en cas de discrimination, de harcèlement et de violence au sein de son établissement.
Keywords: Sophie-Anne

Pollitique contre le harcèlement et l’intimidation et la promotion d’un environnement sain - École nationale de théâtre du Canada (Département du bureau de la direction générale, 2023)
Keywords: Bibliographie; Nettoyer

SPEAK OUT: together for a safer circus - Fédération européenne des écoles de cirque (FEDEC); JUMP (2023)
Keywords: Bibliographie; Nettoyer; Sophie-Anne

Working girl: on selling art and selling sex - Giovannitti, Sophia (Verso, 2023)
"Giovannitti argues that if we delve into our anxieties around art and sex, we can find new ways to live and spaces of freedom"–
Keywords: Bibliographie; Nettoyer

Between denunciations and precautions: the #Metoo movement in Quebec. A Critical Discourse Analysis of Quebec newspaper coverage in 2020 and 2017 - Glorieux, Charlotte (Université Charles, 2023)
Keywords: Bibliographie; Nettoyer

Campagne de sensibilisation : Harcèlement au travail - Groupe d’aide et d’information sur le harcèlement sexuel au travail de la province de Québec (GAIHST, 2023)
GAIHST Inc est un organisme communautaire de la province de Québec qui vient en aide aux travailleurs et travailleuses ayant subi du harcèlement au travail.
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Répertoire des formations de groupe - Groupe de recherche et d’intervention psychosociale (2023)
«Les formations qu’on offre s’adressent principalement aux professionnel.le.s des milieux scolaires, secondaires et postsecondaires et aux professionnel.le.s de milieux variés où l’information sur les drogues est pertinente (milieux festifs, milieux d’intervention, etc.). Elles peuvent également être offertes directement à la population étudiante des milieux d’éducations postsecondaires (Formation générale aux adultes, formation professionnelle, collégiale ou universitaire). L’approche employée dans la création et l’offre de formation est toujours celle de réduction des méfaits. Nos formations abordent des thèmes tels que les violences à caractère sexuel, le consentement, les effets des substances, la prévention et la réduction des méfaits, les bandelettes de détection de Fentanyl et Naloxone, l’intervention en milieu festif, les drogues et la performance académique, ainsi que de nombreux autres sujets pertinents. »

Can Rainbow Become the New Pink? A study of ballet educators’ responses to the advancement of LGBTQ+ rights - Hawkes, Tracey (Researching Education Bulletin : Creative Arts Special Edition, 2023)
Keywords: Bibliographie; Nettoyer

Étude sur l’expérience des adultes ayant reçu des services dans le cadre d’un processus judiciaire : Dossiers judiciarisés entre juillet 2020 et juin 2022 au Québec concernant une infraction commise dans un contexte de violence conjugale ou sexuelle - Institut de la statistique du Québec (2023)
Keywords: Bibliographie; Nettoyer

Accueil - Juripop (L'Aparté, 2023)
L'Aparté offre des services juridiques gratuits à toute personne ayant vécu du harcèlement dans le milieu de la culture partout au Québec
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Collectif social collective - Le Collectif social (Lutte contre les violences sexuelles, 2023)
Offrent des formations sur mesure, ainsi que les formations : - Prévenir la violence sexuelle dans les événements festifs ou sociaux - Les violences sexuelles chez les communautés LGBTQIA2S+ - Devenir un témoin actif
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Check tes chums - Massé, Manon (Facebook, 2023)
Keywords: Bibliographie; Nettoyer

Stratégie en matière de justice autochtone : Ce que nous avons appris Phase 1 de la mobilisation dirigée par le ministère de la Justice Canada - Ministère de la justice Canada (2023)
Keywords: Bibliographie; Nettoyer

Que reste-t-il de nos humours ?À la recherche d’un rire de gauche - Quemener, Nelly (Revue du Crieur, 2023)
Les enjeux liés aux luttes menées par les personnes trans’ sont une parfaite illustration du fait que la visibilité ne suffit pas et qu’elle peut même parfois se révéler préjudiciable. En effet, depuis quelques mois, la presse, la télévision, la radio s’agitent dès qu’une actualité touche de près ou de loin à la transidentité. Actuellement, les voix des trans’ sont encore trop souvent couvertes par les discours cis’, lesquels tendent également à délégitimer les savoirs produits par et pour des trans’. Il est grand temps de retourner la lunette : au lieu de scruter les personnes trans’ – leur transition –, il est urgent de les lire et de les écouter. Ces expériences-là ont certes des choses à apprendre aux personnes cis’ : bien sûr que l’on comprend mieux ce qu’est le genre face à des personnes qui ont fait l’expérience de quitter celui qui leur a été assigné à la naissance, bien sûr que cela rend plus insupportable encore la rigidité des normes de genre, binaires et arbitraires jusqu’à l’absurde. Mais au-delà de ce que les cis’ peuvent apprendre des trans’ pour mieux se comprendre elles-mêmes et eux-mêmes, au-delà de cette lecture instrumentale, il s’agit désormais de laisser les marges parler. Il s’agit de se concentrer sur les luttes sociales, les revendications portées par les personnes trans’ et les associations, de défendre les conditions matérielles d’existence des trans’, de lutter contre les nombreuses discriminations qui pèsent encore sur elles et eux, y compris contre celles qui limitent drastiquement leur accès aux positions permettant de produire légitimement du savoir, il s’agit de les laisser libres de définir leurs cadres de pensée et la manière dont ils, elles, iels souhaitent parler ou pas de leurs parcours. De les laisser, enfin, écrire leur histoire.
Place: Paris Publisher: La Découverte

Les pratiques des directrices l'industrie de la musique au Québec pour naviguer entre les exigences multiples de leurs fonctions - Saucier, Myriam (Université du Québec à Montréal, 2023)
Keywords: Bibliographie; Nettoyer

En réponse à : « Check ton verre » - Scène & Sauve (Facebook, 2023)
Keywords: Bibliographie; Nettoyer

POLITIQUE ÉDI (ÉQUITÉ, DIVERSITÉ, INCLUSION) - Télé-Québec (2023)
Keywords: Coffre à outils; À ajouter

#metoo: The Good, the Bad, and the Backlash - Tranchese, Alessia (From Fritzl to #metoo: Twelve Years of Rape Coverage in the British Press, 2023)
I start this discussion in this chapter with an outline of the key points within the #metoo debate, looking at what, according to various scholars, has and has not been achieved since the hashtag went viral in 2017. This overview constitutes the context for the subsequent analysis and critical evaluation, which will look at how the press conceptualised #metoo, and how it shaped some of the wider discussions about the hashtag. In Chapter 11, it will focus on whether (and how) the widespread use of #metoo after 2017 affected the representation of violence against women in the British press compared to the previous years.
Keywords: Irina

Comedy’s double killjoy: workers’ DIY strategies to address harassment and precarity in the comedy industry - Trusolino, Madison; Ships, Diandra (Feminist Media Studies, 2023)
Since 2017, the #MeToo movement has highlighted gender-based violence and harassment in the comedy industry, where those comedians affected have little to no workplace infrastructure to lean on. Because comedy clubs are described as venues rather than sites of work, comedy workers are not technically employees and are not protected by workplace safety laws nor supported by professional organizations or unions. We argue that the lack of a formal workplace and its related precarity exacerbates violence against women, queer, transgender, disabled, and/or workers in the Canadian and American comedy industries, pushing comedy workers to enact do-it-yourself workplace safety strategies to protect themselves and one another. We describe these protective, caring activities as akin to Brenda Parker’s “double killjoy,” and push our understanding of creative work into places of public resistance and life-making.
Publisher: Routledge _eprint: https://doi.org/10.1080/14680777.2023.2229055
Keywords: Bibliographie; Nettoyer; Sophie-Anne

Now About All These Women in the Swedish Film Industry - Wallenberg, Louise; Papadopoulou, Frantzeska; Koskinen, Maaret; Soila, Tytti (Bloomsbury Academic, 2023)
In the aftermath of the MeToo movement, during an ongoing pandemic, and in the midst of repeated demands for a 50/50 split between men and women in above-the-line positions, this book analyzes and interrogates the politics of gender focusing on the Swedish film industry, often considered to be the most "gender equal" film industry worldwide. While this gender equality (with a considerable proportion of women behind the camera) is much due to policies carried out of the state funded Swedish Film Institute, women filmmakers in Sweden still struggle with the same problems as do women in other national film industries. These problems entail having smaller production and distribution budgets than men and working in an environment involving recurring scandals of gender discrimination and sexual harassment. This open access book looks behind the statistics and explores the often complex cultural, legal, and political conditions under which women have entered a male-dominated industry and discusses women’s strategies and efforts to promote change while providing evidence on how women’s presence has challenged the industry by provoking critical reactions and introducing new ways to portray women on screen. Using a wide range of different sources (e.g. archival material, laws, contracts, films, biographical materials, and interviews), the book tells the history of the rise of gender equality efforts undertaken by the Swedish Film Institute and investigates women’s possibilities to manage the rights to their work. It offers compelling portraits of pioneering women who have worked in or in relation to the industry and looks at the experiences of women currently working in the film industry. The ebook editions of this book are available open access under a CC BY-NC-ND 4.0 licence on bloomsburycollections.com. Open access was funded by Örebro universitet.
Accepted: 2023-02-09T13:06:14Z
Keywords: Irina; Metoo; Sweden; Swedish Film Institute; TV & radio::APF Films; change; cinema::APFA Film theory & criticism; cinema::APFN Film: styles & genres; conditions; discrimination; equality; film industry; filmmakers; male-dominated; pioneering; politics of gender; rights; scandal; sexual harassment

Against Sexual Violence in the Museum: Art, Curating, and Activism - Perry, Lara; Krasny, Elke (Journal of Cultural Analysis and Social Change, 2022)
Depictions of sexual violence are frequently found in the collections and displays of art museums, and material that represents and affirms violence against women often is displayed unchallenged. This article poses questions about how the presence of this material has been addressed in the relations between feminist activism against sexual violence, art made by artists responding to and participating in feminist activism, and the curatorial activities that have arisen to address the challenges that these activities present to art museums. The chapter investigates the 2021 exhibition Titian: Women, Myth and Power at the Isabella Stewart Gardner Museum and its handling of themes of rape in the central exhibit, Titian’s Rape of Europa; the history of themes of rape in feminist art since the 1970s and in exhibitions of this art that have taken place in museums in the last two decades; and curatorial engagements with sexual violence and rape in recent art exhibitions in the US and in the UK. The article argues that new strategies for the presentation and interpretation of artworks dealing with sexual violence are needed for museums to redress the patriarchal and colonial presence of sexual violence in their collection.
Keywords: Art Curating; Fine Arts; Museum; Museum Violence; Myriam; Rape; Sexual Violence; Visual activism

Femmes de spectacle au XIXe siècle - Ponzetto, Valentina; Fix, Florence (2022)
Quelle est la place des femmes dans l’industrie du spectacle du XIXe siècle au-delà des métiers de performance très exposés qu’exercent les actrices, ...
ISSN: 1376-3199
Keywords: Sophie-Anne

#MeToo et la justice réparatrice (Curio.ca, 2022)
Ça fait plus de 5 ans que le mouvement #MeToo (#MoiAussi) a commencé. Depuis, de nombreuses victimes de crimes sexuels critiquent notre système de justice traditionnel. Mais il existe une autre solution, fondée sur des principes et des processus autochtones : la justice réparatrice. Comment fonctionne-t-elle exactement? Tom-Éliot Girard est …
Keywords: Coffre à outils; Nettoyer; À ajouter

La Circassienne: A Study of the Female Circus Artist in French Literature - Menninga, Crystal (Masters Theses, 2022)

Edgar Fruitier est libre après moins d’un mois de prison - Radio-Canada (Radio-Canada, 2022)
Son risque de récidive est jugé faible en raison de son état physique et mental.
Publisher: Radio-Canada.ca
Keywords: Bibliographie; Nettoyer

Le mouvement #MoiAussi et ses événements marquants - Pineda, Améli (Le Devoir, 2022)
En octobre 2017 émergeait un mouvement de dénonciation planétaire.
Keywords: Bibliographie; Nettoyer

La littérature après #MoiAussi - Hébert-Dolbec, Anne-Frédérique (Le Devoir, 2022)
Le milieu littéraire attend encore des changements structurels importants, cinq ans après le début du mouvement.
Keywords: Bibliographie; Nettoyer

Politique visant à prévenir et combattre les violences à caractère sexuel - École nationale de théâtre du Canada (2022)
Keywords: Bibliographie; Nettoyer

Une nouvelle accusation contre Eddy Toussaint: Son école de danse change de nom pour se dissocier du chorégraphe - Duhamel, Frédérik-Xavier (La Presse, 2022)
Alors que le chorégraphe Eddy Toussaint fait face à une deuxième accusation d’agression sexuelle, l’école et la troupe de ballet qu’il a fondées prennent leurs distances et changent de nom. Des spectacles ont aussi été retirés de l’affiche dans la foulée des accusations, mais la direction estime qu’il est injuste de pénaliser les danseurs.
Keywords: Bibliographie; Nettoyer

Violences à caractère sexuel: Les actes « graves » de Samuel Archibald - Perron, Louis-Samuel (La Presse, 2022)
L’écrivain réputé Samuel Archibald a profité de son statut de professeur de littérature pour avoir des relations sexuelles avec deux étudiantes sous son autorité, conclut une enquête indépendante commandée par l’Université du Québec à Montréal (UQAM). Une de ces femmes l’accuse même de l’avoir étranglée lors d’une relation sexuelle non consentie. Des actes « graves » et « hostiles » qui ont mené à son départ en catimini de l’UQAM l’an dernier.
Keywords: Bibliographie; Irina; Nettoyer

La relation de pouvoir entre un professeur et ses étudiantes - Radio-Canada (Tout un matin, 2022)
Tout un matin | L'ex-professeur de littérature Samuel Archibald aurait commis des « violences à caractère sexuel » et du « harcèlement sexuel » envers deux étudiantes avec lesquelles il était en situation d'autorité en tant que directeur de maîtrise. Le lien d'emploi entre l'auteur et l'Université du Québec à Montréal (UQAM) aurait été rompu l'année dernière. Au micro de Tout un matin, Rachel Chagnon, professeure au Département des sciences juridiques de l'UQAM, définit ce qu'est une relation de pouvoir entre un enseignant et un étudiant (ce sont majoritairement des femmes), principe qui se trouve au cœur de la politique de l'université pour prévenir et combattre les violences à caractère sexuel.
Keywords: Bibliographie; Nettoyer

Une présumée victime d’agression sexuelle poursuivie en diffamation pourra rester anonyme - Marin, Stéphanie (Le Devoir, 2022)
Au coeur de la poursuite : une publication dénonçant l’humoriste Alexandre Douville sur la page Dis son nom.
Keywords: Bibliographie; Nettoyer

Allégations d’agressions sexuelles contre Win Butler : des radios boycottent Arcade Fire - ICI.Radio-Canada.ca, Zone Arts- (Radio-Canada, 2022)
Trois femmes font état d’interactions inappropriées, une autre dit avoir été agressée sexuellement en 2015.
Publisher: Radio-Canada.ca

Working with “monstrous men”: ambivalent sexism in the Bombay film industry - Sanchez Lozoya, Zeltzyn Rubi (Feminist Media Studies, 2022)
In India, the 2012 Delhi gang rape case catalyzed protests for women’s rights, particularly in regard to their safety. These demands were rekindled with vigor anew with the eruption of the #MeToo movement. In the Indian film industry, the most visible change appeared in the gradual increase of films with womenleads. But behind the scenes, there has been comparatively less change in female representation. Currently, approximately less than 10% of film directors in India are women. Considering the impor tance of having stories about women being made by women, in this article I examine the factors that hinder women’s entrance and tenure in the Mumbai film industry. I argue that a composite of concerns, including but not limited to reputability and personal security, thwarts women’s progress in the industry. I base my con clusions on interviews with women and men working in the film industry, conducted in Mumbai in 2017. I use the framework of the Ambivalent Sexism Index developed by psychologists Glick and Fiske in 1996, and revised in 2013, (1996, 2001, 2013) to examine my interviewees’ encounters with hostile and benevolent sexism. This article complicates our understanding of the reasons that limit the work of women beyond explanations of overt discrimination.
Keywords: Irina

Sex and safety on set: intimacy coordinators in television drama and film in the VOD and post-Weinstein era - Sørensen, Inge Ejbye (Feminist Media Studies, 2022)
This article examines the work of intimacy coordinators on television drama and film sets and the rise of this new role in the screen industry from a policy and production studies perspective. Since HBO made the employment of an intimacy coordinator mandatory on all productions with scenes of sex, nudity, and physical intimacy in 2018, intimacy coordination has become an industry standard and expectation. Through interviews and analysis of production practices, this article explores how intimacy coordinators change and challenge established production practices on and off set and interrogates the reasons behind the emergence of this role in the screen industry. It situates intimacy coordination in the context of recent industry policies and initiatives that promote equality and diversity, and counter harassment and abuse in the post-Weinstein era. It analyses this role on relation to changing production and distribution models and regimes in the era of VOD portals. The article argues that intimacy coordination is not only a catalyst for reforming practices on set, but a way for the screen industry to negotiate contemporary and historic concerns about sexual harassment and abuse, comply with recent policy and funding requirements, and a mechanism for mitigating economic and reputational risk to productions.
Publisher: Routledge _eprint: https://doi.org/10.1080/14680777.2021.1886141
Keywords: #MeToo; Intimacy Coordination; Irina; Prévention; VOD; equality; screen industries

Humoristes cherchent « safe spaces » - Blais-Poulin, Charles-Éric (La Presse, 2022)

Laughter from the Sidelines: Precarious Work in the Canadian Comedy Industry - Trusolino, Madison (Creative Industries in Canada, 2022)
Creative Industries in Canada is a foundational text that encourages students to think critically about creative industries within a Canadian context and interrogate the current state and future possibilities of the industry. While much of current creative industries literature concerns the United Kingdom, the United States, and Asia, this text captures the breadth of how Canadian industries are organized and experienced, and how they operate.This ambitious collection aims to guide students through the current landscape of Canadian creative industries through three thematic sections. “Production” collects chapters focused on how national discourses and identities are produced through creative industries and the tensions that exist between policy and media. “Participation” explores how we engage with these industries in different roles: as consumer, creator, policy-maker, and more. “Pedagogies” explores how education impacts inclusion and visibility in creative industries.Truly intersectional, Creative Industries in Canada provides students with practical industry knowledge and frameworks to explore the current state of the field and its future. With a broad application to many undergraduate programs, this text is a must-read resource for those pursuing media studies, arts management, creative and cultural industries studies, communications, and arts and humanities.
Keywords: Bibliographie; Business & Economics / Industries / Media & Communications; Nettoyer; Social Science / Media Studies; Sophie-Anne

Gros été pour la culture du viol - Elkouri, Rima (La Presse, 2022)
Nouveau scandale de viol collectif à Hockey Canada. Allégations d’inconduites sexuelles contre l’humoriste Philippe Bond. Absolution conditionnelle pour l’ingénieur Simon Houle coupable d’agression sexuelle…
Keywords: Bibliographie; Nettoyer

Philippe Bond était déjà sur des listes noires - Bélanger, Cédric (Le Journal de Québec, 2022)
L'humoriste Philippe Bond était déjà depuis plusieurs années sur la liste noire de grandes organisations culturelles.
Keywords: Bibliographie; Nettoyer

Allégations d’agressions et d'inconduites sexuelles visant Julien Lacroix (2022)
Lisez tous nos articles, analyses et opinions sur les allégations d’agressions et d'inconduites sexuelles visant Julien Lacroix. Le Devoir, le quotidien indépendant par excellence au Québec depuis 1910.

Julien Lacroix, Maripier Morin... Le retour des personnalités dénoncées fait mal - Cazzaniga, Constance (Métro, 2022)

What else can a crush become: working with arts-methods to address sexual harassment in pre-teen romantic relationship cultures - Huuki, Tuija; Kyrölä, Kata; Pihkala, Suvi (Gender and Education, 2022)
Keywords: Myriam

Capsules sur le harcèlement au travail - Groupe d’aide et d’information sur le harcèlement sexuel au travail de la province de Québec (GAIHST, 2022)
Le Groupe d’aide et d’information sur le harcèlement au travail (GAIHST) lance 5 capsules vidéo dédiées aux travailleurs(euses) du Québec.
https://gaihst.qc.ca/capsules
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Que fait #MeToo à la littérature ? - Zenetti, Marie-Jeanne (Revue critique de fixxion française contemporaine, 2022)
Que fait #MeToo fait à la lecture, à la critique et à l’enseignement des textes littéraires ? Le mouvement #MeToo a contribué à une large prise de conscience quant aux enjeux linguistiques liés aux violences sexuelles et sexistes : lutter contre de ces violences suppose d’abord de nommer un viol un viol. Mais une telle exigence de désambiguïsation peut entrer en contradiction avec la complexité interprétative valorisée dans le cadre de la lecture littéraire. Elle présenterait par ailleurs le risque d'inviter à lire des textes éloignés de nous dans le temps et l’espace en les évaluant à l’aune de notions et d’une morale contemporaines jugées anachroniques. Prolongeant les réflexions récentes de Gisèle Sapiro (Peut-on dissocier l’œuvre de l’auteur ?) et d’Hélène Merlin-Kajman (La littérature à l’ère de MeToo), cet article étudie la réception du récit de Vanessa Springora, Le consentement (2020). En interrogeant la polarisation des discours critiques et théoriques entre une lecture “féministe” et une lecture “littéraire” parfois présentées comme incompatibles, il pose la question du lien possible entre violences sexuelles et pratiques interprétatives. Il théorise une pratique de lecture soucieuse de contextualiser l’usage des modèles interprétatifs mobilisés dans l’analyse littéraire et de les critiquer en interrogeant les rapports de pouvoir qu’ils dissimulent. Il défend ainsi l’hypothèse que le mouvement #MeToo invite les littéraires à réévaluer leurs pratiques et leurs paradigmes de lecture en fonction de ce qu’ils rendent possible.
Number: 24 Publisher: Ghent University
Keywords: #metoo; Irina; consentement; lecture féministe; lecture littéraire; violences sexuelles

Let Her Play: A report on gender-based violence in video games - Mettler, Kirsten (Embodied: The Stanford Undergraduate Journal of Feminist, Gender, and Sexuality Studies, 2022)
Globally, video games are a $152 billion industry, and approximately 3.1 billion people, or 40% of the population, are players (Ingersoll & Anti-Defamation League, 2019, Price, 2020). Gaming is a huge industry, and it’s only getting bigger. Unfortunately, women and other historically marginalized groups often face staggering levels of harassment and violence in these communities. This report aims to explore the issue of gender-based violence in video games by analyzing contributing factors and proposing gaming company interventions.
Number: 1
Keywords: Bibliographie; Irina; Nettoyer; esports

Review: Cooperative Gaming: Diversity in the Games Industry and How to Cultivate Inclusion - Hanussek, Benjamin (Press Start, 2022)
Review: Cooperative Gaming: Diversity in the Games Industry and How to Cultivate Inclusion, by Alayna Cole and Jessica Zammit. 2020. CRC Press. xv + 95 pp.
Number: 2
Keywords: Irina; diversity; game industry; game studies; inclusion

Caste, gender, and “global Indian-ness”: spaces of safety in stand-up comedy in global Mumbai - James, Aju (Feminist Media Studies, 2022)
This paper argues that stand-up comedy produces the places it uses in the city of Mumbai as “safe” for new middle-class women by excluding Dalit and working-class people who are deemed “dangerous.” Such exclusion is achieved by mobilising places and infrastructure that are built to make Mumbai a “world-class” city, a process that requires the dispossession and exploitation of the masses from which the new middle-class benefits. In the context of the sexual harassment charges that hit the stand-up comedy scene in 2018 and the responses to those charges, I posit that stand-up comedy is a site where “appropriate” gender hierarchies are formulated in the pursuit of “global Indian-ness.”
Keywords: Bibliographie; Global Indian-ness; Mumbai; Nettoyer; Sophie-Anne; sexual harassment; stand-up comedy; world-class city

Poursuite intentée par Gilbert Rozon: La requête de Julie Snyder et Pénélope McQuade rejetée en appel - Morin-Martel, Florence (La Presse, 2022)
La poursuite de Gilbert Rozon réclamant 450 000 $ à Julie Snyder et Pénélope McQuade pour diffamation ira de l’avant. La requête des deux animatrices visant à mettre fin aux procédures, qui relèvent « d’une poursuite-bâillon », selon elles, a été déboutée en Cour d’appel, vendredi.
Keywords: Bibliographie; Nettoyer

Rainbow dancing in Finland and the challenge of transgender inclusion - Kavoura, Anna; Rinne, Santtu (Routledge Handbook of Gender Politics in Sport and Physical Activity, 2022)
Traditionally, partner dances occur between a woman and a man, following rather conservative gender roles and rules. However, as a result of international lesbian, gay, bisexual, transgender, intersex, queer, asexual, allies and more (LGBTIQA+) activism, some social dancing events and competitions have made space for gender and sexual diversity. This chapter focuses on the Rainbow and Same-Sex dancing scene in Finland and its potential and challenges for transgender inclusion. We draw on data collected during the first author’s ethnographic and participatory action research study on trans-inclusive sport spaces and the second author’s experiences as a professional dance teacher and Rainbow trans dancer at both same-sex and mainstream dance competitions. Our findings reveal that the Rainbow dancing movement has helped make dancing more accessible and inclusive for members of the trans community through challenging traditional cis- and heteronormative dance roles and the men-lead/women-follow paradigm. Yet, certain challenges for trans-inclusion persist, such as the transphobic politics and rules of national and international dance associations. In concluding this chapter, we provide recommendations for enhancing access and positive experiences of trans people in dance, DanceSport and sport in general.
Keywords: Bibliographie; Nettoyer

Time for a change: women, work, and gender equality in TV production - Milner, Susan; Gregory, Abigail (Media, Culture & Society, 2022)
This article uses Acker’s concept of inequality regimes to analyze qualitative research findings on work-life balance and gender equality for women in British television production. Female survey respondents, focus group participants, and interviewees spoke of their subjective experience of gendered work practices which disadvantage women as women. These findings build on existing research showing gender disadvantage in the industry, leading to loss of human capital and a narrowing of the range of creative experience. They also show that growing numbers of women are seeking alternative modes of production, at a time of increased awareness of inequality. Such alternatives suggest that change is possible, although it is strongly constrained by organizational logics and subject to continued resistance, in line with Acker’s framework of analysis. Visibility of inequalities is the key to supporting change.
Publisher: SAGE Publications Ltd
Keywords: Myriam; TV; TV production; Television

Vague de suicides chez les artisans de la scène: Quand le rideau tombe à jamais - Blais-Poulin, Charles-Éric; Groguhé, Marissa (La Presse, 2022)
Keywords: Bibliographie; Nettoyer

Women actors, insecure work, and everyday sexism in the Canadian screen industry - Liinamaa, Saara; Rogers, Malia (Feminist Media Studies, 2022)
Acting, especially in the screen arts industry, is a job where women are subjected to pronounced and widely accepted socio-cultural aesthetic ideals within an industry that has become renowned for its tolerance for and justifications of sexism and sexualized violence. However, there is a limited amount of scholarship that examines actors and acting from a work and employment perspective. Drawing on the literature on work insecurity and gender inequities in cultural work, this article examines the screen industry from the perspective of women actors in a semi-peripheral location in Canada. This is a cohort that has managed to remain in the industry, despite high levels of attrition. Drawing on in-depth semi-structured interviews, our participants identify a range of strategies they employ (toughness, silence, humour, refusal, creative resistance) to respond to workplace sexism and gender-based constraints as they try to balance their creative agency with career sustainability. Participants emphasized that finding multiple outlets for realizing creative agency is crucial to counteracting everyday sexism and remaining in the industry.
Publisher: Routledge _eprint: https://doi.org/10.1080/14680777.2020.1759114
Keywords: Bibliographie; Irina; Nettoyer; Screen industry; everyday sexism; gender and cultural work; women actors and acting

Entente collective 2022-2024 entre l'Orchestre Métropolitain et la Guilde des musiciens et musiciennes du Québec (2022)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Personal Safety for Dance (2022)
Personal Safety for Dance exists to develop a dance environment that is free from abuse, open, and supportive for all in dance.
Keywords: Bibliographie; Nettoyer

Soutien psychologique (Guilde des musiciens et musiciennes du Québec, 2022)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Music as Labour: Inequalities and Activism in the Past and Present - Abfalter, Dagmar; Reitsamer, Rosa (Taylor & Francis, 2022)
This book brings together research at the intersection of music, cultural industries, management, antiracist politics and gender studies to analyse music as labour, in particular highlighting social inequalities and activism. Providing insights into labour processes and practices, the authors investigate the changing role of manifold actors, institutions and technologies and the corresponding shifts in the valuation and evaluation of music achievements that have shaped the relationship between music, labour, the economy and politics. With research into a variety of geographic regions, chapters shed light on the various ways by which musicians’ work is performed, constructed and managed at different times and show that musicians’ working practices have been marked by precarity, insecurity and short-term contracts long before capitalism invited everybody to ‘be creative’. In doing so, they specifically examine the dynamics in music professions and educational institutions, as well as gatekeepers and mechanisms of inclusion and exclusion. With a specific emphasis on inequalities in the music industries, this book will be essential reading for scholars seeking to understand the collective actions and initiatives that foster participation, inclusion, diversity and fair pay amongst musicians and other workers.
Accepted: 2022-05-18T09:38:24Z
Keywords: Music; Myriam; Personnel and human resources management; bic Book Industry Communication::A The arts::AV Music; bic Book Industry Communication::K Economics; business & management::KJ Business & management::KJM Management & management techniques::KJMV Management of specific areas::KJMV2 Personnel & human resources management; finance

#MeToo and beyond: perspectives on a global movement - Alcalde, M. Cristina; Villa, Paula-Irene (University Press of Kentucky, 2022)

Hypermasculinity Makes the Queer Boy Faint - Alterio, Anthony M. (Masculinity, Intersectionality and Identity: Why Boys (Don’t) Dance, 2022)
Through the lens of personal experience, this chapter provides an exploration of the oft-concealed practices and hypermasculine ideals in dance education. Commercial, concert, and academic dance pedagogy continues to create and perpetuate homophobia that restricts the definition of “boy dancer” to the point of creating a false scarcity and competition to be the most cis-heteronormative male possible. Alterio argues this environment contributes to the perpetuation of discrimination against LGBTQIA+ dancers, the exclusion of non-cis boys, and lack of innovation in the field. Recommendations are offered to those interested in pushing the boundaries of performance and gender identity and a call for institutions to support this work.
Keywords: Bibliographie; Nettoyer

Re-Cognizing Harassment with the Arts - Babulski, Timothy (Phenomenology & Practice, 2022)
Absent mechanisms of restorative justice, victims of sexual harassment, particularly those within the LGBT+ community that are already frequent targets of relational aggression, are unlikely to either report or reckon with the consequences of inappropriate workplace behaviors and discrimination. Written from the perspective of a masculinized bisexual whose encounter with a pervasive culture of sexual harassment and psychological abuse provoked suicidal ideation, this paper employs the artistic practices of illustration as a means of first re-cognizing and recognizing phenomena, a Ricœurean construct of narrative and a palimpsest of multivocal text and images to evoke the lived experience of harassment and an analytic layer to invoke the phenomenon. By drawing, writing, and thinking through the phenomenon, the marriage of artistic and phenomenological approaches allows both researcher and reader to confront the ‘painful truths’ that otherwise resist easy analysis.
Number: 2
Keywords: LGBTIQ; Myriam; Safe spaces; Teaching arts; Visual arts

Gendered Responses to Gendered Harms: Sexual Violence and Bystander Intervention at Australian Music Festivals - Baillie, Greta; Fileborn, Bianca; Wadds, Phillip (Violence Against Women, 2022)
Bystander intervention has shown promise in preventing sexual violence in certain social contexts. Despite emerging evidence of pervasive sexual violence at music festivals, no research has considered bystander intervention in this setting. Drawing on an online survey conducted with 371 Australian festival attendees, we explore the role of gender on bystander intervention at music festivals. Findings point to significant gender differences, with women more willing and likely to intervene in a broader range of scenarios. We argue that responses to sexual violence are a collective responsibility shared by both women and men, as well as festival organizers and industry bodies.
Keywords: Camille

Rapport de recherche sur l’éthique en regard des violences à caractère sexuelle dans le milieu de l’humour québécois francophone - Bernier, Dominique; Paré, Christelle; Carbonneau, Karine; Vernus, Judith; Morency, Sophie-Anne (UQÀM et partenaires, 2022)
Rapport interne
Keywords: Bibliographie; Nettoyer; Sophie-Anne

Les femmes dans l’industrie musicale canadienne francophone - Bissonnette, Joëlle (Musicaction, 2022)
Rapport d’étude réalisé pour et avec la collaboration de la Fondation Musicaction, grâce à l’appui du Gouvernement du Canada
Keywords: Bibliographie; Nettoyer

“#UsToo”: Empowerment and Protectionism in Responses to Sexual Abuse of Women with Intellectual Disabilities - Boux, Holly Jeanine (Berkeley Journal of Gender, Law & Justice, 2022)
Publisher: Berkeley Journal of Gender, Law & Justice
Keywords: Bibliographie; Nettoyer

Révision des lois sur le statut de l'artiste - Cabinet du ministre de la Culture et des Communications et ministre responsable de la Jeunesse (Gouvernement du Québec, 2022)
QUÉBEC, le 3 juin 2022 /CNW Telbec/ - L'Assemblée nationale du Québec a adopté à l'unanimité aujourd'hui le projet de loi numéro 35, Loi visant à moderniser et à harmoniser les règles relatives au statut professionnel de l'artiste, déposé par la ministre...
Keywords: Bibliographie; Nettoyer

Les violences sexistes après #MeToo (Presses des Mines, 2022)
''À partir d'octobre 2017, #MeToo devient un phénomène mondial, en diffusant internationalement le slogan que Tarana Burke, militante new-yorkaise contre les violences sexuelles, avait lancé dix ans plus tôt. Une multitude de victimes témoignent sur divers supports numériques et médiatiques, reformulant et intensifiant des luttes féministes en cours contre les violences sexistes. À l'initiative d'une nouvelle génération de chercheuses et chercheurs francophones sur les violences de genre, ce premier ouvrage académique en France sur #MeToo cherche à comprendre l'événement. Il propose une approche empirique de ce mouvement mondial. Il décrypte d'abord l'événement #MeToo dans sa matérialité, ses contextes de réception et d'appropriation et s'efforce de montrer comment l'usage des réseaux socionumériques permet d'articuler de nouvelles formes de militantisme ou de renforcer des pratiques militantes existantes en ligne et hors ligne. Il inscrit ensuite #MeToo dans une histoire des luttes féministes de plus long terme et s'efforce de questionner son unité à travers l'étude de ses résonances contrastées dans différents milieux professionnels.''– Site de l'éditeur
OCLC: 1354535098

Dancing Boys and Men: Negotiating Masculinity and Sexuality - Christofidou, Andria (Masculinity, Intersectionality and Identity: Why Boys (Don’t) Dance, 2022)
Theatrical dance remains widely perceived as an unconventional activity for boys and young men in many Western contexts. This chapter focuses on professional male dancers’ pathways into recreational, pre-professional dance and assesses the various obstacles encountered and the sources of encouragement available to continue dancing and to pursue a dance career. Data analysis challenges the assumption that homophobia and hierarchies among boys, men, and masculinities have been erased. The chapter argues that wider systems of inequality, oppression, and power persist. These continue to affect boys and young men, influencing their choices and the possibilities to transgress gender norms.

Recommandations de l’équipe à l’issue de trois phases d’une programmation de recherche partenariale université/collectivités - Collectif de recherche Justice pour les femmes victimes de violence (Service aux collectivités de l’Université du Québec à Montréal /Fédération des maisons d’hébergement pour femmes / Regroupement des maisons pour femmes victimes de violence conjugale /Concertation des luttes contre l’exploitation sexuelle /Regroupement québécois des centres d’aide et de lutte contre les agressions à caractère sexuel, 2022)

How Independent Contractors Respond to Sexual Harassment: The Case of the Modeling Industry - Crowley, Jocelyn Elise (Employee Responsibilities and Rights Journal, 2022)
Sexual harassment continues to be a problem that most commonly affects women in the United States workforce today. While there are legal and organizational remedies available, most of these mechanisms for redress only exist for workers in traditional employeremployee contexts. Independent contractors, self-employed workers who represent a growing number of labor force participants in this economy, can therefore only use informal means of addressing sexual harassment. This study used grounded theory methods to analyze 88 separate narratives of sexual harassment from 70 fashion models, an overwhelmingly female set of independent contractors currently operating in the American economy. The aim of the analysis was to understand the mix and meaning behind the use of informal strategies—more specifically confrontation versus non-confrontation—in response to this sexual harassment. Notably, models most often confronted the perpetrators of harassment. Critically, however, those models who chose non-confrontation did not minimize the abuse that they faced. Instead, they either saw themselves as powerless or engaged in self-blame when faced with harassment on the job.
Keywords: Bibliographie; Confrontation; Fashion industry; Independent contractors; Models; Myriam; Nettoyer; Sexual harassment

Analysis of the “Regional Survey on Violence and Harassment in the Workplace in the Audiovisual and Performing Arts Industry in Latin America” - FIA-LA; UNI Americas MEI (International Federation of Actors et UNI Americas MEI / Panartes, 2022)
Keywords: Bibliographie; Nettoyer; Raphaël

Cadre de référence évolutif des objectifs et contenus de prévention des violences à caractère sexuel en milieu d’enseignement supérieur - Fradette-Drouin, Laurie; Bergeron, Manon (Chaire de recherche sur les violences sexistes et sexuelles en milieu d’enseignement supérieur. Université du Québec à montréal, 2022)
Keywords: Bibliographie; Nettoyer

Loi sur le statut professionnel des artistes des arts visuels, du cinéma, du disque, de la littérature, des métiers d’art et de la scène - Gouvernement du Québec (2022)

*Loi visant à harmoniser et à moderniser les règles relatives au statut professionnel de l'artiste - Gouvernement du Québec (2022)
Keywords: Bibliographie; Nettoyer

Exploring Vicarious Liability to Remedy the #E-Too Movement - Hewson, Eloise (York Law Review, 2022)
The esports, or competitive video gaming, industry is an exciting area of economic and cultural growth. Gaming can facilitate interpersonal connection, shared problem-solving, and creativity. Players may purchase a game, watch a streamer play it online, join an online gaming community, attend a tournament, compete professionally, or find employment in game development or a related field. The gaming industry generates enormous economic value and employs tens of thousands of people in the UK alone. However, the esports sector does not extend its benefits equally. Women are regularly verbally harassed in video games, countless women have been groped at esports events, women have been raped by professional players, underage fans have been groomed. Abuse is endemic to online gaming communities.
Keywords: Bibliographie; Irina; Nettoyer

“My work opportunities depend on how much I can take” : inappropriate behaviour and harassment in the cultural domain in Finland - Jaakola, Meri (2022)
Phenomena of inappropriate behaviour and harassment are neither new nor unique to the cultural domain. However, these phenomena have not been largely publicly discussed before the 2017 me too movement, presumably due to the culture of silence prominent within the cultural domain. After the movement that started from the film industry and quickly spread around the world, discussion on ethical working conditions has arisen within all the cultural domain as well. This qualitative driven mixed methods research reviews the current situation of inappropriate behaviour and harassment in Finland and seeks to understand the magnitude and forms of the phenomena. The research questions are: 1) What special characteristics or structures in the arts and culture field enable inappropriate behaviour and harassment or the possibility of them? And 2) What can be done to eliminate inappropriate behaviour and harassment from arts and culture workplaces? The research questions are answered analyzing research data collected using a survey and six themed interviews. Research data was collected in the spring of 2021. Topics that surfaced from the survey were used as a basis for the interview questions. Findings from the survey and the interviews act as the thematical scope of this master’s thesis, as they are the most important themes to come out of this research. The main findings of the thesis are that there are four elements that enable and maintain the improper working culture within the cultural domain. The elements are insufficient funding, poor management, artist myth, and limitlessness of the work. These themes are examined in discussion with literature. The four steps this thesis suggests helping uproot the improper behaviour in the cultural domain according to the research data and literature are 1) Pushing for the cultural domain’s ethical board to be established, 2) Composing ethical guidelines for all the cultural domain, 3) Basing funding on following the said guidelines, and 4. Talking about improper behaviour publicly and bringing cases of misconduct forward.
Accepted: 2022-03-30T06:27:19Z Publisher: Taideyliopiston Sibelius-Akatemia

Understanding Sexual Harassment in the #MeToo Era - Julios, Christina (Sexual Harassment in the UK Parliament: Lessons from the #MeToo Era, 2022)
This chapter provides a contextual account of the rise of #MeToo as an global gender-equality campaign supporting those affected by sexual transgressions. Originally articulated by African-American civil rights activist Tarana Burke in 2006, the slogan ‘me too’ was meant as a rallying cry to support young minority ethic survivors of sexual abuse. Years later, social media would turn Burke’s motto into a byword for the global #MeToo movement. The chapter chronicles the events surrounding #MeToo’s inception, including Hollywood producer Harvey Weinstein’s sexual exploitation scandal in 2017, and The New York Times and The New Yorker exposés of his serial offending within the film industry. It also examines the narratives of countless survivors and #MeToo campaigners, including high-profile cases such as those of Rose McGowan, Alyssa Milano, Mimi Haleyi, Jessica Mann and Zelda Perkins. The chapter then critically considers the growth and international significance of #MeToo as well as its inherent shortcomings.
Keywords: #MeToo; Farrow; Harvey Weinstein; Irina; Kantor and Twohey; Rose McGowan

Considering Queerness - Actor Training's Issues and Alternatives - LeBlanc, Jacob G. (Université du Commonwealth de Virginie, 2022)
Keywords: Bibliographie; Nettoyer; Raphaël

Pour une culture du consentement - Les frères Seaborn (2022)
Place: Montréal Publisher: Société Radio-Canada
Keywords: Bibliographie; Nettoyer

How is the Ballet World Including Non-Binary Dancers? - Lund, Rebekah (Dance Major Journal, 2022)
A few pioneers have shown the way, but who will follow?
Keywords: Bibliographie; Nettoyer

La quatrième vague du féminisme : quel impact sur le champ littéraire ? - Mairesse, Lise (Université catholique de Louvain, 2022)
Keywords: Bibliographie; Irina; Nettoyer

The impact of #MeToo in the South African film and television industry, within a historical framework - Majiba, Ntsika (Université de l'Afrique du Sud, 2022)
The study is a history project and is concerned with tracking the impact of #MeToo in the South African Film and Television industry in South Africa. Its main premise were the findings made public by a South African organization, Sisters Working in Film and Television (SWIFT) in 2017, that found that sexual harassment in the television and film industry was not just a norm but a crisis. The core focus of the study was on the development and impact of the #MeToo movement, which entailed investigating the manner in which women reacted to the hashtag (#MeToo), the reaction of their male counterparts, as well as the reaction and actions taken by the various bodies, institutions and organisations in the Film and Television industry, which included; broadcasters and production houses alike. This study begins by giving a concise background of the movement by firstly, historicising various female-led movements and comparing and contrasting them with the rise of digital movements or digital activism. The historicisation involves a brief comparison of past and present women-led activism, as well as a brief review of other hashtags like #AmINext and #Enough, on which #MeToo has had an influence. It goes on to investigate the development of #MeToo movement and to discuss the responses of the industry and individuals to the movement. The study embarked on a data collection quest by interviewing eleven female television and film practitioners in South Africa. Their ages ranged from 20 to 55. The findings of the research revealed that female practitioners were still being harassed post #MeToo, although subtly. The lack of unity amongst women in the sector was cited as one of the reasons behind the ongoing harassment. Gender parity and equity was also still lacking in the South African television and film industry. This study emerged in the midst of activism and scholarship seeking to unravel the norms of South African sexual harassment and rape culture against women. Thus, the study focused on the changes and transformations brought about by the hashtag within the industry. With South Africa’s historical background and the current circumstances around Gender Based Violence (GBV), this study was concerned with tracking whether or not digital activism had in some way been able to aid change and transformation. In particular, this study looked at the impact of the MeToo phenomenon on the women in the industry, the extent to which it empowered them, what they began to say and how they began to act. The study also explored South Africa’s ‘rape culture’ as South Africa has been proclaimed the ‘worlds rape capital’. It reflected on the colonial rule as the perpetuation of patriarchy and male entitlement over female bodies. Patriarchy in the industry was also confirmed by the findings and through data analysis, as one of the key factors in the emergence of #MeToo in South Africa, and in the utilisation of the hashtag by women in the sector to speak up against sexual harassment.
Accepted: 2023-02-20T11:59:11Z
Keywords: Bibliographie; Irina; Nettoyer

In Her Own Words: Documenting the Current Realities of Women-in-Jazz - Manfredo, Alexandra, Kiernan Steiner (The Routledge Companion to Jazz and Gender, 2022)
Since the inception of jazz, the lives and experiences of women-in-jazz have been inadequately documented and archived, which has led to a lack of female representation in the jazz community. During the recent resurgence of the #MeToo Movement, many women-in-jazz bravely shared stories of sexual discrimination and harassment. As the jazz community continues to address the gender disparity, women’s stories need to be centered in order to address current realities of women-in-jazz. By documenting the experiences of women-in-jazz in higher education as students, educators and performers, sexual discrimination and harassment must be considered as contributing factors of the gender disparity in jazz.
Num Pages: 14
Keywords: Jazz; Music; Myriam

La justice réparatrice en matière de violences sexuelles : L’expérience de dialogue entre personnes victimes et personnes auteures dans les cas de violences sexuelles - Marceau, Laurence (2022)

L'artiste et son oeuvre - McEwen, Jérémie (2022)
Keywords: Bibliographie; Nettoyer

Briser le rideau de verre en humour - Morency, Sophie-Anne; Cézard, Zed; Carbonneau, Karine (2022)
Keywords: Sophie-Anne

Morinom - Office québécois de la langue française (Grand dictionnaire terminologique, 2022)
Prénom qui a été donné à une personne à sa naissance, mais que celle-ci ne souhaite plus qu'on emploie pour la désigner.
Keywords: Bibliographie; Nettoyer

Dancing with Inclusivity: The Importance of Integrating Genderless Terminology into Swing Dance Spaces - Olander, Guinievere.R. (Unbound, 2022)
Keywords: Bibliographie; Nettoyer

Theatre-making in the age of #MeToo: Working cross-culturally toward a framework for making safer creative spaces - Park, Younghee (Université de technologie du Queensland, 2022)
Keywords: Bibliographie; Nettoyer; Raphaël

Que reste-t-il de #MoiAussi?: secousses québécoises d'un mouvement planétaire - Pineda, Améli (Somme toute : Le Devoir, 2022)
"Au Québec, la vague #MoiAussi qui déferle jusqu'à ce jour a pris son essor les 18 et 19 octobre 2017, lorsque des enquêtes du Devoir et de La Presse ont déboulonné deux géants du monde des médias. C'est avec cet épisode critique que s'ouvre le livre d'Améli Pineda, qui entamait alors sans le savoir plusieurs années de couverture du phénomène des dénonciations d'abus sexuels à grande échelle. À l'intersection des mondes des médias, de la justice et de l'activisme, ce texte synthétise et contextualise les cinq ans du mouvement #MoiAussi au Québec, dépeignant ses plus grands moments et relatant la réaction en chaîne du public et des magistrats. Améli pineda s'appuie sur des articles phares parus depuis 2017 dans Le Devoir ainsi que sur une pléiade d'entrevues menées auprès des protagonistes du mouvement - femmes ayant dénoncé, homme visés par des allégations, avocates et avocats, chercheuses, créatrices de pages de dénonciations virtuelles - ainsi que sur son expérience personnelle de l'effervescence médiatique des cinq dernières années pour trouver un sens à cette prise de conscience collective qui a transformé notre société."–back cover
OCLC: 1346354564

Dénoncé en ligne, Yann Perreau est lui aussi largué par sa maison de disques - Radio-Canada (Radio-Canada, 2022)
Keywords: Bibliographie; Nettoyer

Masculinity, Intersectionality and Identity: Why Boys (Don’t) Dance - Risner, Doug; Watson, Beccy (Springer International Publishing, 2022)
Keywords: Bibliographie; Nettoyer

Raising Their Voices: Independent Review into Sexual Harm, Sexual Harassment, and Systemic Discrimination in the National Music Industry - Shehadie, Alexandra; The Review Team (Support Act, 2022)
Keywords: Bibliographie; Nettoyer

Sex, consent and justice: a new feminist framework - Sikka, Tina (Edinburgh University Press, 2022)

Le privilège de dénoncer: justice pour toutes les victimes de violences sexuelles - Souffrant, Kharoll-Ann (Éditions du remue-ménage, 2022)
Keywords: Bibliographie; Nettoyer

Justice pour les femmes marginalisées victimes de violences sexospécifiques : Ce que la littérature et les intervenantes nous apprennent - Thibault, Sarah; Pagé, Geneviève; Boulebsol, Carole; coll. (Service aux collectivités de l’Université du Québec à Montréal / Fédération des maisons d’hébergement pour femmes / Regroupement des maisons pour femmes victimes de violence conjugale / Concertation des luttes contre l’exploitation sexuelle / Regroupement québécois des centres d’aide et de lutte contre les agressions à caractère sexuel., 2022)

Creative Industries in Canada - Thompson, Cheryl; Campbell, Miranda (Canadian Scholars, 2022)
Keywords: Cultural industries.; Irina

Jouer Sur le Banc Les Filles Dans le Monde de L'improvisation. - Walsh-Viau, Emmanuelle.; Joubert, Lucie (Somme Toute, 2022)
Keywords: Bibliographie; Nettoyer; Sophie-Anne

Plan de lutte contre les violences et le harcèlement sexistes et sexuels dans le spectacle vivant - Ministère de la Culture français (2021)
Keywords: Bibliographie; Nettoyer; Raphaël

The Routledge Companion to Romantic Love - Brooks, Ann (Routledge, 2021)
Keywords: Irina

Politique visant à prévenir et à combattre les violences à caractère sexuel (Annexe E) - École nationale de l'humour (2021)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer; Sophie-Anne

Why #MeToo Hasn’t Transformed the Stand-Up Scene - Baum, Gary (The Hollywood Reporter, 2021)
Female comics say that the empowerment movement has been met with pushback, retaliation and mockery from male counterparts: “If you’re a woman who’s been harassed, if you just talk about what happened, people perceive you as being some ‘cancel culture’ advocate.”
Keywords: Sophie-Anne

ANNULÉ(E): Réflexions sur la cancel culture - Lussier, Judith (Éditions Cardinal, 2021)
Après On peut plus rien dire, vendu à près de 7 000 exemplaires, Judith Lussier s’attaque à la culture de l’annulation avec son nouveau livre Annulé(e). Un brillant essai d’analyse qui, grâce à de nombreux exemples évocateurs et contemporains, fait le point sur un sujet brûlant d’actualité.« Alors que les réseaux sociaux ont permis à plus d’individus de prendre la parole et à différentes réalités d’être enfin nommées, il semble que le terrain discursif soit de plus en plus miné. Nous n’avons jamais pu autant nous exprimer librement, et pourtant, nous avons le sentiment que communiquer ses idées n’a jamais été aussi complexe et risqué. »C’est avec ce point de départ tout en nuances que la journaliste et essayiste Judith Lussier tente de comprendre la cancel culture. Cet essai examine ce phénomène complexe aux contours flous qui sème parfois la panique et alimente de nombreuses chroniques, sans faire l’économie d’une réflexion sur les dynamiques de pouvoir qui dictent sa trajectoire.
Keywords: Bibliographie; Nettoyer

Un hommage pour Romane Bonnier (2021)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

“She’s just another pretty face:” sexual harassment of female photographers - Somerstein, Rachel (Feminist Media Studies, 2021)
This article examines sexual and gendered harassment among professional female editorial photographers, whose experiences have largely been under-researched. It draws on semi-structured interviews conducted between 2017–2019 with 17 female professional editorial photographers, aged 23–82, who work in a variety of beats. Sixteen of 17 interviewees encountered sexual harassment, with gendered harassment the most common. Harassers included professors, other photographers, colleagues, salespeople, subjects, and the general public, whom photographers encountered at school, work, while networking, and when using and buying gear. Largely, participants addressed the sexual and gendered harassment on an individual level, rather than reporting it to editors or other authorities. These findings add qualitative nuance to quantitative research that suggests physical risks and economic precarity may drive women from the profession.
Keywords: Bibliographie; Embodiment; Myriam; Nettoyer; Sexual harassment; female journalists; gender and work; photographers; photojournalism

Narrating women workers’ perceptions of sexism and change in the Australian screen postproduction sector before and after #MeToo - Dooley, Kath; Erhart, Julia (Feminist Media Studies, 2021)
This article interrogates the localized experiences of present-day workers who identify as women in Australian postproduction sectors, including editing, visual effects (VFX), and animation, exploring sex ism and perceptions of change in the age of #MeToo. Considering the significant numbers of women working in these sectors, and the scant research into their experiences undertaken in an Australian context, the authors conducted semi-structured interviews with ten women in various roles and in various geographical locations in Australia. This qualitative approach to data collection aims to explore inequalities that may not be captured in industry surveys, providing fine-grain details of the ways that individuals in postproduction experience sexism. The resulting data suggests that while there is continuity between the gendered experiences of these workers and that of women in industry sectors that have already been documen ted, there are, however, new observations about changes in work place behavior in the sector, brought about by growing public awareness of industry discrimination and harassment and of shifts in Australian industry policy. The authors isolated recurring themes within women’s gendered experiences in relation to how they per ceived the impact of the gender-equity initiatives on the attitudes of their co-workers, their workplace opportunities, and their experi ences as workers.
Keywords: Irina

Indian Women in Comedy: : An Inquiry into the Perpetuation of Rape Culture on Social Media - Sharma, Mridula (Sanglap: Journal of Literary and Cultural Inquiry, 2021)
‘Postfeminist’ society has created the impression that contemporary discourses on gender representation, particularly in digital media platforms, are pointless. This misconception is coupled with online aggression by men’s rights activists who position feminist debates as sources of male oppression. However, media practices and consumption processes continue to maintain the supremacy of the male gender identity, which strengthens the process of transforming social media into a component of the “manosphere.” The failure of the fourth wave of feminism in utilising the Internet for mobilising activism for the ontological equality of all genders has succeeded by increasing gender-based violence against women. Indian women in comedy negotiate with these systemic inequalities while navigating male dominance in the comedy industry. The paper is an attempt to examine the structures of gender inequality and bias that affect the participation and advancement of women in the comedy circuit. Its focus remains on the formulation of a rape culture on social media and its subsequent consequences in the larger social context of the development of a patriarchal culture.
Number: 2
Keywords: Digital Abuse; Sophie-Anne

“The balance of power is me: 0, Harvey Weinstein: 10”: A Critical Discourse Analysis of the press representation of Hollywood’s biggest sexual harassment scandal - Nikolova, Evelin (Women's Studies International Forum, 2021)
On 5 October 2017, The New York Times published an article in which Harvey Weinstein was accused of sexual harassment by five women. The scandal grew to enormous proportions as more allegations against him followed. This led to the #MeToo and TIME'S UP movements, initiatives to fight sexual harassment in the workplace. Given that media discourse can have an impact on the knowledge, beliefs, attitudes, and behaviours of the public regarding these phenomena (van Dijk 1989), this study adopts a Critical Discourse Studies (CDS) perspective and explores how power and gender inequality are sustained, (re)shaped and/or challenged by focusing on the reporting of the Harvey Weinstein case which - to the author's best knowledge - has not been analysed before in the field of linguistics. It draws from the systemic functional linguistics and the discourse-historical approach and it examines the way the perpetrator, the accusers and the phenomenon of sexual harassment were discursively constructed in five key articles published in the New York Times. The findings differ in a major way from existing research on sexual violence against women in that 1) the perpetrator, Weinstein, was depicted with clear ascription of agency, 2) women victims' voices and feelings were foregrounded, 3) the link between sexual harassment and the social context in which it occurs was discussed.
Keywords: Critical discourse studies; Discourse-Historical Approach; Discursive strategies; Media representation; Myriam; Sexual harassment; Transitivity analysis; Weinstein

Designing Women: Learning from Feminist Legacies and the Women-In-Games Movement - Schoemann, Sarah (Georgia Institute of Technology, 2021)
In 2019 the video games industry was rocked by a slew of high-profile sexual harassment and assault allegations that some called the #MeToo movement of the games world, but to many these revelations came as no surprise. From the 2004 EA Spouse controversy to the 2014 #Gamergate harassment campaign the games industry has long been known for harboring an at times toxic atmosphere of exploitation and discrimination. This project looks at a handful of Women-In-Games organizations that set out to change the experience of women in the industry by helping newcomers to gain high tech skills and to supporting early career professionals through mentorship and community building. Along the way, it combines the study of these Women-In-Games organizations with a years-long collaboration bringing video games to the US' oldest feminist bookstore, Charis Books & More in Atlanta, GA. Through examining the work and values of two types of organizations devoted to women's equality, one a historic feminist movement-building space and the others, contemporary interventions into the professional games and tech industry, this study asks the questions "What can the Women-In-Games movement learn from the rich history of feminist organizing at spaces like Charis?" "Can games play a part in feminist movement building?" and "What does the future of feminist organizing look like in the games industry?”
Accepted: 2021-09-15T15:43:41Z Publisher: Georgia Institute of Technology
Keywords: Bibliographie; Irina; Nettoyer

Vague de dénonciations : un an après: Qu’est-ce qui cloche dans le milieu culturel ? - Groguhé, Marissa (La Presse, 2021)
C’était il y a un an. En juillet 2020, une nouvelle vague de dénonciations d’agressions et d’inconduites sexuelles a déferlé sur les réseaux sociaux au Québec. Sans être la seule industrie touchée, le milieu culturel a été secoué par plusieurs scandales. Retour sur cet été de grands bouleversements.
Keywords: Bibliographie; Nettoyer

Michel Venne coupable d’agression sexuelle - Béland, Gabriel (La Presse, 2021)
L’ancien journaliste Michel Venne a été reconnu coupable mercredi d’agression et exploitation sexuelle sur Léa Clermont-Dion alors qu’elle avait 17 ans. La poursuite espère que ce verdict encouragera d’autres victimes à porter plainte.
Keywords: Bibliographie; Nettoyer

“Just a Junior Journalist”: Field Theory and Editorial Photographers’ Gendered Experiences - Somerstein, Rachel (Journalism Practice, 2021)
Women outnumber men in graduate and undergraduate programs in photojournalism and work as photo editors at a number of high-profile publications. But in the field of professional editorial photography, they lag men in pay, legitimacy, and status. Using Bourdieu’s field theory, this paper explores how gender shapes the way women experience, compete in, and negotiate the field, specifically regarding assignments, salary, sexual harassment, and tactics for achieving access to stories. Findings suggest that women use their gender as a competitive advantage however they can, but that negative capital attached to femaleness and femininity persists. The findings are based on semi-structured interviews conducted between 2017 and 2019 with 17 female professional editorial photographers, aged 23–82, who work in a variety of beats.
Publisher: Routledge _eprint: https://doi.org/10.1080/17512786.2020.1755345
Keywords: Field theory; Myriam; gender; journalism; photojournalism; women and photography

Pourquoi une telle indifférence face au #MeToo de l’édition française ? - Haegel, Mymy (Madmoizelle, 2021)
Ce 21 avril, Mediapart a publié une enquête fouillée relatant des accusations de harcèlement sexuel envers Stéphane Marsan, patron d'une grande maison d'édition. Mais contrairement à d'autres #MeToo, celui-ci n'a pas trouvé beaucoup d'écho...
Keywords: Irina

Normalising sexualised violence in popular culture: eroding, erasing and controlling women in rock music - Hill, Rosemary Lucy; Richards, Daisy; Savigny, Heather (Feminist Media Studies, 2021)
How does music play a role in normalising men’s sexual violence towards women? Using mainstream rock and metal music as an illustrative case study, we offer a nuanced account of the ways in which men’s sexual violence is normalised. Using a definition of sexual violence drawn from Liz Kelly’s notion of a continuum, which reframes sexual violence as the loss of women’s ability to control sexual experiences, we explore the ways in which sexual violence is a prevalent lyrical and audio-visual component of rock and metal songs. We show that a pernicious theme of rock and metal over the last 25 years is the erosion of women’s ability to refuse sexual activity and to have voice and be heard. We argue that this erosion of women’s consent takes place through the representational use of emotional abuse, controlling/coercive behaviour, and through the objectification of women. The erasure of consent presented through these methods becomes a key means of establishing sexual control. Through manipulation, the confusion of what counts as sexual violence and how it is defined, men’s sexual violence against women is normalised.
Publisher: Routledge _eprint: https://doi.org/10.1080/14680777.2021.1902368
Keywords: Feminism; music video; rock lyrics; rock music; sexual violence

Creative Control: The Ambivalence of Work in the Culture Industries - Siciliano, Michael L. (Creative Control, 2021)
Michael L. Siciliano draws on nearly two years of ethnographic research as a participant-observer in a Los Angeles music studio and a multichannel YouTube network to explore the contradictions of creative work. Creative Control explains why “cool” jobs help us understand how workers can participate in their own exploitation.
Keywords: Myriam; cognitive capitalism; creative labor; digital media; precarity; sociology of labor

Rachat de Dare To Care par Cœur de pirate : un symbole pour les femmes en musique - Radio-Canada (Radio-Canada, 2021)
La rachat de la maison de disque par Béatrice Martin « a une symbolique très forte ».
Publisher: Radio-Canada.ca
Keywords: Bibliographie; Nettoyer

Kesha’s Comeback and the Stakes of Live Performance: Connecting through Trauma at the 2018 Grammy Awards - Hearfield, Katelyn (Journal of Musicological Research, 2021)
The use of live popular music performance as a platform to address gendered and sexual violence and trauma within the popular music industry can be demonstrated through the analysis of Kesha’s performance of “Praying” at the 2018 Grammy Awards. Analyzing the artist’s vocal and artistic delivery, in addition to her public persona following her allegations of sexual abuse against producer Lukasz Gottwald (Dr. Luke), illustrates how live performance—building on and contrasting with social media campaigns, such as #FreeKesha and #MeToo, and studio recordings—is a uniquely effective mode of processing individual and collective trauma.
Keywords: Bibliographie; Nettoyer

Commande un Angelot (2021)
« Le protocole d’accréditation Commande un Angelot a été conçu afin de s’attaquer aux violences à caractère sexuel dans les bars et les événements festifs ou sociaux. Celui-ci vise à prévenir ces situations et à venir en aide aux personnes en difficulté. Le Collectif social, un organisme sans but lucratif qui souhaite déployer et soutenir la réalisation d’initiatives de nature communautaire ou sociale qui répondent aux besoins des communautés étudiantes des établissements d’enseignement supérieur, est derrière ce projet. »
https://www.commandeunangelot.com
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

"Droit au but" pour prévenir les violences subtiles (Parminou: Théâtre socialement engagé, 2021)
Keywords: Bibliographie; Nettoyer

The Change You Want to See: Results of the first-ever survey of workplace sexual harassment in the Canadian performing arts, film, and television industries - Aftermetoo (2021)
Keywords: Bibliographie; Nettoyer; Raphaël

A Balancing Act: Agency and Constraints in University Students’ Understanding of and Responses to Sexual Violence in the Night-Time Economy - Anitha, Sundari; Jordan, Ana; Jameson, Jill; Davy, Zowie (Violence Against Women, 2021)
This article extends our understanding of how university students make sense of, and respond to, sexual violence in the night-time economy (NTE). Based on semi-structured interviews with 26 students in a city in England, we examine students’ constructions of their experiences of sexual violence within the NTE, exploring their negotiations with, and resistance to, this violence. Building upon theories of postfeminism, we interrogate the possibilities for resistance within the gendered spaces of the NTE and propose a disaggregated conceptualization of agency to understand responses to sexual violence, thereby offering useful insights for challenging sexual violence in the NTE and in universities.
Keywords: Camille

Avantage pour membre - Assocation canadienne des humoristes stand-up, Sketch & Impro (AQHS, 2021)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Naviguer les attentes genrées de la communauté de danse swing de Montréal - Batty, Megan (Les Cahiers de la Société québécoise de recherche en musique, 2021)
Keywords: Bibliographie; Nettoyer

A Gap in the Narrative: Exploring the Experiences of Trans Dancers Today - Best, Erica (Collège Ursinus, 2021)
Keywords: Bibliographie; Nettoyer

Why we lost the sex wars: sexual freedom in the #MeToo era - Bracewell, Lorna N. (University of Minnesota Press, 2021)
"Reexamining feminist sexual politics since the 1970s-the rivalries and the remarkable alliances"–
Keywords: Feminism; MeToo movement; Political aspects; Sex; Sexual harassment

L’opéra, un monde professionnel hanté par les violences de genre - Buscatto, Marie; Helbert, Soline; Roharik, Ionela (Les Cahiers de la Société québécoise de recherche en musique, 2021)
Le 19 août 2020, la soprano Chloé Briot dénonce dans La Lettre du Musicien des agressions sexuelles répétées portées par un collègue chanteur lors de la production de l’opéra L’inondation. Faute d’avoir été entendue et défendue par sa direction, elle annonce encore avoir porté plainte devant la justice française dès le mois de mars de la même année et vouloir ainsi « en finir avec la loi du silence ». Pourquoi l’artiste lyrique n’a-t-elle pas été entendue à plusieurs reprises malgré ses plaintes auprès de ses collègues et de la production ? Dans quelle mesure cette agression sexuelle est-elle symptomatique d’un mode de fonctionnement sexiste plus large du monde de l’opéra français ? Peut-on parler effectivement d’une « loi du silence » dénoncée par la chanteuse ? Si oui, que risquent ceux et celles qui dénonceraient des faits sexistes et des violences sexuelles ?
Publisher: Société québécoise de recherche en musique
Keywords: Bibliographie; Nettoyer

Harcèlement au travail - Commission des normes de l'équité de la santé et de la sécurité du travail (CNESST) (2021)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Formations et autres ressources - Conseil des ressources humaines du secteur culturel (Milieux de travail respectueux dans les arts, 2021)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Rebâtir la confiance (Secrétariat à la condition féminine, 2021)
OCLC: 1333502296

Sexual Harassment in Display Work: The Case of the Modeling Industry - Crowley, Jocelyn Elise (Gender & Society, 2021)
Keywords: Bibliographie; Cultural industries; Display work; Fashion; Informal industries; Modeling industry; Myriam; Nettoyer; Power dynamics; sexual harassment

Why We Should Avoid Artists Who Cause Harm: Support as Enabling Harm - Elicker, Bradley (Journal of Applied Philosophy, 2021)
This article examines our ethical responsibility toward artists engaged in harmful behaviors. Specifically, I demonstrate when and why we are morally obligated to withdraw our public and financial support from Artists Who Cause Harm such as Louis C.K., Terry Richardson, and Ryan Adams. Using a moral distinction presented by Philippa Foot and others, I identify this support as enabling harm when the wealth and influence that we support removes typical barriers that protect victims from harm and interposes barriers that prevent victims from avoiding harm. I proceed to demonstrate that our personal support is morally significant, and we have a moral responsibility to make contributions to collective action when the cost is low or the degree of belief that others will contribute is high. Here we have both a strong belief that others will withdraw support and a relatively low cost to ourselves to do so. I acknowledge that enabling current harms is only a sufficient condition to withdrawing support from an artist and should not minimize other reasons for avoiding certain artists and their works. However, when we do believe that our support enables an artist engaged in harmful behaviors, we have an obligation to withdraw that support.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/japp.12467
Keywords: Bibliographie

The Royal Court in the Wake of #MeToo - Fallow, Catriona; Mullan, Sarah Jane (Performing #MeToo: How Not to Look Away, 2021)
Keywords: Bibliographie; Nettoyer; Raphaël

Portrait de la pratique de l'improvisation théâtrale en milieu scolaire et plan d'action pour son optimisation - Garneau, Jocelyn (L'escabeau, 2021)
Keywords: Bibliographie; Nettoyer; Sophie-Anne

Resistance: righteous rage in the age of #MeToo - Goyette, Sue (University of Regina Press, 2021)
"Writers across the globe speak out against sexual assault and abuse in this powerful new poetry anthology, edited by Sue Goyette. These collected poems from writers across the globe declare one common theme: resistance. By exploring sexual assault and violence in their work, each writer resists the patriarchal systems of power that continue to support a misogynist justice system that supports abusers. In doing so, they reclaim their power and their voice. Created as a response to the Jian Ghomeshi case, writers including Joan Crate, Ashley-Elizabeth Best, and Beth Goobie are, as editor Sue Goyette explains, a "multitude, resisting." The collection could not be more timely. The work adds a new layer to the ever-growing #MeToo movement. Resistance underscores the validity of all women's experiences, and the importance of dignifying such experiences in voice, however that may sound. Because once survivors speak out and disrupt their pain, there is no telling what else they can do."–
OCLC: on1178897147
Keywords: 2000-2099; 21st century; Canadian poetry; Crimes against; Poetry; Sex crimes; Sexual abuse victims; Violence against; Women

#MeToo: Theatre Women Share Their Stories - Heyliger, Yvette (Performing #MeToo: How Not to Look Away, 2021)
Keywords: Bibliographie; Nettoyer; Raphaël

#MeToo In Polish Theatre Education - Kwaśniewska-Mikuła, Monika (Philosophy, Sociology, Psychology and History, 2021)
Keywords: Bibliographie; Nettoyer; Raphaël

Justice sera-t-elle enfin rendue? Weinstein, Matzneff, Rozon et les autres - Lamartine, Thérèse (M. Éditeur, 2021)
La librairie Gallimard vous renseigne sur Justice sera-t-elle enfin rendue? Weinstein, Matzneff, Rozon et - les autres de l'auteur Lamartine Thérèse (9782924924303). Vous êtes informés sur sa disponibilité, son prix, ses données techniques. Vous pouvez le commander en ajoutant ce livre à votre panier.
Keywords: Coffre à outils; À ajouter

“Frat Boy” Culture: Will the Activision Lawsuit Reform the Gaming Industry? - Lawrence, Kelsey (2021)
Keywords: Irina; games; gaming; industry; lawsuits; sexual harassment; students

T'as juste à porter plainte (2021)
Keywords: Bibliographie; Nettoyer

Krytyczki as Activists: On Theatre Criticism, Affect, Objectivism and #MeToo in Polish Drama Schools: Interview with Monika Kwaśniewska - Lech, Kasia (Critical Stages/Scènes critiques, 2021)
Keywords: Bibliographie; Nettoyer; Raphaël

Québec, un modèle de « safe space » ? - Léger, Souen (Livres Hebdo, 2021)
Face au #metoo qui a secoué l'édition québécoise à l'été 2020, le milieu littéraire a posé des premiers jalons garantissant des rapports exempts de harcèlement et de violences sexuelles. Une réponse rapide, organisée, qui témoigne de la longueur d'avance prise par le Québec sur les enjeux liés au féminisme et à l'inclusion. De quoi séduire les autrices, françaises notamment. Et donner des idées à la France ?
Keywords: Bibliographie; Nettoyer

Céder n'est pas consentir: une approche clinique et politique du consentement - Leguil, Clotilde (PUF, 2021)

We protect animals well": A structural approach to abusive conduct within circus schools - Matthis, Rosa (Linköping University, 2021)
This master thesis investigates abusive conduct in circus schools. Focus is put on the management level in order to achieve and provide knowledge of measures and attitudes related to prevention. Th ...
Keywords: Bibliographie; Nettoyer; Sophie-Anne

For the Love of Music: Ending Sexual Harassment in the Music Industry - Musicians’ Union (2021)
Keywords: Bibliographie; Nettoyer

Prix Artis : le retrait de la nomination de Maripier Morin confirmé par TVA | Radio-Canada - Radio-Canada (Radio-Canada, 2021)
Keywords: Bibliographie; Nettoyer

A More Pixelated Union: A Look at the Path to Unionization in the Video Game Industry under Trump's National Labor Relations Board - Selfridge, William C. (2021)
Keywords: Irina

Title IX, Esports, and #EToo - Stoever, Jane K (The George Washington Law Review, 2021)
As colleges and universities increasingly award video gaming scholarships, field competitive esports teams, construct esports arenas in the centers of campuses, and promote student interaction through gaming, schools should anticipate the sexual cyberviolence, harassment, and technology-enabled abuse that commonly occur through gaming.
Keywords: Bibliographie; Irina; Nettoyer

Supporting Brave Spaces for Theatre-​Makers Post-#MeToo: A Chicago-Based Study on Rehearsing and Performing Intimacy in Theatre - Studham, Susan Fenty (Performing #MeToo: How Not to Look Away, 2021)
Keywords: Bibliographie; Nettoyer; Raphaël

We Get It: Calling Out Sexism and Harassment in Australia’s Live Performance Industry - Thomasson, Sarah (Performing #MeToo: How Not to Look Away, 2021)
Keywords: Bibliographie; Nettoyer; Raphaël

Super Fluid/Super Black: Translations and Teachings in Transembodied Metaphysics - Whitson, Ni’Ja (Critical Black Futures: Speculative Theories and Explorations, 2021)
Ni’Ja Whitson turns a piece that was originally commissioned as a keynote lecture for the 2020 Collegium for the African Diaspora Dance (CADD) conference, Fluid Black: Dance Back. This chapter is a hybrid text that centralizes Black Transgender and Nonbinary experiences in a conversation of futurity in African Diasporic spirituality, dance traditions, and performativities. Furthermore, Super Fluid/Super Black interrogates beingness through an exploration of astrophysics and global attempts at Black erasure to uncover new strategies of collectivizing under physical, metaphysical, and cosmic bodies that dismantle cisheteronormativity at their core.

An Examination on Sexual Harassment Activities in the South African Professional Performing Arts Industry - Yende, Sakhiseni Joseph (Journal of African Films & Diaspora Studies, 2021)
Keywords: Bibliographie; Nettoyer; Patriarchal power; Performing arts industry; Professional theatres; Raphaël; Sexual harassment; Women in theatre

Le milieu du jeu vidéo est-il indécrottablement discriminatoire? - Baillargeon, Stéphane (Le Devoir, 2020)
Le mouvement #MoiAussi frappe l’industrie de la manette et son sexisme systémique.
Keywords: Bibliographie; Nettoyer

La musique québécoise à l'ère de #MeToo | UQAM (2020)
La musicologue Vanessa Blais-Tremblay analyse l’évolution des chansons évoquant des violences à caractère sexuel.
Section: Recherche

Comme une «gifle» au visage des victimes - Pineda, Améli (Le Devoir, 2020)
L’action collective des Courageuses contre Gilbert Rozon a finalement été rejetée par le plus haut tribunal du pays.

Il n'y aura pas d'action collective contre l’ex-producteur Gilbert Rozon - ICI.Radio-Canada.ca, Zone Justice et faits divers- (Radio-Canada, 2020)
La Cour suprême rejette l’appel du groupe Les Courageuses, qui souhaitait entreprendre un tel recours.
Publisher: Radio-Canada.ca

Les Courageuses déboutées: « C’est d’une injustice incroyable » - Perron, Louis-Samuel (La Presse, 2020)
« C’est d’une injustice incroyable », lâche Anne-Marie Charette, sous le choc. Comme ses sœurs d’armes, la membre du collectif « Les Courageuses » digère mal le refus de la Cour suprême d’entendre leur appel pour autoriser une action collective contre Gilbert Rozon. Mais pas question de « baisser les bras », assure-t-elle.

Sexual Violence and Gender Equality in Grassroots Music Venues: How to Facilitate Change - Hill, Rosemary Lucy; Megson, Molly (IASPM Journal, 2020)
Sexual violence in the music industry is known to impact negatively on women’s participation. We examine how grassroots venues and promoters can implement changes to tackle sexual violence and work towards gender equality. We draw on UK-based, impact-focused research which sought to raise awareness of sexual violence, and to facilitate anti-violence changes within organisations. We find that working across a city’s music scene and engaging with oversight organisations such as local authorities can aid in persuading venues and promoters to seek training. However, for individuals leading on changes, personal experiences of sexual violence as a victim/survivor or bystander are important factors in their decision. We conclude that men in the music industry need to become more aware of the need for change, and willing to act on that awareness; and that more women need to own, manage, and run venues and events.
Keywords: Bibliographie; Gender; Nettoyer; live music; music industry; music venues; prevention; sexual violence

Politique de prévention du harcèlement psychologique ou sexuel au travail et traitement des plaintes - Théâtre de la Ligue Nationale d'Improvisation (2020)
Keywords: Bibliographie; Nettoyer

Le programme Possibilités de justice réparatrice (médiation entre la victime et le délinquant) - Service correctionnel Canada (2020)
Le programme Possibilités de justice réparatrice (médiation entre la victime et le délinquant)
Last Modified: 2023-08-03
Keywords: Bibliographie; Nettoyer

Milieu littéraire : le harcèlement touche une écrivaine sur trois - UNEQ (union des écrivaines et des écrivains québécois, 2020)
L’Union des écrivaines et des écrivains québécois (UNEQ) révèle les résultats d’une enquête menée auprès des autrices et auteurs québécois début octobre. Ces chiffres démontrent sans équivoque le déséquilibre du rapport de force entre les partenaires du milieu, déséquilibre qui mène bien souvent à des comportements inacceptables et à une omerta intolérable.
Keywords: Bibliographie; Nettoyer

#MeToo in Sweden: Museum Collections, Digital Archiving and Hashtag Visuality - Uimonen, Paula (Ethnos, 2020)
In October 2017, the Nordic Museum in Stockholm launched its #metoo collection. The aim was to capture the viral #MeToo campaign that in Sweden has been likened to a (feminist) revolution. Based on archival research, interviews and media analysis, this article explores public submissions to the #metoo collection and analyses the museum’s rationale for collecting what is considered to be difficult cultural heritage. Noting the absence of images in the collection, the article argues that the iconic hashtag #MeToo constitutes an alternative form of digital visuality, here termed hashtag visuality. Hashtag visuality, the article suggests, is an emerging form of visual representation that captures the multimodal logic of social media, blurring distinctions between texts and images. In Sweden, #MeToo hashtag visuality reveals the contradictory prevalence of structural sexism and sexual violence in a country with a national self-image of gender equality and a self-proclaimed feminist government, while affirming feminist agency.
Publisher: Routledge _eprint: https://doi.org/10.1080/00141844.2019.1640264
Keywords: Digital cultural heritage; Myriam; feminist agency; online testimonies; sexual violence; viral campaign

Michel Brûlé reconnu coupable d’agression sexuelle - Béland, Gabriel (La Presse, 2020)
L’éditeur Michel Brûlé a été reconnu coupable mercredi d’agression sexuelle à l’endroit d’une auteure venue le rencontrer pour présenter un manuscrit.
Keywords: Bibliographie; Nettoyer

Patriarchal pits: the gendered experiences of female concert photographers - Lough, Kyser (Journal of Gender Studies, 2020)
While the presence of women in photojournalism is increasing, the way they are treated by their male counterparts remains unbalanced. Drawing from feminist theory and embodiment, this study examines how the gendered experience plays out for women in a particular niche of photojournalism; concert photography. The restricted access of the music scene and the embodied nature of photojournalism combine to present unique barriers for women. In-depth interviews with male and female concert photographers show women still face a form of patriarchal oppression in the field. This is seen through gendered language, such as ‘one of the guys’ versus a ‘mom in the pit’, embodied actions such as direct sexual harassment or indirect benevolent sexism, and in how women are questioned when they identify themselves as a photographer.
Publisher: Routledge _eprint: https://doi.org/10.1080/09589236.2020.1821178
Keywords: Bibliographie; Myriam; Nettoyer; Photojournalism; concert photography; embodiment; feminist theory

Raport de recherche de l'enquête pièces : violences sexuelles en milieu collégial au Québec - Bergeron, Manon; Gagnon, Audréanne; Blackburn, Marie-Ève; M-Lavoie, Dominique; Paré, Caroline; Roy, Sophie; Szabo, Andrea; Bourget, Claudie (Chaire de recherche sur les violences sexistes et sexuelles en milieu d’enseignement supérieur, Université du Québec à Montréal, 2020)
Keywords: Bibliographie; Nettoyer

Recommandations - Rudesse (Facebook, 2020)
Keywords: Bibliographie; Dans le rapport; Sophie-Anne

Webinaire contre le harcèlement et les violences (milieu cirque) pour artistes & travailleuses/eurs (2020)
En partenariat avec Juripop, En Piste vous présente le webinaire qui fût présenté dans le cadre de sa clinique contre le harcèlement et les violences dans le milieu cirque, qui a eu lieu le mardi 25 août 2020. Ce webinaire présente les services du Centre d'aide aux victimes d'actes criminels (CAVAC) et du Groupe d'aide et d'information sur le harcèlement sexuel au travail (GAIHST). Pour plus d'information et de ressources, visitez notre site web : www.enpiste.qc.ca
Keywords: Bibliographie; Nettoyer; À ajouter

Vague de dénonciations : au tour du cirque de faire son examen de conscience - Siag, Jean (La Presse, 2020)
Depuis quelques semaines déjà, les témoignages de violences sexuelles dans le monde du cirque se multiplient sur les réseaux sociaux. Au point où le regroupement national des arts du cirque, En Piste, a décidé de lancer dès mardi avec Juripop une clinique « contre le harcèlement et les violences dans le milieu du cirque ». La Presse a parlé aux instigateurs de Victims_Voices_Circus, espace virtuel où la parole de nombreuses artistes s’est fait entendre.
Keywords: Bibliographie; Nettoyer

Allégations d'agressions sexuelles : Julien Lacroix rayé des nominations aux Gémeaux (Radio-Canada.ca, 2020)
Le jeune humoriste a récemment fait l'objet d'allégations d’agressions et d’inconduites sexuelles.

Milieu de l’édition sain et prévention du harcèlement - Association nationale des éditeurs de livres/Québec Édition (2020)
L’ANEL représente des maisons d’édition de langue française du Québec et du Canada. Québec Édition est dédié au rayonnement international du livre québécois et franco-canadien.

Julien Lacroix visé par des allégations d’agressions et d’inconduites sexuelles - Pineda, Améli (Le Devoir, 2020)
Neuf femmes racontent avoir été victimes d'agressions ou d'inconduites sexuelles de la part de l'humoriste et comédien.
Keywords: Bibliographie; Nettoyer

Harcèlement à Ubisoft : la joueuse professionnelle Stéphanie Harvey témoigne - Agence France-Presse (Radio-Canada, 2020)
Une vague de dénonciations secoue Ubisoft et l'industrie du jeu vidéo depuis quelques semaines.
Keywords: Bibliographie; Nettoyer

Me Too: The Effects of Sexual Harassment and Assault in the Entertainment Industry - Gaal, Cassandra (Backstage Pass, 2020)
Keywords: Entertainment Industry; Myriam

Simple Plan renvoie son bassiste de tournée suite à des allégations d’inconduites sexuelles contre lui - Bibeault, Matt (99scenes, 2020)
C’est la firme de management de Simple Plan, Coalition Music, qui a confirmé la nouvelle. Chady Awad avait justement remplacé David Desrosiers lorsque ce dernier avait pris une pause de SP pour traiter sa dépression de 2017 à 2019. Awad était également photographe et vidéaste pour Simple Plan. Simple Plan a mis fin à sa... View Article
Keywords: Bibliographie; Nettoyer

Des violences sexuelles et des abus de pouvoir dénoncés dans le milieu littéraire - ICI.Radio-Canada.ca, Zone Arts- (Radio-Canada, 2020)
Un groupe de 300 personnes s’est créé pour que les victimes témoignent et pour exprimer des revendications.
Publisher: Radio-Canada.ca

Le milieu littéraire ébranlé par le mouvement de dénonciations - Lapointe, Josée (La Presse, 2020)
Le milieu littéraire fait face lui aussi au mouvement de dénonciations lancé il y a une dizaine de jours. Un groupe de 300 autrices et actrices de la chaîne du livre s’est formé de manière privée pour échanger à propos de cas d’inconduites sexuelles dont beaucoup ont été victimes.
Keywords: Bibliographie; Nettoyer

Violences sexuelles et abus de pouvoir dans le milieu littéraire : il est plus que temps d’agir - UNEQ (Union des écrivaines et des écrivains québécois, 2020)
L’UNEQ donne son appui à la lettre rédigée par un groupe constitué de plusieurs centaines de femmes et minorités de genre déterminées à faire cesser une situation qui ne peut plus durer dans le milieu littéraire.
Keywords: Bibliographie; Nettoyer

Cooperative Gaming: Diversity in the Games Industry and How to Cultivate Inclusion - Cole, Alayna; Zammit, Jessica (CRC Press, 2020)
Description Cooperative Gaming provides context and practical advice regarding diversity in the games industry. The book begins with a deep dive into research literature and the history of diversity in the games industry to provide context around what diversity is and why it is a topic worth considering. The book looks at the different facets of diversity and games, exploring the issues and solutions within game development, studio management, event planning, and more. It provides people with practical advice about being a marginalized person in the games industry and how to be heard, how studios can support inclusive practices, and events can actively become more accessible to a diverse audience. Key Features • Explores the history of diversity in games • Provides important information around what it is like to be a marginalized person in the industry • Gives practical steps to improve the inclusivity of the industry that are designed to aid in contextualizing and upskilling new developers Author Bios Alayna Cole is the managing director of Queerly Represent Me, a not-for-profit championing queer representation in games. Alayna is also a producer at Sledgehammer Games, co-chair of the IGDA LGBTQ+ special interest group, and an award-winning games journalist and game developer. She was featured on the 2016 and 2017 Develop Pacific 30 Under 30 lists and the 2017 and 2019 Develop Pacific Women in Games lists, and she has received several other accolades in the industry. Jessica Zammit started writing in 2013 for Start Select Media, and for the next five years she followed her interest in writing about representations of mental health, diversity, and particularly, sexuality in video games. Jessica has been speaking about diversity in games at conventions such as PAX Australia since 2016 and has been featured on several other discussions in and around the topic of representation in games and games criticism. Along with her co-author, she is co-chair of the IGDA LGBTQ+ special interest group, and she was featured on the 2018 Develop Pacific 30 Under 30 and Women in Games lists.
Google-Books-ID: 0XjtDwAAQBAJ
Keywords: Computers / Programming / Games; Irina

Inconduite sexuelle: deux acteurs largués - Gendron-Martin, Raphaël (Le Journal de Montréal, 2020)
La valse des dénonciations pour inconduite sexuelle touchant le milieu culturel se poursuit.
Keywords: Bibliographie; Nettoyer

Vague de dénonciations: des têtes tombent dans le milieu artistique - Bélanger, Cédric (Le Journal de Québec, 2020)
Les dénonciations font tomber Maripier Morin, Bernard Adamus et le patron de Dare To Care.
Keywords: Bibliographie; Nettoyer

Quand se taire n’est plus une option - Papineau, Philippe; Renaud, Philippe (Le Devoir, 2020)
Keywords: Bibliographie; Nettoyer

Safia Nolin accuse, Maripier Morin s’excuse - Groguhé, Marissa (La Presse, 2020)
L’auteure-compositrice-interprète Safia Nolin a provoqué une onde de choc en accusant mardi Maripier Morin de s’être livrée à du harcèlement sexuel, d’avoir commis une agression physique et d’avoir proféré des propos racistes lors d’une soirée dans un bar il y a deux ans. Des allégations en partie admises par l’animatrice télé, qui a présenté ses excuses le lendemain.
Keywords: Bibliographie; Nettoyer

#ThisIsArtSchool Is Exposing Allegations Of Racism & Sexual Abuse In Montreal Universities - Elliot, Teddy (MTL Blog, 2020)
As stories of racism and discrimination towards Black, Indigenous, and people of colour continue to dominate public discourse, more and more shocking allegations come to light about the lived experiences of systemic racism.
Keywords: Bibliographie; Nettoyer

'Urban' no more: black British music execs call for industry reforms (the Guardian, 2020)
Open letter from new group seeks action on racism and better career development
Section: Music

‘To draw light, you need shadow’: Using graphic art to counter gender based violence in Drawing the Line - Zare, Bonnie (South Asian Popular Culture, 2020)
Women in India cope with an ongoing sense of precarity owing to the frequency of street harassment and sexual violence; this impacts their freedom to travel and sense of autonomous agency. The December 2012 Nirbhaya case, the rape and fatal injury of a Delhi medical student, returned the subject of rape to public discourse leading to mass protests and, eventually, some stronger anti-rape laws; however, #metoo allegations surface weekly, and artists and activists are demanding that the trivialization of rape and verbal abuse stop and active steps be taken to dismantle the cultural scaffolding undergirding twomen's violation. In 2014 a collaboration by Zubaan Press (New Delhi) and the Goethe Institute (Germany) brought a group of Indian graphic artists together to create stories about women’s ground realities and the microaggressions they experience. The resulting publication, Drawing the Line: Indian Women Fight Back, contains fourteen vignettes which reveal the constraints women experience and also illuminate women’s capacity for resilience and boldness. This essay analyzes the forms of resistance imagined in these narratives, how particular stories illuminate slow violence, and what may be lost if we know little about the perpetrators who commit these acts against women.
Publisher: Routledge _eprint: https://doi.org/10.1080/14746689.2020.1775342
Keywords: Essay; India; Indian women; Myriam; Sexual harassment; Gender; graphic novel; sexuality; violence

Contemporary Feminist Protest in Ireland: #MeToo in Irish Theatre - Fitzpatrick, Lisa (Irish University Review, 2020)
This essay draws upon the work of Judith Butler, Sara Ahmed, and Germaine Greer to consider the #MeToo movement and its reflection in the work of the author's students and the scandal at Dublin's G...
Publisher: Edinburgh University Press
Keywords: #MeToo; Bibliographie; Contemporary Feminism; Intergenerational; Intersectional; Nettoyer; Raphaël; Teaching

Le point de vue des improvisatrices au sujet des inégalités et des stéréotypes de genre véhiculés en improvisation théâtrale et ce que ceux-ci révèlent sur la société : une recherche en travail social féministe - Robert Durand, Catherine (2020)
L’improvisation théâtrale est une discipline artistique qui est grandement pratiquée, et ce, au Québec comme dans le monde. De manière implicite et explicite, l’une des réflexions qui revient souvent dans ce milieu est celle de la place différente qu’y occupent les femmes en comparaison avec celle de leurs collègues masculins. Les improvisatrices constatent qu’elles ont une place souvent minoritaire, rappelant les inégalités qui se présentent aussi en société pour les femmes. Ce constat n’est pas nouveau mais puisque très peu de recherches portent sur l’improvisation théâtrale, cette question n’a jamais vraiment été explorée. Ce mémoire pose donc les questions de recherche suivantes : Quelle est la place particulière des femmes dans ce milieu ? Quels inégalités et stéréotypes de genre ce milieu véhicule-t-il ? Et, comment les improvisatrices ont-elles le potentiel d’agir sur ces inégalités de genre et de défaire les stéréotypes ? Les objectifs de recherche sont : 1) Recueillir le point de vue des improvisatrices au sujet de leur pratique ; 2) Comprendre la situation particulière des femmes dans ce milieu ; 3) Identifier les stéréotypes et les inégalités de genre véhiculés en improvisation théâtrale ; 4) Relier ces stéréotypes et inégalités de genre à ceux véhiculés en société. Le cadre théorique de ce mémoire est celui du travail social féministe qui s’intéresse notamment aux oppressions et inégalités vécues par les femmes au quotidien, dans « l’ordinaire » de leur vie, ce dont la pratique de l’improvisation théâtrale fait partie. Ancrée dans une méthodologie féministe et qualitative, 8 entretiens semi-dirigés ont été réalisées. L’analyse et la discussion de ces résultats a mis de l’avant l’idée que l’improvisation théâtrale est un espace de reproduction de la socialisation genrée mais aussi un lieu de résistances et donc, plus globalement de négociation entre ces deux pôles. En conclusion, sont soulignés certains nœuds féministes de la recherche et des pistes de solutions pour y pallier. _____________________________________________________________________________ MOTS-CLÉS DE L’AUTEUR : Féminisme, Improvisation théâtrale, Socialisation genrée, Stéréotypes de genre, Résistances, Recherche féministe, Travail social féministe.
Place: Montréal (Québec, Canada) Publisher: Université du Québec à Montréal

Mobilisations féministes sur Facebook et Twitter: Le cas du mouvement #StopCultureDuViol au Québec - Hübner, Lena A.; Pilote, Anne-Marie (Terminal, 2020)

Comedy in the Era of #MeToo: Masking and Unmasking Sexual Misconduct in Stand-Up Comedy - Oppliger, Patrice; Mears, Kathryn (The Dark Side of Stand-Up Comedy, 2020)
With the announcement of allegations of sexual harassment and sexual assault against beloved comedians, we ask, “Can one separate the art from the artist?” Comedians are supposed to bring audiences joy and laughter; however, this role is challenged when there is incongruity between the comic persona and the real-life misdeeds of comedians. We explore the rise of the #MeToo movement and the role of comedy in exposing as well as masking allegations against Bill Cosby, Louis C.K., Al Franken, and Aziz Ansari. Guided by disposition theory and disengagement models, findings reveal factors of race, gender, and personal relationships appear to influence comedians’ assessment of fellow comedians accused of sexual misconduct. Audience members also appear to experience moral disengagement.
Keywords: Bibliographie; Nettoyer; Sophie-Anne

Louis C.K.’s time’s up time out: rereading persona post-scandal - Piper, Melanie (Celebrity Studies, 2020)
Keywords: Bibliographie; Nettoyer; Sophie-Anne

Are Female Clowns Politically Incorrect? A Case Study on Female Clowns’ Political Engagement at the 7th “Esse Monte de Mulher Palhaça” festival in Rio de Janeiro - Cézard, Zed (Cadernos de Arte e Antropologia, 2020)
By linking the notion of politics with clown practices played out during the biennial festival «Esse Monte de Mulher Palhaça» in Rio de Janeiro (2018), dedicated specifically to female clowns, the relations between politics and feminism are raised, as well as the question of the place of clowns and women within the social system in which they act. In addition to reassessing the concept of politics through this new field of application, looking at what artistic practices convey or denounce as inequalities, allows us to identify politicized and political social elements. The private sphere, the power relations, the importance of gender, and the body and sexuality as treated in the festival’s performances raise political issues. We are lead to think of the phenomenon of Brazilian female clowns as a political space of claims, in particular feminist ones, and a resistance to dominant sexist normativity.
Keywords: Bibliographie; Brazil; Nettoyer; Sophie-Anne; female clowns; feminism; activism; politics

Non-Consensual Sexual Contact at Electronic Dance Music Parties - Palamar, Joseph J.; Griffin, Marybec (Archives of Sexual Behavior, 2020)
Non-consensual sexual contact in bars is common, but few studies have focused on the extent of this problem at electronic dance music (EDM) parties, which are growing in popularity. We aimed to estimate prevalence and correlates of non-consensual sexual contact among individuals who attend EDM parties in New York City (NYC). Adults (ages 18–40 years) entering EDM parties in NYC were surveyed in 2018 using time–space sampling. Participants (n = 1005) were asked whether they had experienced unwanted or uninvited sexual contact including unwanted groping, kissing, or touching at an EDM party. We estimate that 15.2% of EDM party attendees in NYC have experienced non-consensual sexual contact at such parties. The majority (62.5%) of those reported that it occurred 1–2 times and 49.1% were usually or always drunk or high during the encounter(s). Almost all women experiencing non-consensual contact (99.5%) were all or mostly touched by men; 38.6% of men were all or mostly touched by other men. Women were at more than twice the odds of reporting non-consensual sexual contact than men (aOR = 2.38, p < .05) with 21.8% of women reporting experiencing non-consensual sexual contact compared to 11.0% of men. Among women, those ages 18–24 were at over twice the odds (aOR = 2.75, p < .05) of experiencing non-consensual sexual contact than those ages 25–40. EDM party environments can increase susceptibility to non-consensual sexual contact. Prevention needs to be geared toward those at risk, and education is needed for those likely to commit non-consensual sexual contact.
Keywords: Dance music; Drug use; Non-consensual sex; Sexual assault

Gendered Violence at International Festivals: An Interdisciplinary Perspective - Platt, Louise; Finkel, Rebecca (Routledge, 2020)
Gendered Violence at International Festivals is a groundbreaking collection that focusses on this highly important social issue for the first time. Including a diverse range of interdisciplinary studies on the issue, the book contests the widely held notion that festivals are temporal spaces free from structural sexism, inequalities or gender power dynamics. Rather, they are spaces where these concerns are enhanced and enacted more freely and where the experiential environment is used as an excuse or as an opportunity to victim blame and shame. In this emerging and under-researched area, the chapters not only present original work in terms of topics but also in theoretical and methodological approaches. All of the chapters are cross- or interdisciplinary, drawing on gender, sexualities, cultural and ethnicity studies. Studies from a range of highly regarded academics based around the world examine the subject by looking at examples from a wide range of destinations, including Spain, Argentina, Nigeria, Zimbabwe, Australia, Canada and the UK. This significant book progresses understanding and debates about gendered festival experiences and emphasises the symbolic and physical violence often associated with them. This will be of great interest to, undergraduate and postgraduate students and academics in the field of Events Studies. It will also be of use to practitioners or non-profit workers in the festival industries, including festival management organisations and planning committees.
Google-Books-ID: Q6bYDwAAQBAJ
Keywords: Business & Economics / Industries / Hospitality; Travel & Tourism

Sexual violence and nightlife: A systematic literature review - Quigg, Zara; Bigland, Charlotte; Hughes, Karen; Duch, Mariangels; Juan, Montse (Aggression and Violent Behavior, 2020)
Preventing and responding to sexual violence in nightlife settings is increasingly of global concern. The goal of this article was to identify and summarise academic studies on nightlife-related sexual violence. Specifically, to explore the nature, extent and consequences of, or associations with nightlife-related sexual violence, and interventions to prevent and respond. Of the 61 studies identified, 29 explored or reported on the nature of nightlife-related sexual violence, 22 provided information on extent, 38 on associations, and 19 on prevention and response. The majority of studies had been implemented in the past ten years (2009–2018) and in high-income countries. The review illustrates that nightlife-related sexual violence is pervasive, with lifetime prevalence reaching over 50% amongst numerous study samples. Studies suggest that a combination of factors at an individual, relationship, and community/environmental level is associated with nightlife-related sexual violence. No studies directly explored consequences, and few studies evaluated prevention and response approaches. Globally, further research is required to understand nightlife-related sexual violence, and inform the development of prevention programmes across all but particularly low and middle-income countries. Critically, interventions aimed at preventing and responding to nightlife-related sexual violence require thorough evaluation, with findings disseminated in both lay and academic literature.
Keywords: Bars; Bibliographie; Nettoyer; Nightlife; Prevention; Rape; Sexual; Violence

#metoo 2.0 to #meNOmore: Analysing Western Reporting About Sexual Violence in the Music Industry - Baker, Andrea; Williams, Katrina; Rodrigues, Usha M. (Journalism Practice, 2020)
In October 2017, #metoo 2.0 reinforces the gendered sexual violence in the creative sector [Marghitu, 2018. “It’s Just art: Auteur Apologism in the Post-Weinstein era”, Feminist Media Studies, 18(93): 491–494] Building on this movement, on 11 November that year, 2912 women “testified about the situation in the Swedish music industry”, signing an open letter condemning sexual violence [Nyheter, 2017. “2192 Women in the Swedish Music Industry Behind Appeal Against Sexism.” Dagens Nyheter, November 17. https://www.dn.se/kultur-noje/2192-women-in-the-swedish-music-industry-behind-appeal-against-sexism/]. After the Swedish initiative, on 12 December 2017, the #meNOmore hashtag was established by 1000 women who signed an open letter to the Australian music industry speaking out against similar behaviour [Whyte, 2017a. “Artists Speak Out Against Sexual Harassment in the Music Industry.” AM – ABC Radio, December 13. https://www.abc.net.au/radio/programs/am/sexual-harassment-in-the-music-industry/9253956]. Using a content analysis framework, this study examines the media framing of 26 stories about #meNOmore by the Western press from 22 November 2017 (height of the Swedish campaign) to 21 December 2017 (a week after the hashtag surfaced in Australia). Research from journalism studies and musicology highlights that sexual violence is historically engrained in the media and music industries. However, findings from our study of the first month’s coverage of the #meNOmore content analysis in 2017 reveal that media reports about women and sexual violence were framed around addressing gender inequality and systemic structural issues in the music industry. This raises the question, has the media has turned a corner when covering sexual violence in the post #metoo era?
Keywords: Bibliographie; Nettoyer

La Cour d’appel donne raison à Gilbert Rozon - Corriveau, Jeanne (Le Devoir, 2020)
Le tribunal a annulé l’autorisation de l’action collective des Courageuses contre l’ancien magnat de l’humour.
Keywords: Bibliographie; Nettoyer

“These things happen”: Hashtag activism and sexual harassment in the South African film and television industries - Paleker, Gairoonisa (Agenda, 2020)
In August 2017, the South African advocacy group Sisters Working in Film and Television (SWIFT) launched the #ThatsNotOk campaign, which has to date produced six episodes of short films (one episode in two parts, making it seven in total) elucidating the different forms sexual harassment takes, and the different scenarios in which it occurs, in the South African film and television industries. This profile engages with SWIFT and the Public Service Announcement (PSA) films as discursive sites and texts respectively, and provides textual analyses of the PSAs in the context of digital feminism and feminist activism against sexual harassment in the film and television industries. The profile motivates that as expressions of digital feminism, the PSAs critique the pervasiveness and normalisation of sexual harassment, while failing to engage with or critique the neoliberal logic and structure of the film and television industries.
Publisher: Routledge _eprint: https://doi.org/10.1080/10130950.2020.1720162
Keywords: #ThatsNotOk; Irina; South African film and television; digital feminism; hashtag activism

Unwanted Sexual Attention in the Night-Time Economy: Behaviors, Safety Strategies, and Conceptualizing “Feisty Femininity” - Gunby, Clare; Carline, Anna; Taylor, Stuart; Gosling, Helena (Feminist Criminology, 2020)
Almost nothing is known about ?unwanted sexual attention? and women?s navigation of it when in bars and nightclubs. Using focus group discussions, this article addresses that gap. It develops knowledge of the behaviors that constitute unwanted, the safety strategies used to manage them, and examines how these practices underpin gender performance in night-time spaces: environments renowned for the dilemmas they pose to women. We then use these data to develop the concept ?feisty femininity? to highlight a neglected form of femininity that overtly resists unwanted encounters. This femininity can arguably play a role in efforts aimed at ending gendered violence.
Publisher: SAGE Publications

Aide aux Trans du Québec (Aide aux Trans du Québec, 2020)
Ligne d’écoute et de référenceSans frais : 1 (855) 909-9038, poste 1Nous écrireGroupes de soutien hebdomadaires sur ZoomPour et par les personnes trans, non binaires et en questionnement.Nos services Diapositive précédente Diapositive suivante Notre mission Les buts principaux de l’ATQ sont d’apporter de l’aide et de briser l’isolement des personnes trans, non-binaires et en questionnement. […]
Keywords: Coffre à outils; À ajouter

Entente collective entre l'Union des artistes et l'Association québécoise de la production médiatique (Artistes interprètes) (2020)
Keywords: Bibliographie; Nettoyer

Best Practices for scenes involving nudity, intimacy, simulated sex and sexual violence - ACTRA (2020)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Land acknowledgment et Equality statement - ACTRA (2020)

Des violences sexuelles et des abus de pouvoir dénoncés dans le milieu littéraire - Bourel, Fanny (Radio-Canada, 2020)
Un groupe de 300 personnes s’est créé pour que les victimes témoignent et pour exprimer des revendications.
Publisher: Radio-Canada.ca
Keywords: Bibliographie; Nettoyer

Le jour où Éric Salvail est tombé - Bourgault-Côté, Guillaume (Le Devoir, 2020)
Keywords: Bibliographie; Nettoyer

Expériences de comportements sexualisés inappropriés, d’agressions sexuelles et de discrimination fondée sur le genre vécues par les travailleurs dans les provinces canadiennes, 2020 - Burczycka, Marta (Statistique Canada, 2020)
Keywords: Bibliographie; Nettoyer

‘Put some balls on that woman’: Gendered repertoires of inequality in screen composers’ careers - Cannizzo, Fabian; Strong, Catherine (Gender, Work & Organization, 2020)
This study contributes to debates about gendered career outcomes in the creative industries using data collected in interviews with Australian screen composers. We identify how gendered inequalities are legitimated through professional norms by comparing the responses of screen composers on barriers to women’s advancement. The article explores how three distinct interpretive repertoires help reproduce the gender inequality regime present in the screen composition field. These repertoires are ‘art vs. equality’, where working towards equality can be framed as antithetical to artistic ideals; ‘gendered music’, where men and women are posited as making fundamentally different types of music; and ‘confidence’, where men are framed as innately possessing certain entrepreneurial skills vital to success in the creative industries, while women both shoulder the blame for not possessing such skills and recognize the risks inherent for them in performing confidence. By focusing on repertoires, this study describes the means by which gender-based discrimination is made overt and offered justification among screen composers, posing challenges to organizations and individuals seeking to address gender inequality in the profession.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/gwao.12496
Keywords: Australia; Musique de film; Myriam; composers; creative industries; cultural industries; gender inequality; sexism

La musique québécoise à l'ère de #MeToo - Caza, Pierre-Etienne (Actualités UQÀM, 2020)
La musicologue Vanessa Blais-Tremblay analyse l’évolution des chansons évoquant des violences à caractère sexuel.
Keywords: Bibliographie; Nettoyer

Gender Equality in British Film-making: Research, Targets, Change - Cobb, Shelley; Williams, Linda Ruth (Women in the International Film Industry: Policy, Practice and Power, 2020)
In October 2017, the British Film Institute declared that it would commit to specific targets for gender equality and diversity in key production roles on films with support from the Film Fund. This decision by the BFI to set targets, arguably, did not come just from their own diversity and inclusion goals. Activist film-makers had previously called for targets for the Film Fund, especially for women directors. This chapter will give an accounting of the current state of gender (in)equality in the UK industry by: outlining new research that has clarified the stagnant inequality in the UK film industry; articulating the key role of a network of activist groups (that include researchers, professional and campaigning bodies, exhibitors and film-makers) to bring attention to the problem; putting pressure on the film industry and public bodies; and summarising institutional responses to that pressure since 2016, with a critical analysis of the potential and limits of the BFI’s relatively recently implemented diversity and equality targets.
Keywords: Bibliographie; Irina; Nettoyer

Les personnes victimes d'agressions sexuelles ou de violence conjufale face au système de justice pénale: état de situation - Conseil du statut de la femme (Québec, Conseil du statut de la femme, 2020)

Les personnes victimes d’agressions sexuelles ou de violence conjugale face au système de justice pénale: état de situation - Conseil du statut de la femme (Conseil du statut de la femme, 2020)

Violences sexuelles et abus de pouvoir dans le milieu littéraire: il est plus que temps d’agir - Déclaration commune (Liberté – Art et politique, 2020)
Déclaration commune
Keywords: Bibliographie; Nettoyer

Je n'en ai jamais parlé à personne - Delvaux, Martine (Éditions Heliotrope, 2020)
«En octobre 2017, devant la vague de témoignages suscitée par le mouvement #moiaussi, j’ai senti une urgence : une fois sorties du silence, nous ne devions pas y retourner. C’est la raison pour laquelle j’ai lancé un appel. Ce livre est une chambre d’échos. Un chœur. Sans déesse ni héroïne en tête, des voix avancent. Nous faisons front commun.» Martine Delvaux «Je n'en ai jamais parlé à personne» : paroles recueillies et agencées par Martine Delvaux
Keywords: Bibliographie; Nettoyer

Teaching Tertiary music in the #metoo era - Devenish, Louise; Sun, Cecilia; Hope, Cat; Tomlinson, Vanessa (Tempo, 2020)
Abstract Over the past two decades significant changes in approaches to gender equity have taken place in the fields of contemporary music and music research. However, women in music are still disadvantaged in terms of income, inclusion and professional opportunities. In Australia a national approach to improving gender equity in music has begun to emerge as once-controversial strategies trialled by four tertiary institutions have become established practices. This article discusses successful inclusion strategies for women in music, including the commitment to gender-balanced programming across all concerts at Queensland Conservatorium of Music by 2025, the introduction of mandatory quotas in recital programmes at Monash University, mentoring programmes for women composers at Sydney Conservatorium of Music, and the development of coursework devoted to women in music at The University of Western Australia, as well as other initiatives that have emerged from them, both within and beyond the institution. Each approach is examined in the context of broader global discussions around gender and feminism. The public willingness to engage in discussions over sexual harassment, sexual assault and gender discrimination in the workplace that has resulted from the #MeToo movement is cited as key in influencing the engagement of students and professionals with these strategies and subsequent influence on performance practices, project development and presentational formats in new music.
Keywords: Myriam

#TimesUp on Individual Litigation Reform: Combatting Sexual Harassment through Employee-Driven Action and Private Regulation - Dugan, Natalie (Columbia Journal of Law and Social Problems, 2020)
Keywords: Bibliographie; Irina; Nettoyer

Sexual harassment and violence at Australian music festivals: Reporting practices and experiences of festival attendees - Fileborn, Bianca; Wadds, Phillip; Tomsen, Stephen (Australian & New Zealand Journal of Criminology, 2020)
Despite the well-documented under-reporting of sexual violence, to date, no research has considered reporting practices within the specific context of music festivals. Drawing on 16 in-depth interviews with victim-survivors, this article examines survivors’ experiences of (non)reporting sexual violence in festival settings. We argue that while some barriers to reporting are shared across contexts, others play out in context-specific ways. Our research argues that the liberal, often transgressive culture of music festivals, combined with site-specific policing practices and spatial context, creates unique impediments to reporting with particular implications in responding to, and aiming to prevent, sexual violence at music festivals.
Keywords: Bibliographie; Camille; Nettoyer

Rapport de recherche sur l'état du milieu du spectacle d'improvisaiton théâtrale au Québec - Garneau, Jocelyn (Le théâtre de la Ligue Nationale d'Improvisation et la Rencontre Théâtre-Ados de Lavac avec l'appui financier du Ministère de la Culture et des Communications du Québec, 2020)
Keywords: Bibliographie; Nettoyer; Sophie-Anne

Sexual Harassment in the Post-Weinstein World - Grossman, Joanna L. (UC Irvine Law Review, 2020)
Keywords: Myriam; film industry

Sexual violence at live music events: Experiences, responses and prevention - Hill, Rosemary Lucy; Hesmondhalgh, David; Megson, Molly (International Journal of Cultural Studies, 2020)
Recent media reporting has highlighted that incidents of sexual violence frequently occur at live music events. Sexual violence has significant impacts on the health of those who experience it, yet little is known of how it impacts on everyday engagements with music, nor what measures venues and promoters might take to prevent and respond to incidents. Through interviews with concert goers, venue managers, promoters and campaigning groups, we investigated experiences of sexual violence at indie, rock, punk and funk gigs in small venues in one English city. We show that sexual violence at live music events significantly impacts on (predominantly) women’s musical participation. We argue that venues and promoters must work proactively to create musical communities that act as a defence against the normalisation of sexual violence, taking inspiration from safer space policies.
Keywords: Camille; gender; live music; prevention; safe spaces; sexual violence; unwanted sexual attention

Can You Come Back from Being Cancelled? A Case Study of Podcasting, Cancel Culture, and Comedians during #MeToo - Holman, Kylie J. (University of Nebraska, 2020)
Cancel culture is a new phenomenon of public shaming, facilitated by social media. This type of public shaming is accepted due to the alleged transgression of those who are cancelled. Social understanding of cancel culture does not generally allow for redemption. Using the theoretical framework of Feminist Media Studies (Van Zoonen, 1994) and Media Framing Theory (Gitlin, 1980), this study reveals the media’s role and power in the cancelling process. This study utilized a mixed-methods approach of case study and text analysis of episodes from the pop culture and politics podcast, Keep It. The case study focused on podcast episodes pertaining to two comedians cancelled for allegations of sexual misconduct in the #MeToo era [Oct. 2017 – Present]: Aziz Ansari and Louis C.K. The study also provided comparative cases of other comedians and comedic actors who were cancelled. Findings add to our understanding of cancel culture and appropriate methods of redemption for those who are cancelled.
Keywords: #MeToo; Bibliographie; Cancel culture; Comedians; Nettoyer; Podcasting; Redemption; Sophie-Anne

Experiencing Male Dominance in Swedish Film Production - Jansson, Maria; Wallenberg, Louise (Women in the International Film Industry: Policy, Practice and Power, 2020)
Sweden has been hailed for its recent success in increasing the number of female directors, scriptwriters and producers. Published reports, panel discussions and a vast number of press conferences on the pressing matter of gender equality within the industry together with a 5050 quota have all put the Swedish film industry—and its CEO Anna Serner—on the map. However, the last couple of years has disclosed several scandals regarding sexism and discrimination in the Swedish film industry—just as in other national film industries. This paper sets out to discuss how female film workers (e.g., directors, actors and producers) understand and negotiate their experiences of male dominance within their work context. Based on a series of interviews with women working in Swedish film from the early 1960s until today, we analyze similarities and differences in experiences as well as how these experiences are explained by the interviewees. Their stories are analyzed by using feminist institutional theory to understand how policy, funding schemes and other institutional aspects are intertwined with their experiences. The paper sets out to analyze three themes: (1) comments and suggestions during production and post-production regarding female protagonists; (2) experience of gender trouble in the process of fundraising; and (3) strategies used by the interviewed filmmakers to produce a more women-friendly environment during productions.
Keywords: Irina

Faire face au harcèlement en milieu de travail culturel: Un rapport sur les mécanismes de dénonciation et d’enquête existants et potentiels pour travailleurs et employeurs culturels - Labine, Lise; LeSage, Jeanne; Gagnon, Grégoire (Conseil des ressources humaines du secteur culturel, 2020)
Keywords: Bibliographie; Coffre à outils; Nettoyer

Vague de dénonciations : un groupe de soutien est créé dans le milieu littéraire - Larouche, Katy (Radio-Canada, 2020)
Keywords: Bibliographie; Nettoyer

Women in the International Film Industry: Policy, Practice and Power - Liddy, Susan (Springer International Publishing, 2020)
Keywords: Irina

Identity work in female-led creative businesses - Martin, Lynn; Jerrard, Bob; Wright, Lucy (Gender, Work & Organization, 2020)
This study explores the identity work carried out by three female owner-managers in creative industry businesses, identified in Government reports as a discriminatory industrial sector for women in the UK. Through the development of narratives by the owners and other participants, observation of practice and review of online and offline materials, three cases emerged. These showed overlapping, different identities developed and performed through identity work. Each presented rational and logical persona as business leaders despite observation showing extensive use of intuition and gut feeling in both creative and entrepreneurial aspects of the business. Intuition and gut feeling were seen as inappropriate at work as they belonged to the home sphere, emotionally based and therefore automatically unreliable. While occupying male stereotypes and avoiding the female realm of emotion at work, these women expressed femininity through their emphasis on the maternal, ‘being a good mother' as a desired ideal being embedded in work as well as home practice.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/gwao.12357
Keywords: Myriam; creative industries; entrepreneurship; gender; identity; innovation

Conceptualising safety and crime at UK music festivals: A gendered analysis - Measham, Hannah King, Fiona, Hannah Bows (Gendered Violence at International Festivals, 2020)
There has been a global surge in music festivals over the last decade, especially in Europe. In the UK, it is estimated that more than 3.5 million people attended the 230 music festivals in 2015 (Time Out, 2015; UK Festival Awards, 2016). Despite a body of research indicating higher levels of crime, particularly acquisitive and violent crime in spaces with similar characteristics (e.g. nightclubs, pubs and gigs), there have been no previous studies examining the occurrence or nature of crime at music festivals. This chapter brings together conceptual developments across the social sciences to shed light on the underexplored subject of gender and safety at music festivals, a leisure location of growing interest to social scientists and of significant growth within the events industry. This chapter presents data from the first UK study to explore safety and crime at music festivals and raises questions regarding the distinctive features of commercialised music festivals, the extent to which they can be considered transgressive or countercultural spaces and what might be the distinctions, if any, of gendered sexual violence within such spaces.
Num Pages: 18

The most beautiful job in the world: lifting the veil on the fashion industry - Mensitieri, Giulia; Lehrer, Natasha (Bloomsbury Visual Arts, Bloomsbury Publishing Plc, 2020)
Keywords: Fashion; Myriam

De nouveaux gestes déplacés de musiciens dénoncés - Papineau, Philippe (2020)
Keywords: Bibliographie; Nettoyer

Video Games - Pletcher, Isaac (Communication Technology Update and Fundamentals, 2020)
A video game is an interactive digital entertainment that you “play” on some type of electronic device. The medium has existed in some form since the 1950s, and since that time, has become a major worldwide industry, spawning technology battles and being birthed in new iterations that become ubiquitous parts of modern life. This chapter will look at the development of video games from the beginning, through the golden age, and into the era of the console wars. Further, it will point out the enormous revenues video games make, and show how the #metoo movement and unions are working to change the face of the industry.
Num Pages: 12
Keywords: Irina

Ubisoft : les démissions ne viendront pas à bout de la toxicité, disent des employés - Prévost, Hugo (Radio-Canada, 2020)
Le géant du jeu vidéo est plongé dans la tourmente depuis des semaines en raison d'allégations de harcèlement.
Keywords: Bibliographie; Nettoyer

Dénoncer le harcèlement dans le milieu de l'improvisation (D'Est en Est, 2020)
Keywords: Bibliographie; Nettoyer

Cours/Courses - ReadtheCode (2020)
Keywords: Coffre à outils; À ajouter

Le point de vue des improvisatrices au sujet des inégalités et des stéréotypes de genre véhiculés en improvisation théâtrale et ce que ceux-ci révèlent sur la société : Une recherche en travail social féministe - Robert Durant, Catherine (Université du Québec à Montréal, 2020)
Keywords: Bibliographie; Coffre à outils; Nettoyer; Sophie-Anne

Cultural sexism: the politics of feminist rage in the #metoo era - Savigny, Heather (Bristol University Press, 2020)

Gendered Barriers In The Gaming Industry - Singh, Tanya (Journal of Sports Law, Policy and Governance, 2020)
As of 2019, there are an estimated 2.5 billion garners globally. Roughly half of all garners are female. Despite the figures, there is a serious underrepresentation of female gainers in the professional gaming and game development community. It is thus important to examine the underlying causes hindering equally capable female gainers and game developers from pursuing a serious career in gaming, at par with their male counterparts.In this article, the authorexamines the impact of the culturalassociationof games with the male demography, stereotypes andstructuralbarrierslimiting women from realizing theirfullpotential, female representation in video games and workplace, pervasive misogyny and sexual harassment of women across all levels in the industry, and lastly, the steps that can be taken to better the status quo in favour of women.
Keywords: Bibliographie; Irina; Nettoyer

Les expériences des victimes de violence sexuelle dans les programmes de justice réparatrice - Wemmers, Jo-Anne; Parent, Isabelle; Casoni, Dianne; Quirion, Marika Lachance (Centre international de criminologie comparée, 2020)
Keywords: Bibliographie; Expérience; Justice; Nettoyer; Système judiciaire; Victimes; Violence

A Nonbinary Actor Prepares (for Battle) - Woodzick, K. Bylines (Theatre Topics, 2020)
Publisher: Johns Hopkins University Press
Keywords: Bibliographie; Nettoyer; Raphaël

A Single Drop of Water: Vulnerability, Invisibility, and Accountability in South Korean Theatre’s Moment of Crisis - Younghee, Park; Neideck, Jeremy (Performance Paradigm, 2020)
In early 2018, encouraged by the #MeToo movement sweeping the Western media landscape, Korean actor Park Younghee took to Facebook to write of her experiences of sexual harassment at the hands of a prominent theatre director and academic in the 1990s. While Younghee didn’t publicly name her abuser, it was not long before the social media machine identified Oh Tae Suk as the man she alluded to, and his world-renowned Geukdan Mokwha as the site of her abuse. Days later, prolific theatre director Kim Soo-hee made allegations of violence and sexual abuse against Lee Yoon-taek, the artistic director of the juggernaut theatre company Yeonhuidan Georipae, setting off a firestorm in the South Korean Media that has yet to die down. In South Korea, public performances of grief, allyship, and holding the government to account are hallmarks of democratic transformation. In this article, Park Younghee tells parts of her story to longtime collaborator Jeremy Neideck, and they attempt to weave a coherent narrative out of their yearlong discussion about the social, cultural, and political histories of Korea. This article seeks to illuminate, but not necessarily explain, the environments in which men like Lee Youn-taek and Oh Tae Suk were able to perpetrate abuse.
Keywords: Bibliographie; Nettoyer; Raphaël

Towards Gender Equality in the Music Industry: Education, Practice and Strategies for Change - Strong, Catherine; Raine, Sarah (Bloomsbury Publishing USA, 2019)
Gender inequality is universally understood to be a continued problem in the music industry. This volume presents research that uses an industry-based approach to examine why this gender imbalance has proven so hard to shift, and explores strategies that are being adopted to try and bring about meaningful change in terms of women and gender diverse people establishing ongoing careers in music. The book focuses on three key areas: music education; case studies that explore practices in the music industry; and activist spaces. Sitting at the intersection between musical production, the creative industries and gender politics, this volume brings together research that considers the gender politics of the music industry itself. It takes a global approach to these issues, and incorporates a range of genres and theoretical approaches. At a time when more attention than ever is being paid to gender and music, this volume presents cutting edge research that contributes to current debates and offers insights into possible solutions for the future.
Google-Books-ID: DV62DwAAQBAJ
Keywords: Music / Business Aspects; Music / Philosophy & Social Aspects; Social Science / Gender Studies; Social Science / Women's Studies

The Changing Roles of Female Visual Artists in Morocco - El Azhar, Samir (Journal of Global Initiatives: Policy, Pedagogy, Perspective, 2019)
Keywords: Myriam

Le #moiaussi de la danse - Lauzon, Véronique (2019)
Des acteurs du milieu de la danse brisent le silence sur les abus de pouvoir, le harcèlement psychologique et les agressions sexuelles vécus. Deux ans après #moiaussi, une quinzaine d’entre eux tentent de faire éclater l’omerta qui plombe cet environnement jugé toxique.
Keywords: Bibliographie; Nettoyer

Les abus et la «loi du silence» dans la danse - Morneau, Caroline (Le Journal de Québec, 2019)
Abus psychologiques, physiques, sexuels: après les milieux du cinéma et de l’humour, on réalise que celui de la danse comporte son lot de scandales.
Keywords: Bibliographie; Nettoyer

Mapping the Stage Differently: Theatre #MeToo Movement and Internet Culture in South Korea - Yoon, Soo Ryon (Gender IT : Feminist reflexion on Internet policie, 2019)
Keywords: Bibliographie; Nettoyer; Raphaël

Winnipeg comedy club defends decision to book Louis C.K. despite sexual misconduct - Caruk, Holly (CBC News, 2019)
An American comedian and actor who admitted to sexual misconduct will take the stage at a Winnipeg comedy club next week but not everyone is lining up for tickets.
Keywords: Bibliographie; Nettoyer; Sophie-Anne

Rhetorical Constellations and the Inventional/Intersectional Possibilities of #MeToo - Bloomfield, Emma Frances (Journal of Communication Inquiry, 2019)
Publisher: SAGE Publications Inc
Keywords: Bibliographie; Nettoyer

The impact of intervention measures on sexual harassment in the film and television industry - Eng, Ben; McKinney, Ralph; Shao, Lawrence (Journal of International Management Studies, 2019)
Since 2017, increased sexual harassment incidents have been reported in Hollywood; yet, little guidance has been offered on how organizations, which are informally governed by their network members, can effectively reduce sexual harassment. Building upon the theory of network governance, this paper suggests social mechanisms, which are used to coordinate and safeguard exchanges between Hollywood organizations, are more effective at reducing incidents of workplace sexual harassment than traditional strategies. These social mechanisms direct change to the macroculture through collective sanctions that damage the perpetrators reputation and restrict access to network opportunities. In essence, perpetrators become toxic assets that Hollywood avoids and this avoidance is similar to economic sanctions that can deter sexual harassment.
Keywords: Bibliographie; Irina; Nettoyer

Counting the music industry: the gender gap - Bain, V (Counting the music, 2019)

Politique de prévention et d’intervention contre l’intimidation, le harcèlement et la violence - École nationale de cirque - Montréal (2019)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer; Sophie-Anne

“Sorry Not Sorry”: Apologizing in the Wake of #MeToo - MacArthur, Michelle (Canadian Theatre Review, 2019)
This article explores what it means to apologize for misconduct in the #MeToo era through three examples from the Canadian theatre industry: a private apology (Randolph College for the Performing Arts), a public apology (Citadel Theatre), and an absent apology (Soulpepper Theatre). Understanding a public apology as a performative utterance meant to restore a community’s trust, this article suggests the importance of examining the paratexts generated by and around it that help it achieve its function. From policy revisions, to media interviews, to public forums, these materials and events are crucial in the meaning-making process in which a #MeToo apology is engaged, especially when the theatre community’s access to the apology itself is limited. The article concludes by situating its case studies in relation to issues of misconduct in theatre education and training institutions.
Keywords: #MeToo; #SorryNotSorry; Bibliographie; Canadian theatre; Citadel Theatre; Nettoyer; Randolph College for the Performing Arts; Raphaël; Soulpepper Theatre; public apologies

The Experiences of Women Professionals in the Film Industry in Turkey: A Gender-Based Study - Gürkan, Hasan (Acta Universitatis Sapientiae, Film and Media Studies, 2019)
The article is based on 20 in-depth interviews with women professionals conducted for a more comprehensive study focusing on gender roles within the film and television industry in Turkey. This study examines the career possibilities for women, the experience of being a woman working in television and cinema, and the working environment, including work-life balance issues, experiences of discrimination and experiences of sexism. The hypothesis of this study is that film industry is male-dominated, and women have to struggle to be able to prove themselves in this industry in the 21st century in Turkey, where the position of women is made even more difficult by the gender role codes and the structure of Turkish society.
Keywords: Irina

Climat toxique dans le milieu de l’humour, malaises en conférence de presse - Piqueur, Lucie (Urbania, 2019)
Le regroupement « Pour les prochaines » souhaite en finir avec la culture du viol en humour, mais c'est pas gagné.
Keywords: Bibliographie; Nettoyer

Pour les prochaines dénonce une culture toxique en humour - Ruel-Manseau, Audrey (La Presse, 2019)
Des humoristes de la relève affirment que le milieu de l’humour reste gangréné par la culture du viol, même deux ans après le mouvement mondial #moiaussi. En mettant sur pied Pour les prochaines, les jeunes femmes souhaitent « éradiquer » les inconduites sexuelles de l’industrie, et tendent la main aux acteurs importants du monde comique afin qu’ils s’allient pour poser des actions concrètes.
Keywords: Bibliographie; Nettoyer

When Artists Fall: Honoring and Admiring the Immoral - Archer, Alfred; Matheson, Benjamin (Journal of the American Philosophical Association, 2019)
Is it appropriate to honor artists who have created great works but who have also acted immorally? In this article, after arguing that honoring involves identifying a person as someone we ought to admire, we present three moral reasons against honoring immoral artists. First, we argue that honoring can serve to condone their behavior, through the mediums of emotional prioritization and exemplar identification. Second, we argue that honoring immoral artists can generate undue epistemic credibility for the artists, which can lead to an indirect form of testimonial injustice for the artists’ victims. Third, we argue, building on the first two reasons, that honoring immoral artists can also serve to silence their victims. We end by considering how we might respond to these reasons.
Keywords: Bibliographie

Formation sur le respect en milieu du travail (2019)
Cette session d’information au sujet de milieux de travail respectueux explore les raisons derrière l’augmentation du nombre de problèmes de comportement en milieu de travail, de son impact, ainsi que de l'importance de définir les attentes en matière de comportement afin d'aider les employeurs et les organismes à gérer, contrôler et prévenir les comportements pouvant constituer du harcèlement (harcèlement sexuel, discrimination, intimidation et violence ).
Keywords: Bibliographie; Nettoyer

Tackling gender inequalities in music: a comparative study of policy responses in the UK and Sweden - de Boise, Sam (International Journal of Cultural Policy, 2019)
Cross-disciplinary research has highlighted the persistence of gender inequalities across music scenes. However, the way in which cultural policy shapes responses to gender inequalities in music has been relatively underexplored. This article draws on research from Swedish and UK contexts, supporting analysis with reference to 9 key-stakeholder interviews from both. Comparing perspectives from ‘more’ and ‘less’ gender-equal contexts, with sufficiently different cultural policy traditions, the article explores how responses to gender inequalities in music are influenced by ‘cultural democratic’ and ‘arm’s length’ approaches. It demonstrates that, as a result of these traditions, there is a comparatively more interventionist approach in Sweden at a national level, whereas the lack of central government response in the UK has encouraged more market-oriented solutions. It suggests that this ‘arm’s length’ approach necessitates different grassroots organisational strategies in order to affect change but notes that these, alongside austerity agendas, are insufficient in the long term.
Publisher: Routledge _eprint: https://doi.org/10.1080/10286632.2017.1341497
Keywords: Music policy; arm’s length; gender inequalities; interventionist; market-oriented

Harcèlement en milieu de travail dans les arts : à l'intention des employeurs - CulturalHRC (2019)
Une ressource de formation pour les employeurs et les conseils d’administration produite par Williams HR Consulting. Cette ressource de formation en gestion d’une durée de 30 minutes expliquera comment répondre aux allégations de harcèlement et sera accompagnée d’un questionnaire afin d’évaluer le degré de rétention.

Harcèlement en milieu de travail dans les arts : à l’intention des travailleurs culturels - CulturalHRC (2019)
Une ressource de formation pour les artistes/travailleurs culturels/employés produite par Williams HR Consulting. Cette ressource de formation d’une durée de 30 minutes démontre les actions à prendre lorsqu’ils sont victimes ou témoins de harcèlement et sera accompagnée d’un questionnaire afin d’évaluer le degré de rétention.

Sex Worker Resistance in the Neoliberal Creative City: An auto/ethnography - Tigchelaar, Alex (Anti-Trafficking Review, 2019)
Sex workers are subjects of intrigue in urban and creative economies. Tours of active, deteriorating, or defunct red-light districts draw thousands of tourists every year in multiple municipalities around the world. When cities celebrate significant anniversaries in their histories, local sex worker narratives are often included in arts-based public offerings. When sex workers take up urban space in their day-to-day lives, however, they are criminalised. Urban developers often view sex workers as existing serviceably only as legend. A history of sex work will add allure to an up-and-coming neighbourhood, lending purpose to its reformation into a more appropriately productive space, but the material presence of sex workers in these neighbourhoods is seen as a threat to community wellbeing and property values. This paper considers how sex workers, continuously displaced from environments they have carved out as workspaces, may use the arts to draw attention to these ongoing contradictions. It investigates how sex workers may make visible the idiosyncratic state of providing vitality to a city’s history while simultaneously being excluded from its living present. Most critically, it suggests ways in which sex workers may encourage those involved as producers and consumers of neoliberal urban revitalisation projects to connect these often fatal paradoxes to the laws that criminalise their labour.
Keywords: Bibliographie; Nettoyer

Female Brass Musicians Address Gender Parity, Gender Equity, and Sexual Harassment: A Preliminary Report on Data from the Brass Bodies Study - Schmalenberger, Sarah; Maddox, Patricia (Societies, 2019)
The Brass Bodies Study is an exploratory cross-sectional study designed to describe and understand the experience of female brass players. This report discusses selected data from close-ended and open-ended responses to questions regarding gender equity, parity, and sexual harassment within a web-based survey that launched the first phase of the study. The survey queried subjects’ physical changes to their brass playing due to various catalysts: life-cycle events; injury, illness, harassment, mental health, racism, and homophobia. The survey instrument further queried whether subjects received support about these changes and the effectiveness of support. The following report discusses survey responses to questions about gender parity and changes to brass playing due to sexual harassment. Additional qualitative data were generated from open-ended questions in the survey and were qualitatively coded and thematically presented to supplement the descriptive statistics provided. The information presented explores and defines salient items and themes of a population that is under researched with the hopes of generating hypotheses for continued research.
Number: 1 Publisher: Multidisciplinary Digital Publishing Institute
Keywords: Brass Bodies Study; Myriam; female brass players; female musicians; music workplace climate

Consentability: Consent and its Limits - Kim, Nancy S. (Cambridge University Press, 2019)

Violence in the mosh pit: assault within the Australian punk scene - Barnes, Ash; White, Rob (Current Issues in Criminal Justice, 2019)
The mosh pit is a unique crowd formation where audience members dance aggressively to engage with the music, the performers and each other. However, in this space, Australian punks may experience violations of bodily integrity. Multiple levels and types of transgression occur, as members break with mosh pit ethics by engaging in unwanted and unlawful sexual and physical violence. This case study provides an example of how group normative behaviour is confounded in liminal spaces – how transgression within such spaces undermines the supposed freedom experienced by its participants. Whilst the mosh pit is perceived to be a site governed by its own particular ethics, some defy these in word and practice. The rules of engagement are ambiguous, and offenders are able to rationalise their harms through neutralisation techniques and the diffusion of blame and responsibility. The consequence is that more often than not, offenders can use the unique physical nature of the mosh pit to execute personal vendettas and engage in intentional violence such as ‘crowd killing’ and sexual assault, with little social and legal consequence. Moreover, a certain culture of denial permeates participant responses to these issues. Throughout it all, the violence occurring has a decidedly masculine basis, reflecting overarching gender differences in interpersonal violence generally.
Publisher: Routledge _eprint: https://doi.org/10.1080/10345329.2018.1556281
Keywords: assault; cultural criminology; denial; mosh pit; punk scene

Women composers’ use of online communities of practice to build and support their careers - Hennekam, Sophie; Macarthur, Sally; Bennett, Dawn; Hope, Cat; Goh, Talisha (Personnel Review, 2019)
Purpose The purpose of this paper is to examine women composers’ use of online communities of practice (CoP) to negotiate the traditionally masculine space of music composition while operating outside its hierarchical structures. Design/methodology/approach The authors employed a mixed methods approach consisting of an online survey (n=225) followed by 27 semi-structured in-depth interviews with female composers to explore the concept and use of CoP. Content analysis was used to analyze the survey responses and interpretative phenomenological analysis was used to interpret respondents’ lived experiences as relayed in the interviews. Findings The findings reveal that the online environment can be a supportive and safe space for female composers to connect with others and find support, feedback and mentorship, increase their visibility and develop career agency through learning and knowledge acquisition. CoP emerged as an alternative approach to career development for practicing female music workers and as a tool which could circumvent some of the enduring gendered challenges. Originality/value The findings suggest that online CoP can have a positive impact on the career development and sustainability of women in male-dominated sectors such as composition.
Publisher: Emerald Publishing Limited
Keywords: Career progression; Communities of practice; Creative industries; Gender; Mixed methodologies; Myriam; Women composers; music industry

When Artists Fall: Honoring and Admiring the Immoral - Archer, Alfred; Matheson, Benjamin (Journal of the American Philosophical Association, 2019)
Is it appropriate to honor artists who have created great works but who have also acted immorally? In this article, after arguing that honoring involves identifying a person as someone we ought to admire, we present three moral reasons against honoring immoral artists. First, we argue that honoring can serve to condone their behavior, through the mediums of emotional prioritization and exemplar identification. Second, we argue that honoring immoral artists can generate undue epistemic credibility for the artists, which can lead to an indirect form of testimonial injustice for the artists’ victims. Third, we argue, building on the first two reasons, that honoring immoral artists can also serve to silence their victims. We end by considering how we might respond to these reasons.
Publisher: Cambridge University Press
Keywords: Arts; Myriam; admiration; condonation; epistemic injustice; honor; silencing

Antifeminismes et masculinismes d'hier et d'aujourd'hui - Bard, Christine; Blais, Mélissa; Dupuis-Déri, Francis (Presses universitaires de France, 2019)
Antiféminismes et masculinismes d'hier et d'aujourd'hui . Aussi ancienne que les lunes féministes, l'opposition à l'émancipation des femmes est loin de n'être que le reliquat d'un passé révolu : l'anti-féminisme contemporain reste vivace et pluriel. « Printemps des pères », « Manif pour tous », « célibataires involontaires » et mobilisations contre la « théorie du genre » : il est renouvelé par des masques séducteurs, des emprunts au discours égalitaire, par un répertoire d'action actualisé et par une nouvelle militance, dite masculiniste, dans un climat politique et social propice à son extension. Pour être compris et combattus, les antiféminismes doivent aujourd'hui être situés dans une perspective historique. Leur ancrage conservateur est souligné, mais aucune famille politique - ni aucune religion - n'est immunisée. Ils ne sont pas, non plus, le monopole des hommes. En analysant diverses expressions de l'antiféminisme depuis le XIXième siècle, les contributions à cet ouvrage démontrent la vitalité historique de ce combat et mettent en évidence ses points de contact avec l'homophobie et le racisme : l'intersectionnalité des haines. L'ensemble constitue une réponse inédite en même temps qu'un appel à la vigilance.

The Role of Rape-Supportive Attitudes, Alcohol, and Sexual Arousal in Sexual (Mis)Perception: An Experimental Study - Benbouriche, Massil; Testé, Benoit; Guay, Jean-Pierre; Lavoie, Marc E. (Journal of Sex Research, 2019)
While sexual misperception does not irrevocably lead to sexual aggression, it remains a significant risk factor. The present study investigated the effects of rape-supportive attitudes, alcohol, and sexual arousal on sexual perception. We used a 2 × 2 between-participants factorial design to randomly assign 135 men from the general population to a condition with or without alcohol (blood alcohol concentration target of .08%) and to a condition with or without sexual arousal. Participants were asked to listen to an audiotape depicting a sexual interaction between a man and woman and to indicate if and when they believed the woman was no longer interested in having sex. Results, obtained through survival analyses, indicate that the effects of rape-supportive attitudes on sexual misperception are moderated by alcohol consumption. Alcohol appears to be an important situational factor for activating men's implicit theories. Our study sheds new light on the role of knowledge structures in sexual perception: It identifies when, as well as suggesting how, rape-supportive attitudes may disturb sexual perception and ultimately lead to sexual misperception.
Keywords: Adult; Alcohol Drinking; Arousal; Attitude; Female; Humans; Male; Rape; Refusal to Participate; Sexual Behavior; Survival Analysis; Tape Recording; Young Adult

Harcèlement en milieu de travail dans les arts : à l'intention des employeurs (YouTube, 2019)
Conseil des ressources humaines du secteur culturel
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Harcèlement en milieu de travail dans les arts : à l’intention des travailleurs culturels - Conseil des ressources humaines du secteur culturel (YouTube, 2019)
Conseil des ressources humaines du secteur culturel
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Le harcèlement en milieu de travail au Québec - Conseil des ressources humaines du secteur culturel (YouTube, 2019)
Conseil des ressources humaines du secteur culturel
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Trousse à outil pour la gestion des ressources humaines : Harcèlement et violence dans le milieu de travail - Conseil des ressources humaines du secteur culturel. (2019)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Speaking in Public: What Women Say about Working in the Video Game Industry - De Castell, Suzanne; Skardzius, Karen (Television & New Media, 2019)
Since the 1990s, conversations about the dearth of women working in the video game industry have centered on three topics: (1) ways to draw more women into the field, (2) the experiences of women working in the industry, and (3) the experiences of those who once worked in the industry but left. Although there has been considerable research on the conditions and occupational identities of video game developers, less scholarly attention has been devoted to women in gameswork, the barriers/obstacles and challenges/opportunities they face, and how they talk about their experiences. This article offers a feminist approach that demonstrates how discourse focused on affect can be reread as intimately related to silences about power and how the rhetorical constraints that public speech imposes upon what can be said about “women in games” aid us in understanding what might remain unspoken, and why.
Keywords: Bibliographie; Irina; Nettoyer

Le boys club - Delvaux, Martine (Les Éditions du remue-ménage, 2019)
OCLC: 1158938839

Le boys club - Delvaux, Martine (Les Éditions du remue-ménage, 2019)
Ils sont tournés les uns vers les autres. Ils s'observent et s'écoutent. Ils s'échangent des idées, des armes, de l'argent ou des femmes. Dans cet univers clos réservé aux hommes, le pouvoir se relaie et se perpétue a̧ la façon d'une chorégraphie mortifère. Le boys club n'est pas une institution du passé. Il est bien vivant, tentaculaire: État, Église, armée, université, fraternités, firmes – et la liste s'allonge. À la manière d'une chasse à l'image, c'est dans les représentations au cinéma et à la télévision que Martine Delvaux le traque. Véritable plongée en eaux noires, ce livre nous invite á considérer l'entre-soi des hommes comme un phénomène régressif. Un dispositif à profaner, déconstruire, refuser, parce que nos vies comptent

Experiences and perceptions of gender in the Australian music industry - Fairlamb, Hannah Mary; Fileborn, Bianca (Perfect Beat, 2019)
This article reports results from an online survey (n=207) about experiences and perceptions of gender from those working in the Australian music industry. Taking a feminist approach, theory on gender and hegemonic masculinity is used to discuss power in a gendered context in this industry. Literature shows women and girls experience a range of difficulties in the music industry worldwide, such as negative assumptions about their skill levels. The small body of research on gender and the Australian music industry has discussed topics such as the forgetting of women in Australian popular music history. Results reported in this article show that women’s worst experiences most often related to sexual violence or unwanted sexual advances; and men’s most often related to money. Findings contribute to the field by providing gendered analysis of self-reported data in an under-researched industry.
Keywords: Australia; gender; music; music industry; popular music; sexual harassment

Setting the Stage for Sexual Assault: The Dynamics of Gender, Culture, Space and Sexual Violence at Live Music Events - Fileborn, B.; Wadds, P.; Barnes, A. (2019)
Setting the Stage for Sexual Assault: The Dynamics of Gender, Culture, Space and Sexual Violence at Live Music Events
Keywords: Camille

#MeToo and the politics of social change - Fileborn, Bianca; Loney-Howes, Rachel (Palgrave Macmillan, 2019)

Safety, sexual harassment and assault at Australian music festivals: final report - Fileborn, Bianca; Wadds, Phillip; Tomsen, Stephen (2019)
Keywords: Camille

Étude sur la rémunération des travailleurs culturels au sein des organismes artistiques et culturels québécois - Groupe-conseil Solertia (Groupe-conseil Solertia, 2019)

The Experiences of Women Professionals in the Film Industry in Turkey: A Gender-Based Study - G&#252, Hasan; rkan (Acta Universitatis Sapientiae, Film and Media Studies, 2019)
The article is based on 20 in-depth interviews with women professionals conducted for a more comprehensive study focusing on gender roles within the film and television industry in Turkey. This study examines the career possibilities for women, the experience of being a woman working in television and cinema, and the working environment, including work-life balance issues, experiences of discrimination and experiences of sexism. The hypothesis of this study is that film industry is male-dominated, and women have to struggle to be able to prove themselves in this industry in the 21st century in Turkey, where the position of women is made even more difficult by the gender role codes and the structure of Turkish society.
Publisher: Scientia Kiadó
Keywords: Myriam; Turkey; film industry; gender; gender role; women

The power of abuse - Harvie, Jen (The Routledge Companion to Theatre and Politics, 2019)
Following revelations about sexual abuse in theatre and other entertainment industries in autumn 2017, this chapter explores the conditions which allow or
Keywords: Bibliographie; Nettoyer; Raphaël

On peut plus rien dire: Militantisme à l'ère des réseaux sociaux - Lussier, Judith (Cardinal, 2019)
Consacrée par la sous-culture web, l’expression « Social justice warrior » désigne des militants nouveau genre qui semblent s’offusquer pour un rien et ne ratent aucune occasion de saisir leur clavier pour le clamer haut et fort. Ultra réactifs, ils usent de leur voix sur les réseaux sociaux pour s’attaquer aux discours qu’ils considèrent comme racistes, misogynes, spécistes ou encore classistes. Hypersensibles ou acharnés, héros ou bourreaux : qui se cache derrière la caricature? Qu’est-ce qui les motive, et surtout, comment leur démarche s’inscrit-elle dans un projet de société au 21e siècle?Directement concernée par l’appellation, Judith Lussier se plonge au cœur du phénomène, questionne ses limites et part à la rencontre de ces individus qui ont tellement à cœur de défendre leurs idéaux de justice sociale qu’ils finissent parfois par s’en rendre malades.

Institutional Responses to #MeToo: A Conversation - Mengesha, Weyni; Dreyer-Lude, Melanie; Clarke, Kristian; Shaw, Kathryn; Warwick, Jacqueline; Palmer, Alisa; Dubois, Frédéric (Canadian Theatre Review, 2019)
Theatre administrators, artistic directors, and heads of programs from across Canada have a conversation about how institutional policies and cultures have shifted in the wake of #MeToo. The conversation features Kristian Clarke, Executive Director of the Dancer Transition Resource Centre (DTRC); Frédéric Dubois, Director of the French Section, National Theatre School; Melanie Dreyer-Lude, Chair of the Department of Drama at the University of Alberta; Weyni Mengesha, Artistic Director of Soulpepper Theatre; Alisa Palmer, Artistic Director of the English Section, National Theatre School; Kathryn Shaw, Artistic Director of Studio 58 at Langara College; and Jacqueline Warwick, Director of the Fountain School of Performing Arts, Dalhousie University. The participants reflect on the challenges of taking stock of the impacts and effects of a cultural movement that is still unfolding and the ways in which #MeToo has changed the relationship between training institutions and the performing arts industry.
Publisher: University of Toronto Press
Keywords: #MeToo; Bibliographie; Nettoyer; Raphaël; intimacy coaching; performing arts industry; sexual harassment policy; theatre training

Creating Space for Gender Diverse Theatre - Meredith, John; Levine, Sloth; Gender Explosion Working Group (StageSource, 2019)
Keywords: Bibliographie; Nettoyer; Raphaël

Masculinity after #MeToo in Mainstream Theatre - Mignon, Eloïse; Rae, Paul (Performance Research, 2019)
Keywords: #MeToo; Arthur Miller; Bibliographie; Geoffrey Rush; King Lear; Nettoyer; Raphaël; Sarah Kane; masculinity; theatre

Code de Conduite pour les arts de la scène au Canada - Milieux de travail respectueux dans les arts (2019)
Keywords: Bibliographie; Dans le rapport; Nettoyer

Carefree or Controlled? Understanding the Night-Time Economy - Nicholls, Emily (Negotiating Femininities in the Neoliberal Night-Time Economy: Too Much of a Girl?, 2019)
The term ‘Night-Time Economy’ was coined in the late twentieth century (Shaw 2014) in town planning circles, and increasingly used into the twenty-first century to describe the expanding number of pubs, bars and clubs concentrated in city centres and targeting predominantly 18–24-year-olds (Roberts 2006: 332). But what exactly is the Night-Time Economy, and what role does it play in the lives of young women today? How has it changed as a site of leisure, and what does it mean to say that neoliberal forces have played a role in shaping it? What do we mean by the supposed ‘feminisation’ of the NTE, and what are the implications of this process for the ways that women engage with these spaces? This chapter charts the development of the NTE in the UK and the rise of the ‘24-hour city’, highlighting the ways in which neoliberal ideals have shaped both the landscape of the NTE and the types of behaviours and consumption practices that are expected within it. Such considerations are important for research that attends both to the wider social structures within the NTE and the individual specificities of the lives of young people as they participate in it. I will then explore the significance of space and place in research focusing on the NTE, situating the current study geographically and exploring Newcastle’s own NTE in more depth and detail.
Keywords: Charvis; Essex Girl; Geordie; Night-time Economy; Northern Identity

Conclusion - Nicholls, Emily (Negotiating Femininities in the Neoliberal Night-Time Economy: Too Much of a Girl?, 2019)
As has become increasingly evident throughout this book, the girls’ night out clearly offers specific and nuanced ways in which to do femininities and friendships which are not present in other types of night out, and perhaps also specific types of pressures to do femininity. Whilst the NTE is increasingly recognised as a useful avenue through which to research young people’s lives, less attention has been given to the girls’ night out as a specific type of engagement with the NTE that may illuminate nuances in the ways in which young women ‘do’ gender and femininities. This book thus marks a unique contribution within a wider body of research on young people’s drinking and clubbing. This concluding chapter will pull together the main arguments outlined throughout this book, highlighting the tensions and contradictions embedded in young women’s negotiations of femininity and the ways in which these reflect the idea that the successful embodiment of ‘girly’ and ‘girliness’ is simultaneously something that is desired yet derided.
Keywords: Drinking Practices; Girly Girl; Research Young People; Time Girls; otheringOthering

Introduction - Nicholls, Emily (Negotiating Femininities in the Neoliberal Night-Time Economy: Too Much of a Girl?, 2019)
‘Going out’ is widely recognised as a central leisure activity in the lives of many young people (Chatterton and Hollands, Urban nightscapes: Youth cultures, pleasure spaces and corporate power. Routledge, 2003; Waitt et al., ‘The guys in there just expect to be laid’: Embodied and gendered socio-spatial practices of a ‘night out’ in Wollongong, Australia. Gender, Place & Culture, 18(2), pp. 255–275, 2011), and engaging in leisure practices in the Night-Time Economy (NTE) is likely to be an important part of women’s lives in the UK. Indeed, the ‘night on the town’ is framed in many research accounts as offering important opportunities for young women to relax, socialise with friends and escape from the often mundane realities of everyday life, work and other responsibilities (Guise and Gill, ‘Binge drinking? It’s good, it’s harmless fun’: A discourse analysis of accounts of female undergraduate drinking in Scotland. Health Education Research, 22(6), pp. 895–906, 2007; Jayne et al., Emotional, embodied and affective geographies of alcohol, drinking and drunkenness. Transactions of the Institute of British Geographers, 35(4), pp. 540–554, 2010). Yet, young women’s experiences of the NTE are also clearly shaped by neoliberal and gendered expectations around consumption, body work and self-regulation. In particular, it is important to explore in more depth how—within a supposed ‘post-feminist’ context—expectations around ‘appropriately’ feminine dress and behaviour may continue to shape the experiences of young women like Nicole in contemporary leisure spaces. But what does it actually mean and look like for young women to be ‘feminine’ today? Is this something that is relevant or important to them? How are tensions around girliness and femininity lived and negotiated in practice in women’s everyday lives? And crucially, is it still more difficult for some women to adopt ‘appropriately’ feminine identities than others? This book considers these questions and explores the ways in which women’s participation in the UK NTE continues to be constrained in a supposedly post-feminist society (Harris, Jamming girl culture: Young women and consumer citizenship. In A. Harris (ed.) All about the girl: Culture, power and identity. Routledge, 2004).
Keywords: Contemporary Femininity; Contextual Expectations; Feminine Identity; Night-time Economy (NTE); Nightlife Scene

‘It’s Girl Time’: Girliness and Friendships - Nicholls, Emily (Negotiating Femininities in the Neoliberal Night-Time Economy: Too Much of a Girl?, 2019)
With what Chatterton and Hollands call the ‘ritual descent’ (2002: 95) of young women into bars and clubs every weekend, we must take seriously young women’s participation in such spaces and explore further what role participating in the NTE plays in young women’s lives. Participating in the NTE has been increasingly recognised as an important component of the lives of many young women (Hollands 1995), and the participants in my study were no exception. Set against a backdrop of conflicting debates positioning the NTE as simultaneously a site of both pleasure and regulation, it is important to understand the value engaging with the NTE has for young women and the ways in which this can offer opportunities for ‘doing’ femininities or girliness and cementing friendships within these spaces. The girls’ night out represents a discreet and distinctive mode of engagement with the NTE, yet one that has received little attention in research, despite the fact that it is likely to reveal a huge amount about the individual and collective production and negotiation of femininities and friendships in nightlife venues. This chapter provides the backdrop for the remainder of the book by exploring what the girls’ night out means to young women and the central role it can play in the negotiation and maintenance of friendships and in doing ‘girly’. Whilst previous research has depicted friendships within the NTE as potentially shallow or instrumental and consumption practices as highly individualised, this chapter highlights the ways in which going out was described as an important and valued opportunity to maintain close female friendships, spend time together and enjoy opportunities to socialise and relax. I will also introduce some of the ways in which alcohol consumption was central to the young women’s negotiations of the NTE. Drinking could take on a particular role on the girls’ night out, where alcohol could function in the maintenance and cementing of friendships and the creation of intimacy (particularly when ‘pre-drinking’ at home). Consuming certain types of alcohol could also enable ‘girliness’ to be embodied in particular ways through certain consumption choices. I argue that the ‘girling’ of drinking and clubbing is particularly significant because alcohol consumption in public spaces has traditionally been recognised as a masculine pastime, rendering drinking and femininity fundamentally incompatible. If young women are able to rupture the linkages between public drinking and masculinity, they may be able to recast women’s presence and alcohol consumption in the contemporary NTE as feminine and respectable. I also explore the ways in which getting ready for a girls’ night offered further opportunities to do girliness collectively.
Keywords: Female Friends; Girlhood; Girly Girl; Time Girls; wineWine

‘People Don’t See You if You’re a Woman and You’re Not Really Dressed Up’: Visibility and Risk - Nicholls, Emily (Negotiating Femininities in the Neoliberal Night-Time Economy: Too Much of a Girl?, 2019)
Against a backdrop of research suggesting that young women are still expected to engage in active risk management on a night out (Brooks, ‘Guys! Stop doing it!’: Young women’s adoption and rejection of safety advice when socializing in bars, pubs and clubs. British Journal of Criminology, 51(4), pp. 635–651, 2011), this chapter will explore the centrality of understanding of space and visibility to young women’s negotiations of risk and safety in mainstream bars and clubs in Newcastle’s NTE. Visibility comes into play in two distinct ways here—firstly, as in the previous chapter, participants drew on narratives of ‘fitting in’, this time to describe the types of venues that felt comfortable and safe to them. Attending a venue where they felt out of place or ‘different’ to other patrons could leave women feeling exposed, visible and vulnerable, and these spaces were positioned as risky and dangerous. Secondly, women recognised that bars and clubs are spaces where ‘everyday’ experiences of heterosexualised violence are trivialised and normalised, and they managed their dress and appearance in particular ways in order to position themselves as less visible—or even invisible—to try to avoid ‘unwanted attention’ and harassment.
Keywords: Charvis; Posh People; Sexual Abuse Rape; Unwanted Attention; Working-class College Students

‘Rowdy…? That’s the Whole Point of Going on a Night Out’: Time Out, Transgression and Control - Nicholls, Emily (Negotiating Femininities in the Neoliberal Night-Time Economy: Too Much of a Girl?, 2019)
As the previous chapter has highlighted, alcohol consumption plays an important role in the maintenance of friendships and in the individual and collective production of ‘girly’ or feminine identities in the NTE. Yet long-standing and pervasive images of alcohol consumption as a threat to femininity mean women’s negotiations of drinking continue to be fraught with tensions and ambivalences. In something of a paradox, ‘the contradictions engendered by post-feminist discourse constitute drunkenness as unfeminine, [yet] young women are enthusiastically exhorted to consume within the neoliberal culture of intoxication’ (Hutton et al. 2016: 82). In other words, to be a good, neoliberal citizen within leisure sites such as the NTE requires women to consume alcohol, yet the demands of femininity necessitate that they also show restraint. At the same time, the NTE is portrayed as a site where abandonment, hedonism and ‘rowdy’ behaviour are to an extent normalised, perhaps even encouraged, yet such behaviour ruptures traditional expectations of femininity as passive and ‘ladylike’. How do women negotiate and make sense of some of these tensions as they confront the ‘orderly disorder’ (Smith 2014: 2) of a typical night out? Is there a degree of acceptance of ‘rowdy’ or transgressive behaviour? And how does this sit alongside an expectation to be girly, as outlined in the previous chapter?
Keywords: Drinking Practices; Drunk Woman; Girly Girl; Kirsty; Transgressive Behavior

‘What Else About Her Is Fake?’: ‘Emphasised’ Femininity, Authenticity and Appearance - Nicholls, Emily (Negotiating Femininities in the Neoliberal Night-Time Economy: Too Much of a Girl?, 2019)
This chapter charts the ways in which young women’s negotiations of dress in the NTE are shaped by notions of visibility and authenticity and also by class. I explore the ways in which an exaggerated or emphasised mode of femininity is normalised to an extent within the NTE and highlight some of the pleasures and values young women found in their negotiations of femininity through dress, whether wholeheartedly embracing or ‘flashing’ femininity. Tensions and ambivalences are exposed as the participants both adopted and resisted elements of ‘girly’ and ‘tomboy’ identities. I then explore the ways in which forms of classed othering function to construct the feminine self in contrast to those who are perceived to lack the taste and resources to ‘do’ femininity appropriately and instead embody a somehow inauthentic and overdone performance of femininity. I briefly consider the intersections between hyper-feminine and ‘slutty’ dress, and finally explore how attempts by working-class young women to resignify a more excessive look as ‘glamorous’ may be mocked and judged beyond the local context.
Keywords: Essex Girl; Geordie; Girly Girl; Tomboy; clothingClothing

intersectionnalité - Office québécois de la langue française (Grand dictionnaire terminologique, 2019)
Cumul de différentes formes de domination ou de discrimination vécues par une personne, fondées notamment sur sa race, son sexe, son âge, sa religion, son orientation sexuelle, sa classe sociale ou ses capacités physiques, qui entraîne une augmentation des préjudices subis.
Keywords: Bibliographie; Nettoyer

Victim Services - ReadtheCode (2019)
Keywords: Nettoyer; À ajouter

Double Binds and Punchlines: An Examination of Women in Stand Up Comedy and Television Writers' Rooms - Sargent, Amberia (UCLA, 2019)
In this dissertation, I examine how double binds around sexuality and gender norms shape how women navigate sexual harassment and threats to their professional identities in stand up comedy and television writers’ rooms. I explain the ways the workplace dilemmas women confront are informed by race, sexuality, physical attractiveness, tenure, and relationship status.
Keywords: Sophie-Anne

Education in Theatrical Intimacy as Ethical Practice for University Theatre - Shawyer, Susanne; Shively, Kim (Journal of Dramatic Theory and Criticism, 2019)
Keywords: Bibliographie; Nettoyer; Raphaël; acting; ethics; pedagogy; theatre; theatrical intimacy

Le respect de la dignité des femmes dévoilant une agression à caractère sexuel:perspectives d'intervenantes sociales et communautaires Montréalaises - Souffrant, Kharoll-Ann (Université McGill, 2019)
Publisher: McGill University
Keywords: Bibliographie; Nettoyer

Mesures de soutien et d’inclusion des personnes trans et des personnes non binaires en milieu de travail : Guide pour les employeurs et les syndicats - Table nationale de lutte contre l'homophobie et la transphobie des réseaux de l'éducation (2019)
Keywords: Bibliographie; Nettoyer

Comment aider un·e ami·e qui a eu des comportements abusifs par le passé (et qui a changé depuis) ? - Thom, Kai Cheng (Nous faire justice : Reader sur le viol et les ripostes extra-pénales, 2019)
Keywords: Bibliographie; Dans le rapport; Nettoyer

#MeToo, Time's up, and Theories of Justice - Wexler, Lesley; Robbennolt, Jennifer K.; Murphy, Colleen (I) (University of Illinois Law Review, 2019)
Keywords: Irina

La fabrique du viol - Zaccour, Suzanne (Leméac Éditeur, 2019)

Situation des femmes dans les industries artistiques et culturelles au Canada : Examen de la recherche (Hill Strategies Research Inc, 2018)
Cet examen recense plus de 250 rapports, articles et documents de sources ontariennes ou canadiennes contenant des données sur les femmes dans six secteurs d’activités artistiques et culturelles : les arts visuels, la danse, le théâtre, la littérature, la musique et les arts médiatiques/sur écran. Une de ses principales constatations est qu’il n’existe pas d’études ayant […]

#moiaussi de l’humour : un an après ? - Paré, Christelle (Le Journal de Québec, 2018)
Le #moiaussi en humour a sonné l'alarme, chiffres à l'appui.

Men's Intrusion, Women's Embodiment: A critical analysis of street harassment - Vera-Gray, F. (Routledge, 2018)
Research on violence against women tends to focus on topics such as sexual assault and intimate partner violence, arguably to the detriment of investigating men’s violence and intrusion in women’s everyday lives. The reality and possibility of the routine intrusions women experience from men in public space – from unwanted comments, to flashing, following and frottage – are frequently unaddressed in research, as well as in theoretical and policy-based responses to violence against women. Often at their height during women’s adolescence, such practices are commonly dismissed as trivial, relatively harmless expressions of free speech too subjective to be legislated against. Based on original empirical research, this book is the first of its kind to conduct a feminist phenomenological analysis of the experience for women of men’s stranger intrusions in public spaces. It suggests that intrusion from unknown men is a fundamental factor in how women understand and enact their embodied selfhood. This book is essential reading for academics and students involved in the study of violence against women, feminist philosophy, applied sociology, feminist criminology and gender studies.

Un an depuis #moiaussi: la contestation dans les oeuvres - CÔTÉ, ÉMILIE (La Presse, 2018)
Le mouvement #moiaussi a inspiré auteurs, artistes et créateurs de toutes les disciplines artistiques. Tour d'horizon.

Musical genius and/or nasty piece of work? Dealing with violence and sexual assault in accounts of popular music’s past - Strong, Catherine; Rush, Emma (Continuum, 2018)
For many years, the mistreatment of women in particular has essentially been normalized in many parts of the music industry. In recent years, however, there has been an increase in women coming forward and telling their stories, and asking that men be held accountable for wrongdoing. This interdisciplinary (sociology and philosophy) paper pursues two key feminist questions prompted by recent developments. Firstly: How has the construction of the history of popular music legitimated the continuation of this situation? ‘Looking back’ historically and sociologically, examples are provided of the legitimation or ignoring of violence against women (VAW) in the history of popular music to date. Secondly: How should we [archivists, historians, heritage curators and popular music educators], from now on, construct the history of popular music in a way that doesn’t legitimate VAW? Turning to ‘look forward’, applied ethics frameworks are used to explore different aspects of this second question.
Keywords: Bibliographie; Nettoyer

Hard facts, soft measures: Gender, quality and inequality debates in Danish film and television in the 2010s - Redvall, Eva Novrup; Sørensen, Inge Ejbye (Journal of Scandinavian Cinema, 2018)
Abstract This article investigates discussions about gender, quality and equality in Danish film and television in the 2010s. Contrary to Sweden, where gender diversity has been part of public debate and formal screen policy since the 2000s, there was little discussion of gender in the Danish screen industry until the Danish Film Institute (DFI) began focusing on diversity as a priority area before the Film Strategy for 2015–18. The article analyses how both DFI and industry players have continuously argued against gender quotas, instead opting for soft measures such as ‘gender declarations’ and initiatives to raise awareness. One of these initiatives was a manifesto, ManusFestet, that used humour to raise questions about gender representation on-screen. The article discusses how a balance between hard facts and soft measures seems to be experienced as a constructive way forward, as long as this combination does in fact facilitate the intended change.
Publisher: Intellect
Keywords: Irina

“The Whole Feminist Taking-Your-Clothes-off Thing”: Negotiating the Critique of Gender Inequality in UK Music Industries - Bennett, Toby (IASPM Journal, 2018)
This article considers the critique of inequality, exploitation and exclusion in contemporary UK music industries, in light of the latter’s growing internal concerns over work-based gender relations. The creative sector’s persistent inequalities are at odds with its professed liberal, egalitarian, meritocratic values and attitudes. Yet, within music’s industrial production cultures, a dismissive postfeminist sensibility has come under pressure through a reflexive critical moment of popular feminist discourse, expressed in trade press critique, between 2013 and the present moment. Drawing from a study of intermediary work in UK major record labels, the article takes a pragmatist approach to documenting and theorizing this critique – alongside institutional mechanisms, like company policies and corporate PR, that respond to it – in terms of growing industrial reflexivity. Tensions over the representation of work, the nature of inequality, intergenerational and epistemic injustice emerge as key themes, with implications for critical research on popular music industries.
Number: 1
Keywords: Industrial Reflexivity; Inequalities; KEYWORDS: Creative labour; Major record labels; Post-feminism.

Écrire le viol (La Presse+, 2018)
Le sujet est délicat. Tellement que plusieurs personnes contactées ont refusé de se prononcer sur cette nouvelle prise de conscience qui découle des mouvements #moiaussi et #agressionnondénoncée. Les romanciers doivent-ils s’autocensurer pour respecter une nou
Section: ARTS

Comment écrire le viol ? - Clément, Éric (La Presse+, 2018)
Le sujet est délicat. Tellement que plusieurs personnes contactées ont refusé de se prononcer sur cette nouvelle prise de conscience qui découle des mouvements #moiaussi et #agressionnondénoncée. Les romanciers doivent-ils s’autocensurer pour respecter une nou
Keywords: Bibliographie; Nettoyer

Représentation du viol en littérature: pour dire quoi? (Le Devoir, 2018)
La représentation gratuite du viol n’est pas sans effet chez les lectrices.

Comment parler des violences faites aux femmes en littérature? - Caillou, Annabelle (Le Devoir, 2018)
Trois spécialistes se penchent sur le sujet. Analyse.
Keywords: Bibliographie; Nettoyer

Une nouvelle décrivant un viol entraîne la démission de la directrice de la revue «XYZ» - Caillou, Annabelle (Le Devoir, 2018)
Vanessa Courville a claqué la porte de la revue consacrée à la nouvelle littéraire.
Keywords: Bibliographie; Nettoyer

Orchestres symphoniques: une parité favorisée par un processus à l'aveugle - Larochelle, Samuel (La Presse, 2018)
Femmes et hommes côte à côte dans les orchestres symphonique d'ici. La question de parité est souvent lié au processus de sélection à l'aveugle des musiciens, une façon de faire qui permet de mettre de l'avant le talent, et ce, peu importe le sexe des artistes.
Keywords: Bibliographie; Nettoyer

Facing Sexual Harassment and Abuse in the Feminizing Museum - trivedi, nikhil; Wittman, Aletheia (Journal of Museum Education, 2018)
Despite the growing number of women in museums, the undervaluing of educational work traditionally associated with women, and labor largely done by women today, persists. This begs the question: in what other ways are women and femmes working in museums undermined despite their growing presence as workers and the emerging centrality of the educational role of museums? In society more broadly, we see how undervaluing women and their labor leads to a spectrum of treatment that can be considered violent. In this spectrum, we include pay and benefit disparities, disempowerment, and marginalization through sexist, homophobic, and transphobic comments and objectification, harassment, threats, verbal, physical, emotional, and financial abuse, and at the far end of the spectrum sexual assault and murder. In this article, we discuss data collected through a survey conducted about incidences of sexual abuse and harassment experienced by museum workers. We explore the results of the survey in relation to the gender-based division of labor and skills among the museum workforce. We look to the responses to this survey as a gauge of how much power women and gender non-conforming people have in their daily work lives in museums and propose actions that could increase empowerment and support.
Keywords: Bibliographie; Myriam; Nettoyer; Sexual violence; feminization; gender equity; labor; museum education; museum workers

'Shocking' level of sexual harassment at music festivals (BBC News, 2018)
Up to 43% of women under 40, who have been to a music festival, say they have faced unwanted sexual behaviour.

Le #metoo de Coeur de pirate - Cassivi, Marc (La Presse, 2018)
Béatrice Martin, alias Coeur de pirate, fera paraître vendredi son quatrième album, En cas de tempête, ce jardin sera fermé, un hommage à Paris qui coïncide avec ses 10 ans de carrière. Une très belle collection de textes sombres et poétiques, sur des musiques lumineuses et entraînantes, où l'auteure-compositrice-interprète évoque des épisodes douloureux de son passé.

Post Weinstein: gendered power and harassment in the media industries - Cobb, Shelley; Horeck, Tanya (Feminist Media Studies, 2018)
Keywords: #MeToo; Bibliographie; Irina; Nettoyer

What sexual harassment in Zentropa tells us about cultural policy post-Weinstein - Sorensen, Inge (Feminist Media Studies, 2018)
Publisher: Routledge _eprint: https://doi.org/10.1080/14680777.2018.1456165
Keywords: Irina

Les humoristes font leur part pour #MoiAussi - Gendron-Martin, Raphaël (Le Journal de Montréal, 2018)
«On aurait pu avoir 40 humoristes dans le spectacle», lance le coanimateur de la soirée, Patrick Groulx.

The music business’s gender pay gap is embarrassing and uncomfortable. It’s time for change. (Music Business Worldwide, 2018)
MBW Contributing Editor, Rhian Jones, gives her take on the news…

900 000 $ pour contrer les agressions sexuelles et le harcèlement dans le milieu culturel québécois - Ministère de la Culture et des Communications (Gouvernement du Québec, 2018)
Keywords: Bibliographie; Nettoyer

A Dance with Many Secrets: The Experience of Emotional Harm from the Perspective of Past Professional Female Ballet Dancers in Canada - Moola, Fiona; Krahn, Alixandra (Journal of Aggression, Maltreatment & Trauma, 2018)
Originating in the Italian and French courts, ballet is an age-old art that fuses aesthetics and athleticism (Wulff, 2008). Despite changing times, ballet masters and mistresses tenaciously hold on to a sense of deep traditionalism. However, some scholars suggest that unwavering devotion to the art may conceal troubled embodied relations and oppressive practices (Gvion, 2008). In this study, we drew on the phenomenological research tradition in an effort to further examine the power relations that play out on the body in the world of Canadian professional ballet (Papaefstathiou, Rhind, & Brakenridge, 2013). Twenty past professional female ballet dancers from across Canada participated in this study. Our dedicated dancers were relentless. They sacrificed body and mind in the pursuit of excellence in a broader cultural context that expected nothing less. The dancers normalized harmful emotional experiences, inappropriate sexual transgressions, and chronic injury (Gvion, 2008). They also described experiences of neglect—and feeling replaceable—after the onset of injury. We have attempted to theorize our findings within the context of embodiment literature and the work of gender theorists. Emboldened by our dancers’ voices, we have shed light—and broken secrets—regarding some of the harmful practices that still characterize professional ballet in Canada. We hope that our work might further continue efforts to democratize power imbalances in professional ballet and ultimately enhance holistic dancer development and health.
Publisher: Routledge _eprint: https://doi.org/10.1080/10926771.2017.1410747

“The Destruction of a Legacy”: Agenda Setting and the Bill Cosby Sexual Assault Allegations - Terán, Larissa; Emmers-Sommer, Tara M. (Sexuality & Culture, 2018)
Utilizing agenda setting theory, this study investigates the Bill Cosby sexual assault allegation scandal and how the scandal is framed by the media. In order to examine if and how varied networks reported differently on the Cosby scandal, sixty articles from three, distinct networks (CNN, FOX News, E!) were analyzed and coded under seven different categories. Results demonstrate a significant difference among the analyzed networks and media frames most reported in the sample for this study. Although all networks address Cosby’s rise and fall of an American hero, agendas set and story frames presented varied. Specifically, CNN highlighted victims’/survivors’ powerful voice whereas E! and FOX News highlighted Cosby’s support from the black community, celebrities and co-stars. Additional results, discussion and future directions follow.
Keywords: Agenda setting theory; Bill Cosby; Mediated communication; Scandal; Sexual assault; Sophie-Anne

Danse #WeToo - Ferron, Geneviève C. (Regroupement québécois de la danse, 2018)
// English version Depuis l’émergence du mouvement #metoo en octobre dernier, plusieurs femmes artistes du Québec ont pris la parole pour dénoncer le harcèlement, l’intimidation et les abus dont elles ont été victimes ou témoins dans le cadre de leur […]
Keywords: Bibliographie; Nettoyer

Danse #WeToo - Pantalacci, Sandrine (Regroupement québécois de la danse, 2018)
// English version Depuis l’émergence du mouvement #metoo en octobre dernier, plusieurs femmes artistes du Québec ont pris la parole pour dénoncer le harcèlement, l’intimidation et les abus dont elles ont été victimes ou témoins dans le cadre de leur […]

Winnipeg comedy club bans discrimination, hatefulness, harassment | CBC News - Gibson, Shane (CBC, 2018)
Wee Johnny’s comedy room posted a sign this week warning that anyone violating a new anti-harassment policy — which bans “sexism, racism, homophobia, transphobia, physical intimidation or any other form of abusive behaviour” — may be asked to leave the club.

L'Université de Montréal fait son mea culpa (La Presse+, 2018)
L’Université de Montréal reconnaît avoir toléré, faute de balises adéquates, des comportements « inacceptables » du professeur Jean Larose, parti à la retraite en 2011 à la suite d’une plainte pour attouchements et harcèlement sexuels qui a été rejetée. Un cas
Section: ACTUALITÉS

EDM and Ecstasy: the lived experiences of electronic dance music festival attendees - Little, Noah; Burger, Birgitta; Croucher, Stephen M. (Journal of New Music Research, 2018)
Attendance at large-scale music festivals has captivated a global interest in these spectacular experiences, yet little is known about the lasting benefits and personal changes individuals incur following this event. This study aims to provide a comprehensive exploration of the lived experiences of individuals who attended a multi-day electronic dance music festival. The present study was primarily interested in the perceived beneficial changes within the individual, following their festival experience. We investigated if first-time festival attendees perceived changes differed to those of returning individuals. Semi-structured qualitative interviews were used to collect data from 12 individuals who attended the 2015 Electronic Daisy Carnival in Las Vegas. Six participants were first-time attendees while the remaining six were individuals returning to the festival. The data was analysed using Thematic Analysis. Within the data emerged the following central themes: (1) escape, (2) communitas, and (3) self-reported changes; there were 10 subthemes. These findings add to the existing body of music festival literature, further contextualizing how music festivals are both experienced, and reflected upon by individuals. Further, this study highlights the potential lasting changes individuals’ experience from attending electronic dance music festivals.
Publisher: Routledge _eprint: https://doi.org/10.1080/09298215.2017.1358286
Keywords: Music festival; electronic dance music; music; social acceptance; social cohesion

“Essential—Passion for Music”: Affirming, Critiquing, and Practising Passionate Work in Creative Industries - Bennett, Toby (The Palgrave Handbook of Creativity at Work, 2018)
This chapter considers “passion” as an enthusiastic orientation to work within creative worlds: work motivated by intense attachments to the products of work and their conditions of production. Drawing on Luc Boltanski’s pragmatic sociology of critique and justification, the chapter argues that the passionate lens most usefully trains our sights on normative questions: not what or how—but why such work is undertaken. Embedded in research on cultural and creative industries, the contemporary recorded music sector is presented as a “passionate” industry in transformation. Interviews with workers, who both criticize and defend their industry, act as a springboard to explore three possible interpretive approaches: affirmative, critical, and pragmatic. Theoretical flexibility is needed to keep “passion” open to future inquiry—particularly regarding inequalities in creative work.

Représentation du viol en littérature: pour dire quoi? - Boisclair, Isabelle (Le Devoir, 2018)
Keywords: Bibliographie; Nettoyer

Sexisme en danse : le mur du silence s’effrite au Québec - Carpentier, Mélanie (Jeu : revue de théâtre, 2018)
Un article de la revue Jeu, diffusée par la plateforme Érudit.
Publisher: Cahiers de théâtre Jeu inc.
Keywords: Bibliographie; Nettoyer

Charte égalité Hommes-Femmes - Centre national des arts du cirque (2018)
Keywords: Sophie-Anne

The Right of One's Own Image in the Recent Cases of Sexual Harassment in Film Industry: Applying the European Theory of Concentric Circles to Celebrities (In Particular, Women) - Corredoira, Loreto (Journal of Information Policy, 2018)
Keywords: Irina

Politique visant à prévenir et à combattre les violences à caractère sexuel - École nationale de cirque - Montréal (2018)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer; Sophie-Anne

Université de Montréal: briser l'omerta - Elkouri, Rima (La Presse, 2018)
Keywords: Bibliographie; Nettoyer

Intégrer les personnes trans en milieu de travail - Fondation émergence; Aide aux Trans du Québec (ATQ) (2018)
Keywords: Bibliographie; Nettoyer

Sexual Harassment and Violence at Music Concerts and Festivals - Heen, Miliaikeala Sj.; Lieberman, Joel D. (Center for Crime and Justice Policy, 2018)
Publisher: 6876
Keywords: Bibliographie; Nettoyer

Code de conduite - Industries créatrices du Canada (lirelecode.ca, 2018)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

The Bystander Moment - Jeremy Earp (Media Education Foundation, 2018)
Keywords: Coffre à outils; À ajouter

"I Didn't Want To Be 'That Girl'": The Social Risks of Labeling, Telling, and Reporting Sexual Assault - Khan, Shamus; Hirsch, Jennifer; Wamboldt, Alexander; Mellins, Claude (Sociological Science, 2018)
This article deploys ethnographic data to explain why some students do not label experiences as sexual assault or report those experiences. Using ideas of social risks and productive ambiguities, it argues that not labeling or reporting assault can help students (1) sustain their current identities and allow for several future ones, (2) retain their social relationships and group afﬁliations while maintaining the possibility of developing a wider range of future ones, or (3) avoid derailing their current or future goals within the higher educational setting, or what we call “college projects.” Conceptually, this work advances two areas of sociological research. First, it expands the framework of social risks, or culturally speciﬁc rationales for seemingly illogical behavior, by highlighting the interpersonal and institutional dimensions of such risks. Second, it urges researchers to be more attentive to contexts in which categorical ambiguity or denial is socially productive and to take categorical avoidance seriously as a subject of inquiry. Substantively, this work advances knowledge of why underreporting of campus sexual assault occurs, with implications for institutional policies to support students who have experienced unwanted nonconsensual sex regardless of how those students may label what happened.

Modèle de politique pour la création d'un milieu de travail sain, respectueux et exempt de discrimination, de harcèlement et de violence - Labine, Lise; Lorquet, Me Sébastien (L’Association des théâtres francophones du Canada, 2018)
L’Association des théâtres francophones du Canada a développé ce modèle de politique pour ses compagnies membres avec l’appui de Théâtre Action.
Keywords: Bibliographie; Nettoyer

Facing (and Fixing) the Problem of Sexual Harassment in Theatre - Lehman, Stefanie Maiya; Morris, Celestine (Southern Theatre, 2018)
Keywords: Bibliographie; Nettoyer; Raphaël

Examining the Embodied Learning Experiences about Gender in Gay and Bisexual Male Actors - McCadden, Ted; Wright, Robin Redmon (2018)
Keywords: Bibliographie; Nettoyer; Raphaël

Navigating the Margins between Consent and Dissent: Mechanisms of Creative Control and Rock Music in Late Socialist Romania - Mogoș, Petrică; Berkers, Pauwke (East European Politics and Societies: and Cultures, 2018)

Enquête sur le portrait sociodémographique et l’égalité homme-femme chez les créatrices et créateurs d’humour au Québec – Sommaire 2018-2: Données sur la perception de l’égalité entre les femmes et les hommes - Paré, Christelle; Brouard, François (Groupe de recherche sur l’industrie de l’humour (GRIH), SCSE/CSES, Sprott Centre for Social Enterprises / Centre Sprott pour les entreprises sociales (SCSE/CSES), Université Carleton, 2018)
Keywords: Bibliographie; Humour; Nettoyer; Sophie-Anne; Types de VACS

Bar Training for Active Bystanders: Evaluation of a Community-Based Bystander Intervention Program - Powers, Ráchael A.; Leili, Jennifer (Violence Against Women, 2018)
Bystander intervention programs are proliferating on college campuses and are slowly gaining momentum as sexual violence prevention programs suitable for the larger community. In particular, bystander intervention programs aimed at bar staff have been developed in a number of locations. This study entails the exploratory evaluation of a community-based bystander program for bar staff. Using a pre–posttest design, this study suggests that evidence surrounding the effectiveness of this program is promising as it decreases rape myths, decreases barriers to intervention, and increases bartenders willingness to intervene. Future research and policy implications are discussed.
Keywords: Camille

Un enseignant de l'École nationale de cirque accusé de crimes sexuels - Radio-Canada (Radio-Canada, 2018)
L'entraîneur Marcelo Berti Marques fait face à quatre chefs d'accusation, entre autres pour avoir envoyé une photo de ses organes génitaux à un de ses anciens élèves de l'École nationale de cirque, à Montréal. Sa présumée victime est soulagée, mais craint qu'il ait fait d'autres victimes.
Keywords: Bibliographie; Nettoyer

The Morality of Musical Men: From Victorian Propriety to the Era of #MeToo - Shaver-Gleason, Linda (2018)
Keywords: Bibliographie; Nettoyer

Reconceptualizing Sexual Harassment, Again Collection: #MeToo and the Future of Sexual Harassment Law - Shultz, Vicki (Yale Law Journal Forum, 2018)
Keywords: Irina

Encouraging Safer and More Supportive Working Practices in Theatre - Society of London Theatre; UK Theatre (2018)
Keywords: Bibliographie; Nettoyer; Raphaël

Performing Arts Training in the Age of #MeToo - Spencer, Jennifer (Voice and Speech Review, 2018)
Keywords: Bibliographie; Nettoyer; Raphaël

Line Drawn Summit and Survey Report - Stone, Meg (Impact, 2018)
Keywords: Bibliographie; Nettoyer; Raphaël

Harassment and bullying in the theatre industry: a report - The Stage (The Stage, 2018)
Keywords: Bibliographie; Nettoyer; Raphaël

The Whole Feminist Taking-Your-Clothes-off Thing”: Negotiating the Critique of Gender Inequality in UK Music Industries - Toby, Bennett (Gender Politics in the Music Industry, 2018)
This article considers the critique of inequality, exploitation and exclusion in contemporary UK music industries, in light of the latter’s growing internal concerns over work-based gender relations. The creative sector’s persistent inequalities are at odds with its professed liberal, egalitarian, meritocratic values and attitudes. Yet, within music’s industrial production cultures, a dismissive postfeminist sensibility has come under pressure through a reflexive critical moment of popular feminist discourse, expressed in trade press critique, between 2013 and the present moment. Drawing from a study of intermediary work in UK major record labels, the article takes a pragmatist approach to documenting and theorizing this critique – alongside institutional mechanisms, like company policies and corporate PR, that respond to it – in terms of growing industrial reflexivity. Tensions over the representation of work, the nature of inequality, intergenerational and epistemic injustice emerge as key themes, with implications for critical research on popular music industries.

L’ordinaire de la violence. Un cas d’atteinte sexuelle sur mineure en milieu artistique - Trachman, Mathieu (Travail, genre et sociétés, 2018)
L’ordinaire est un thème souvent mobilisé dans les études sur les violences de genre. À partir d’un cas d’atteinte sexuelle sur mineure, cet article a pour objectif d’en préciser les enjeux. Il montre en premier lieu que la notion d’ordinaire, qui signifie souvent ce qui est commun à toutes les femmes, gagne à voir son périmètre précisé : dans le cas analysé, le travail artistique, sa dimension vocationnelle, la personnalisation des relations entre professeur et étudiante, les coûts d’entrée dans le métier pour les femmes sont des éléments déterminants. Dans les études féministes, l’ordinaire désigne également les faits de violence qui caractérisent la vie quotidienne des femmes. En distinguant faits, situation et qualification, l’article montre que la qualification de violence implique un sentiment d’anormalité et une réflexivité largement absents dans les situations de violence de genre. Ce hiatus explique l’incertitude souvent inhérente à la qualification de violence et le caractère rétrospectivement énigmatique des situations de violence. L’ordinaire de la violence désigne ainsi moins une évidence occultée qu’un registre de l’expérience où les abus et les agressions sont intégrés dans le cours des choses et normalisés par les protagonistes.
Place: Paris Publisher: La Découverte

Gender in the Music Industry: Rock, Discourse and Girl Power - Leonard, Marion (Routledge, 2017)
Why, despite the number of high profile female rock musicians, does rock continue to be understood as masculine? Why is rock generally assumed to be created and performed by men? Marion Leonard explores different representations of masculinity offered by, and performed through, rock music, and examines how female rock performers negotiate this gendering of rock as masculine. A major concern of the book is not specifically with men or with women performing rock, but with how notions of gender affect the everyday experiences of all rock musicians within the context of the music industry. Leonard addresses core issues relating to gender, rock and the music industry through a case study of 'female-centred' bands from the UK and US performing so called 'indie rock' from the 1990s to the present day. Using original interview material with both amateur and internationally renowned musicians, the book further addresses the fact that the voices of musicians have often been absent from music industry studies. Leonard's central aim is to progress from feminist scholarship that has documented and explored the experience of female musicians, to presenting an analytic discussion of gender and the music industry. In this way, the book engages directly with a number of under-researched areas: the impact of gender on the everyday life of performing musicians; gendered attitudes in music journalism, promotion and production; the responses and strategies developed by female performers; the feminist network riot grrrl and the succession of international festivals it inspired under the name of Ladyfest.

Rape and abuse: The music industry's dark side exposed (BBC News, 2017)
"Dangerous men" at the top of the industry are abusing their power, the BBC has been told.

Dick pics on blast: A woman’s resistance to online sexual harassment using humour, art and Instagram - Vitis, Laura; Gilmour, Fairleigh (Crime, Media, Culture, 2017)
This article brings to attention and explores women?s use of non-traditional forms of resistance to online sexual harassment. In this piece we use Anna Gensler?s Instagram art project Instagranniepants to examine how women are appropriating the language and practices of the cyber realm to expose online sexual harassment and to engender a creative resistance which is critical, comedic and entertaining. Drawing from interdisciplinary literature on witnessing, satire and shaming, we explore the techniques Gensler uses to not only document harassment but also resist, engage and punish those who seek to perpetrate it. This article problematises the stereotype of women as passive victims of online public spaces, and is critical of popular discourses that portray online spaces as exclusively risky and that position women as the natural victims of online violence. It concludes that a more nuanced account of women?s negotiation of online spaces is necessary, particularly as an overarching narrative of risk and victimisation undermines the liberatory potential of the online realm.
Publisher: SAGE Publications
Keywords: Myriam; Résistance aux VACS

Not So Funny Business: Sexual Harassment in Stand-Up Comedy - Hansen, Briana (Workandmoney, 2017)
Up-and-coming Los Angeles comedian reflects on her experience of assault among some of the funniest people on the planet
Keywords: Sophie-Anne

ReadTheCode.ca - Canadian Creative Industries (2017)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer; Sophie-Anne

2192 women in the Swedish music industry behind appeal against sexism (Dagens Nyheter, 2017)
Sexual assault. Rude and outspoken sexism.

L'Union des artistes dépose des griefs pour harcèlement - Radio-Canada (Radio-Canada, 2017)
Après une vague de dénonciations de gestes à caractère sexuel dans le milieu artistique, l'Union des artistes (UDA) annonce avoir déposé des griefs pour harcèlement.
Keywords: Bibliographie; Nettoyer

Forty-Seven DJs, Four Women: Meritocracy, Talent, and Postfeminist Politics - Gadir, Tami (Dancecult, 2017)
In 2016, only four of forty-seven DJs booked for Musikkfest, a festival in Oslo, Norway, were women. Following this, a local DJ published an objection to this imbalance in a local arts and entertainment magazine. Her editorial provoked booking agents to defend their position on the grounds that they prioritise skill and talent when booking DJs, and by implication, that they do not prioritise equality. The booking agents’ responses, on social media and in interviews I conducted, highlight their perpetuation of a status quo in dance music cultures where men disproportionately dominate the role of DJing. Labour laws do not align with this cultural attitude: gender equality legislation in Norway’s recent history contrasts the postfeminist attitudes expressed by dance music’s cultural intermediaries such as DJs and booking agents. The Musikkfest case ultimately shows that gender politics in dance music cultures do not necessarily correspond to dance music’s historical associations with egalitarianism.

Un nouveau festival d'humour pour rire encore un peu, beaucoup, ensemble - Baillargeon, Stéphane (Le Devoir, 2017)
Un regroupement d’humoristes comprenant plusieurs têtes d’affiche du Québec crée le Festival du rire de Montréal. La première mouture du nouvel événement prendra l’affiche à l’été 2018, promettent les artistes.

Justice 2.0: Street harassment victims’ use of social media and online activism as sites of informal justice - Fileborn, Bianca (The British Journal of Criminology, 2017)
Emerging scholarship has considered the potential for online spaces to function as sites of informal justice. To date, there has been little consideration of the experiences of individuals who seek justice online, and the extent to which victims’ justice needs can be met online. Drawing on the findings of a mixed-methods research project with street harassment victims in Melbourne, Australia, I consider participants’ reasons for, and experiences of, disclosing their encounters of street harassment online. I examine the extent to which these ‘map on to’ a selection of victim’s justice needs. While it is evident that online spaces can function as sites of justice, it is vital to ask for whom and in which contexts justice can be achieved online.

Léa Clermont-Dion accuse Michel Venne de l’avoir agressée - Bussières, Ian; Piedboeuf, Guillaume (Le Soleil, 2017)
L’écrivaine et militante Léa Clermont-Dion, qui avait révélé en 2014 avoir été agressée sexuellement à l’âge de 17 ans, a déposé une plainte à la police contre le fondateur de l’Institut du Nouveau Monde, Michel Venne. Des allégations d’agression sexuelle que nie ce dernier.
Keywords: Bibliographie; Nettoyer

Michel Brûlé visé par une plainte d'agression sexuelle à Québec - Piedboeuf, Guillaume (La Tribune, 2017)
Une écrivaine de la Rive-Sud de Québec accuse l’éditeur Michel Brûlé de l’avoir agressée sexuellement à sa résidence du Vieux-Québec, en mars 2014, alors qu’elle venait lui proposer un manuscrit. Jill Côté a porté plainte à la police de Québec, vendredi, pour un incident dont M. Brûlé nie l’existence.
Keywords: Bibliographie; Nettoyer

Le patron des Éditions des Intouchables Michel Brûlé à son tour visé par des allégations d’inconduites sexuelles - Lévesque, Ève (Le Journal de Montréal, 2017)
Sept ex-employées se vident le cœur.
Keywords: Bibliographie; Nettoyer

Allégations de nature sexuelle: Gilbert Rozon visé par neuf femmes - Pineda, Améli (Le Devoir, 2017)
Neuf femmes racontent au «Devoir» ainsi qu’au 98,5 FM avoir été victimes de harcèlement et d’agressions sexuelles de la part du fondateur de Juste pour rire, Gilbert Rozon, et ce, dans la foulée du mouvement #MeToo. Certaines d'entre elles étaient même mineures au moment des incidents rapportés. Et pendant des années, elles ont cru être seules.
Keywords: Bibliographie; Nettoyer

Allégations de nature sexuelle: Gilbert Rozon visé par neuf femmes - Pineda, Améli (Le Devoir, 2017)
Neuf femmes racontent au «Devoir» ainsi qu’au 98,5 FM avoir été victimes de harcèlement et d’agressions sexuelles de la part du fondateur de Juste pour rire, Gilbert Rozon, et ce, dans la foulée du mouvement #MeToo. Certaines d'entre elles étaient même mineures au moment des incidents rapportés. Et pendant des années, elles ont cru être seules.

Inconduites sexuelles reprochées à Éric Salvail - Gagnon, Katia; Vallet, Stéphanie (La Presse, 2017)
Avances sexuelles en string, parties intimes exhibées ou empoignées, tentatives de séduction insistantes dans des salles de montage: 11 personnes ont raconté à La Presse avoir subi des inconduites, ou en avoir été témoins, de la part du producteur et animateur Éric Salvail, la plupart du temps dans un contexte professionnel.
Keywords: Bibliographie; Nettoyer

When Women Do Not Want It: Young Female Bargoers’ Experiences With and Responses to Sexual Harassment in Social Drinking Contexts - Graham, Kathryn; Bernards, Sharon; Abbey, Antonia; Dumas, Tara M.; Wells, Samantha (Violence Against Women, 2017)
Women frequently experience unwanted sexual touching and persistent advances at bars and parties. This study explored women?s responses to these unwanted experiences through online surveys completed by 153 female bargoers (aged 19-29) randomly recruited from a bar district. More than 75% had experienced sexual touching or persistence (46% both). Most women used multiple deterrent strategies, including evasion, facial expressions, direct refusals, aggression, friends? help, and leaving the premises. Women experienced negative feelings (disrespected, violated, disgusted, angry, embarrassed), especially from incidents involving touching. Cultural change is needed to reduce substantial negative impacts of sexual harassment on women in drinking and other settings.
Publisher: SAGE Publications Inc

Gender, Subjectivity, and Cultural Work: The Classical Music Profession - Scharff, Christina (Routledge, 2017)
What is it like to work as a classical musician today? How can we explain ongoing gender, racial, and class inequalities in the classical music profession? What happens when musicians become entrepreneurial and think of themselves as a product that needs to be sold and marketed? Gender, Subjectivity, and Cultural Work explores these and other questions by drawing on innovative, empirical research on the working lives of classical musicians in Germany and the UK. Indeed, Scharff examines a range of timely issues such as the gender, racial, and class inequalities that characterise the cultural and creative industries; the ways in which entrepreneurialism – as an ethos to work on and improve the self – is lived out; and the subjective experiences of precarious work in so-called ‘creative cities’. Thus, this book not only adds to our understanding of the working lives of artists and creatives, but also makes broader contributions by exploring how precarity, neoliberalism, and inequalities shape subjective experiences. Contributing to a range of contemporary debates around cultural work, Gender, Subjectivity, and Cultural Work will be of interest to scholars and students in the fields of Sociology, Gender and Cultural Studies.
Google-Books-ID: CHE3DwAAQBAJ
Keywords: Music; Myriam; Social Science / General; Social Science / Sociology / General

Architects singer calls out man who sexually assaulted a fan: 'Not at my f***ing show' (The Independent, 2017)
Singer paused the show after witnessing the incident from the stage
Section: Culture

Swedish music festival to go 'women-only' following string of sexual assaults - White, Adam (The Telegraph, 2017)
Sweden's biggest music festival will be replaced next year by a women-only alternative after reports of a series of rapes and sexual assaults at this year's event.
Keywords: Crime; Culture; Music; Skepta; Standard; Sweden

Data and responsibility: Towards a feminist methodology for producing historical data on women in the contemporary UK film industry - Cobb, Shelley; Wreyford, Natalie (Feminist Media Histories, 2017)
This paper addresses how feminist interrogations of research methods and knowledge claims have an important role to play in the collection and dispersion of quantitative data. Taking the contemporary film industry as a historical formation, and seeking to identify and understand patterns of continued gendered inequality, we consider the methodological and ethical dilemmas we have experienced as feminist researchers gathering and presenting quantitative data on the numbers of women working in the UK film industry between 2003 and 2015. We argue that data plays a paradoxical role in creating a sense of women’s absence and arrive at a set of guiding principles for feminist quantitative research in film histories.
Number: 3

Des musiciennes unies contre le sexisme - Lauzon, Véronique (La Presse, 2017)
Cent trente-cinq femmes issues du milieu musical ont décidé de dénoncer le sexisme et les injustices qu'elles subissent régulièrement au travail.
Keywords: Bibliographie; Nettoyer

Code of Silence (The Dance Current, 2017)
Fifteen years ago, Lisa, a dance conservatory student, became pregnant. She was told in no uncertain terms by her school’s directors that abortion was recommended, and that she wouldn’t be allowed to continue attending the conservatory otherwise. It was made clear to her that the fact that her pregnancy would be in its seventh month at the time of graduation...

Indian women journalists' responses to sexism and sexual harassment - Chadha, Kalyani; Steiner, Linda; Guha, Pallavi (International Communication Research Journal, 2017)
Gale Academic OneFile includes Indian women journalists' responses to sexism and by Kalyani Chadha, Linda Steiner, and Pall. Click to explore.
Publisher: International Communication Division (ICD), of AEJMC
Keywords: Myriam; journalism

L'écrivain jeunesse Maxime Roussy en prison pour 5 ans - Nguyen, Michael (Le Journal de Montréal, 2017)
Pendant cinq ans, de 2006 à 2011, Roussy avait profité d’une jeune lectrice pour assouvir ses fantasmes sadomasochistes.
Keywords: Bibliographie; Nettoyer

The deterrent effects of Australian street-level drug law enforcement on illicit drug offending at outdoor music festivals - Hughes, Caitlin Elizabeth; Moxham-Hall, Vivienne; Ritter, Alison; Weatherburn, Don; MacCoun, Robert (International Journal of Drug Policy, 2017)
Background Australian and international street-level drug law enforcement deploy many strategies in efforts to prevent or deter illicit drug offending. Limited evidence of deterrence exists. This study assessed the likely impacts of four Australian policing strategies on the incidence and nature of drug use and supply at a common policing target: outdoor music festivals. Methods A purpose-built national online survey (the Drug Policing Survey) was constructed using five hypothetical experimental vignettes that took into account four policing strategies (High Visibility Policing, Riot Policing, Collaborative Policing, and policing with Drug Detection Dogs) and a counter-factual (no police presence). The survey was administered in late 2015 to 2115 people who regularly attend festivals. Participants were block-randomised to receive two vignettes and asked under each whether they would use, possess, purchase, give or sell illicit drugs. Results Compared to ‘no police presence’, any police presence led to a 4.6% point reduction in engagement in overall illicit drug offending: reducing in particular willingness to possess or carry drugs into a festival. However, it had minimal or counterproductive impacts on purchasing and supply. For example, given police presence, purchasing of drugs increased significantly within festival grounds. Offending impacts varied between the four policing strategies: Drug Detection Dogs most reduced drug possession but High Visibility Policing most reduced overall drug offending including supply. Multivariate logistic regression showed police presence was not the most significant predictor of offending decisions at festivals. ConclusionConclusion The findings suggest that street-level policing may deter some forms of drug offending at music festivals, but that most impacts will be small. Moreover, it may encourage some perverse impacts such as drug consumers opting to buy drugs within festival grounds rather than carry in their own. We use our findings to highlight trade-offs between the goals of public health promotion and crime control in street-level enforcement.
Keywords: Deterrence; Drug law enforcement; Supply; Use

Rape culture, lad culture and everyday sexism: researching, conceptualizing and politicizing new mediations of gender and sexual violence - Phipps, Alison; Ringrose, Jessica; Renold, Emma; Jackson, Carolyn (Journal of Gender Studies, 2017)
Introduction to Special Issue of Journal of Gender Studies entitled Rape culture, lad culture and everyday sexism: Researching, conceptualizing and politicizing new mediations of gender and sexual violence.

Skipping a beat: Assessing the state of gender equality in the Australian music industry - Cooper, Rae; Coles, Amanda; Hanna-Osborne, Sally (2017)
This report demonstrates that male advantage is a pervasive feature of the Australian music industry. Using publicly available published data the report interrogates the industry dynamics that have produced a contemporary music scene in which radio playlists, festival line-ups, industry awards, peak bodies and major industry boards are dominated by male contributions and voices. We make 5 key recommendations, discussed in more detail in the report, to begin the process of addressing the industry’s chronic gender inequality: 1. Collect more and better data on the music industry on a gender disaggregated basis; 2. Establish a well-resourced independent gender equality industry advocacy body; 3. Use gender equality criteria in deciding public funding outcomes; 4. Increase women’s representation in decision-making structures; 5. Address gender bias in the Australian music industry by prioritising inclusivity and representation as core industry values (for example through funding and implementing training programs). The music industry is skipping a beat when it comes to gender equality. We hope that our report will stimulate industry thinking and action for change.
Accepted: 2019-10-24 Publisher: University of Sydney

The Going Out In Sydney App: Evaluating the Utility of a Smartphone App for Monitoring Real-World Illicit Drug Use and Police Encounters Among Festival and Club Goers - Hughes, Caitlin Elizabeth; Moxham-Hall, Vivienne Louisa (Substance Abuse: Research and Treatment, 2017)
Gaining accurate information on illicit drug use and policing in real-world settings is a challenge. This study examines the utility of a smartphone app (‘Going Out In Sydney’) to prospectively follow up illicit drug use and policing encounters at music festivals and licensed entertainment precincts in Sydney, Australia. In all, 38 regular festival and licensed entertainment venue attendees used the app to log nights out over a 3-month period, including (1) where they went (eg, festival, nightclub), (2) the prevalence of illicit drug use, and (3) the incidence and nature of police encounters. A survey and interview were then conducted about the utility of the app. The app enabled rich data collection (n = 353 entries) about illicit drug use and policing at both target settings. Follow-up surveys indicated that most participants were extremely satisfied with the ease of use of the app and privacy afforded, and compared with other data collection modes, such as paper-based logs and online surveys, rated the app the most desirable method of data collection. This suggests smartphone apps may be a viable option for future studies on illicit drug use and policing of drugs.
Publisher: SAGE Publications Ltd STM
Keywords: Mobile app; app; drug use; offending; policing; smartphone

Not in our house Chicago Theatre Community (Not in our house Chicago Theatre Community, 2017)
making safe spaces to do dangerous work
Keywords: Bibliographie; Nettoyer

Femmes et jazz dans le Québec de l’entre-deux-guerres : entre le récit historique, les archives et le passé - Blais-Tremblay, Vanessa (Les Cahiers de la Société québécoise de recherche en musique, 2017)
This article contextualizes some of the roles that women played in Montreal’s interwar jazz scene. The archives testify to the importance of pianists such as Vera Guilaroff and Ilene Bourne, piano teacher Daisy Peterson Sweeney, dance teachers Olga Spencer Foderingham and Ethel Bruneau, as well as black women performers on the variety stage in the development of Canada’s most thriving jazz scene in the first half of the twentieth century. This article explains why women were drawn to these particular performance spaces (piano, teaching, theatrical dance) and documents the historiographical processes that have led to their marginalization from the historical record.
Publisher: Société québécoise de recherche en musique
Keywords: Bibliographie; Nettoyer

Montréal une ville festive pour toutes: Avis sur la sécurité des femmes et des jeunes femmes cisgenre et trans lors des événements extérieurs à Montréal - Conseil des Montréalaises (2017)
Keywords: Bibliographie; Camille; Nettoyer

More Than Two-Spirit: Queer Indigenous Sovereignty and Survivance in Museums - Cooper, Caitlin Skye (Université de Washington, 2017)
Keywords: Bibliographie; Nettoyer

gender inequalities in music: a comparative study of policy responses in the UK and Sweden - de Boise, S (International Journal of Cultural Policy, 2017)

Consultations publiques sur le harcèlement et la violence sexuelle en milieu de travail: ce que nous avons entendu - Emploi et Développpement social Canada (Gouvernement du Canada, 2017)
OCLC: 1015238443
Keywords: Bibliographie; Nettoyer

‘Staff can't be the ones that play judge and jury’: Young adults’ suggestions for preventing unwanted sexual attention in pubs and clubs - Fileborn, Bianca (Australian & New Zealand Journal of Criminology, 2017)
This paper explores young adults' suggestions for preventing unwanted sexual attention in licensed venues. Despite emerging evidence that unwanted sexual attention and sexual violence are significant issues faced by young adults in the night-time economy, there has been little introduced in the way of preventative strategies or campaigns. Drawing on a mixed-methods research project undertaken in Melbourne, Australia, I contend that exploring young adults' suggestions for prevention is instructive in a number of ways. Young adults are the primary users of licensed venues and thus may provide insight into potential strategies for prevention. It can also illuminate the discursive positions that young adults draw on in talking about prevention and their understandings of unwanted sexual attention.
Keywords: Camille

Code of Silence: A call to action to address and prevent abuse in dance communities - Forcier, Marie France (The Dance Current, 2017)
Keywords: Bibliographie; Nettoyer

*Loi visant à prévenir et à combattre les violences à caractère sexuel dans les établissements d’enseignement supérieur - Gouvernement du Québec (2017)
Keywords: Bibliographie; Nettoyer

Sexual Harassment in the Creative Industries: Tolerance, Culture and the Need for Change - Hennekam, Sophie; Bennett, Dawn (Gender, Work & Organization, 2017)
The economic, social and cultural contributions of the creative industries are essential elements of many societies and their governments' policies. However, there is growing evidence that precarity, competition and lack of regulation within these industries is exacerbating inequalities with respect to gender, race and class. With a focus on gender and sexual harassment among female workers, this study involved 32 in-depth interviews with women working in the Netherlands' creative industries. Data were analyzed using content analysis. Findings suggest that sexual harassment is prevalent, and many women considered it to be part of their occupational culture and career advancement. Four factors influenced this phenomenon: competition for work; industry culture; gendered power relations; and the importance of informal networks. Implications include the need for a climate of non-tolerance, sector-specific research and guidelines, sensitivity training and further work with unions and professional associations to provide worker protection strategies traditionally undertaken by organizations. The article concludes that effective sexual harassment prevention requires action at the individual, educational, sectoral and governmental levels, beginning with public conversations to convey the message that sexual harassment is never acceptable.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/gwao.12176

Sexual Harassment in the Creative Industries: Tolerance, Culture and the Need for Change: Sexual harassment in the creative industries - Hennekam, Sophie; Bennett, Dawn (Gender, Work & Organization, 2017)
The economic, social and cultural contributions of the creative industries are essential elements of many societies and their governments’ policies. However, there is growing evidence that precarity, competition and lack of regulation within these industries is exacerbating inequalities with respect to gender, race and class. With a focus on gender and sexual harassment among female workers, this study involved 32 in-depth interviews with women working in the Netherlands’ creative industries. Data were analyzed using content analysis. Findings suggest that sexual harassment is prevalent, and many women considered it to be part of their occupational culture and career advancement. Four factors inﬂuenced this phenomenon: competition for work; industry culture; gendered power relations; and the importance of informal networks. Implications include the need for a climate of non-tolerance, sector-speciﬁc research and guidelines, sensitivity training and further work with unions and professional associations to provide worker protection strategies traditionally undertaken by organizations. The article concludes that effective sexual harassment prevention requires action at the individual, educational, sectoral and governmental levels, beginning with public conversations to convey the message that sexual harassment is never acceptable.
Keywords: Bibliographie; Irina; Nettoyer

Debranchée (Unplugged) - Laurier, Mathilde; St-Laurent, Marie-Claude; Hébert, Maude; Milot, Marie-Ève (2017)
Débranchée (Unplugged) est une fiction qui traite des violences sexuelles dans le monde adolescent. La pièce raconte l'histoire de deux amies ébranlées par les rumeurs d'agressions sexuelles qui se propagent à haute vitesse dans leur école. Quand Allison brise la loi du silence, toute une chaîne de réactions s'enclenche. Des témoignages fusent, donnant une voix à toutes ces violences sexuelles trop souvent vécues dans l'anonymat. Devant l'ampleur du phénomène, les deux protagonistes cherchent à transformer l'explosion créée en un élan de solidarité. Elles iront jusqu'au bout. Le show aura lieu.
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Les dénonciations publiques d'agressions sexuelles : du mauvais usage de la présomption d’innocence - Lessard, Michaël (Revue Femmes et Droit, 2017)
French Abstract: Lorsqu’une victime dénonce son agresseur sur la place publique, certaines personnes tentent de la réduire au silence en invoquant le droit à la présomption d’innocence. Ce fut particulièrement évident en 2014, lors du mouvement #AgressionNonDénoncée ; ce le fut encore à l’automne 2015, alors que des femmes autochtones de Val-d’Or dénonçaient les agressions sexuelles commises à leur endroit par des policiers ; ce le fut aussi en 2016 à l’occasion de la dénonciation du député Gerry Sklavounos par Alice Paquet ; et l’argument légaliste réapparaît ainsi périodiquement sur la scène publique. Pourtant, peut-on vraiment bâillonner une victime en mettant de l’avant les droits de son agresseur ? L’auteur estime qu’il s’agit là d’un mauvais usage de la présomption d’innocence. Dans ce texte, il explique que la présomption d’innocence doit être replacée dans son contexte juridique. Le droit à la présomption d’innocence est un principe fondamental qui protège les accusés contre le pouvoir punitif de l’État. Il trouve uniquement application dans le processus pénal et n’est pas conçu pour être employé sur la scène publique. De plus, l’auteur explique que, dans le cadre du processus pénal, la présomption d’innocence favorise la création d’un espace de discussion où les parties peuvent débattre de la culpabilité. Pourtant, lorsqu’elle est invoquée sur la scène publique, elle ne fait que placer les victimes dans un processus violent de remise en question de leur crédibilité, tout en protégeant les agresseurs. Son invocation crée une atmosphère qui décourage les dénonciations. Le débat public dévie, laissant peu de place pour critiquer nos systèmes de plaintes dysfonctionnels et la culture du viol. En ce sens, la présomption d’innocence n’est pas invoquée afin d’établir un dialogue constructif, mais plutôt pour faire taire les critiques.English Abstract: When a victim reports her aggressor publicly, some people try to silence her voice under the guise of the right to the presumption of innocence. This was especially remarkable in 2014, within the movement #AgressionNonDénoncée; and again in the fall of 2015, when Val-d’Or Indigenous women reported being sexually assaulted by police. It was also the case in 2016 when Alice Paquet denounced Member of Provincial Parliament Gerry Sklavounos, and the legal argument thus periodically reappears on the public stage. However, can we really silence a victim by advancing the rights of her aggressor? The author believes that this is a case of inappropriate use of the presumption of innocence. In this text, he explains that the presumption of innocence must be placed in its legal context. The right to the presumption of innocence is a principle that protects litigants against the punitive power of the state. Its sole application belongs in the criminal process, and it was not designed to be used as such on the public stage. In addition, the author explains that, at the heart of the criminal process, the presumption of innocence promotes the creation of a discussion space where all parties may debate the guilt. However, when it is invoked in the public sphere, it only places the victims in an aggressive process of questioning their credibility while protecting the aggressors. Its invocation creates a climate that deters denunciations of sexual assaults. The public debate deviates, leaving little room to criticize our dysfunctional complaint systems and rape culture. In that sense, the presumption of innocence is not invoked in order to establish a constructive dialogue, but it has the effect of shutting down its critics. In this article, the author explains why the right to the presumption of innocence must not be engaged in this way in the public sphere.
Keywords: Bibliographie; Nettoyer

"They're Only Laughing 'Cause You're Pretty": Women's Experiences at Comedy Clubs - Lopez, Victoria Angelina (2017)
Stand-up comedy, like many forms of public entertainment or workplace organizations, is a field dominated by men. The deeply embedded perception that women are not funny, or not as funny as their counterparts, allow men’s privileged position in pursuing their career in comedy without their humor being questions based on their gender. However, the women’s’ experiences were found to be challenging with women’s humor being questioned and overshadowed by a hostile environment of sexual harassment. This disparity in the number of women represented in comedy is even more prevalent when it comes to the number of women who participate in stand-up comedy at the amateur level of open mic nights. This thesis examines gender disparity among comedians, the prejudices and discrimination women comedians face at the level of amateur comedian, and how they navigate through those barriers in comedy. Based on the findings from 14 in depth-interviews with 7 men and 7 women comedians, as well as observations of open-mic nights, this study investigates their experiences and perceptions of gender politics in comedy.
ISBN: 9780355540321
Keywords: Comedy clubs; Communication and the arts; Social sciences; Sophie-Anne

Sexual Harassment, Criminal Misconduct & Bullying in Australian Live Performance - Media Entertainment Arts Alliance (2017)
Keywords: Bibliographie; Nettoyer; Raphaël

Our Music My Body: 2017 Campaign & Survey Report - OurMusicMyBody (2017)
Keywords: Bibliographie; Nettoyer

Preventing Sexual Harassment and Abuses of Power: A Code of Behaviour - Royal Court Theatre (2017)
Keywords: Bibliographie; Nettoyer; Raphaël

Le traitement médiatique du mouvement #AgressionNonDénoncée dans la presse écrite québécoise francophone - Savard-Moisan, Raphaëlle (Université du Québec à Montréal, 2017)
Keywords: Bibliographie; Nettoyer

Brit awards announce voting shakeup after #BritsSoWhite outrage (the Guardian, 2016)
Organisers say academy is more gender-balanced and diverse after last year’s failure to nominate black artists
Section: Music

«Sous la ceinture»: La culture du viol, «pas une lubie de féministe» - Chabot, Kim (HuffPost, 2016)
«Sous la ceinture»: La culture du viol, «pas une lubie de féministe»
Keywords: Bibliographie; Nettoyer

« Sous la ceinture, unies pour vaincre la culture du viol », un livre qui tombe à point - Radio-Canada (Radio-Canada, 2016)
Judith Lussier, l'une des auteurs du livre « Sous la ceinture, unis pour vaincre la culture du viol », souligne que ce phénomène est omniprésent et tend à banaliser les gestes des agresseurs.
Publisher: Radio-Canada.ca
Keywords: Bibliographie; Nettoyer

Sexual Harassment in the Norwegian Theatre World - Kleppe, Bård; Røyseng, Sigrid (The Journal of Arts Management, Law, and Society, 2016)
The aim of this article is to provide insight into the phenomenon of sexual harassment in the theatre world. A survey among Norwegian actors is presented showing that sexual harassment is much more prevalent in the theatre world than in Norwegian work life in general. Further, the article aims at understanding why the prevalence is as high as it is. Based on qualitative interviews, the article points out some risk factors that shed light on the high prevalence of sexual harassment. Lastly, the risk factors are related to charismatic authority as an important power base in the theatre world.
Publisher: Routledge _eprint: https://doi.org/10.1080/10632921.2016.1231645
Keywords: Art organizations; Bibliographie; Nettoyer; Raphaël; charismatic authority; gender roles; mixed methods; sexual harassment; theatre

How to be a boss woman in the music industry - Jones, Rhian (Medium, 2016)
The music industry is hugely homogenised. In the UK, all three heads of the major record labels are men, and there’s just three women…

Doing gender, doing safety? Young adults’ production of safety on a night out - Fileborn, Bianca (Gender, Place & Culture, 2016)
This article explores the ways in which young adults produce a sense of safety in pubs and clubs. Despite considerable anxiety around issues pertaining to safety and violence in the night-time economy, there is little consideration of how young adults themselves feel about their safety on a night out, or how they achieve a sense of safety in a seemingly ‘risky’ social space. Drawing on mixed-methods research conducted in Melbourne, Australia, in this article I consider the strategies that young adults used to feel safe on a night out. I argue that feeling ‘safe’ is something that is actively produced through the use of these strategies, as well as providing an avenue for ‘doing’ gender.
Keywords: Camille; Safety; Seguridad; economía nocturna; feminidad; femininity; gender performance; licensed venues; locales autorizados; masculinidad; masculinity; night-time economy; performance de género; 夜间经济; 女性气质; 安全; 性别展演; 拥有许可证之营业场所; 男性气概

LGBTQ Welcoming Guidelines for Museums: developing a resource for the museum field - Leitch, Christopher; Youngs, Renae; Gavigan, Annette; Lesperance, Michael; Burns, William James; Cohen-Stratyner, Barbara; Hammond, Paul; Hansen, Jaden (Museums & Social Issues, 2016)
Beginning in 2014, the LGBTQ Alliance professional network of the American Alliance of Museums (AAM) met to develop and publish a broad set of LGBTQ Welcoming Guidelines for Museums. The authors sought to help museums be more inclusive of lesbian, gay, bisexual, transgender and queer staff and visitors. The Guidelines conform to the most recent established standards of professional practice in museums and touch on all areas of museum work; they may be viewed as part informational reference, part institutional self-assessment tool. The Guidelines were unveiled at the AAM’s 2016 annual meeting, and are now available at no charge online (http://www.aam-us.org/resources/professional-networks/lgbtq). The LGBTQ Alliance encourages readers to use and review the Guidelines and to make observations, critiques and corrections directly to the current chair, Mike Lesperance (mike@thedesignminds.com).
Publisher: Routledge _eprint: https://doi.org/10.1080/15596893.2016.1217460
Keywords: Bibliographie; Coffre à outils; Lesbian; Nettoyer; bisexual; diversity; gay; inclusion; transgender

Drugs at the campsite: Socio-spatial relations and drug use at music festivals - Dilkes-Frayne, Ella (International Journal of Drug Policy, 2016)
Background Music festivals have received relatively little research attention despite being key sites for alcohol and drug use among young people internationally. Research into music festivals and the social contexts of drug use more generally, has tended to focus on social and cultural processes without sufficient regard for the mediating role of space and spatial processes. Methods Adopting a relational approach to space and the social, from Actor-Network Theory and human geography, I examine how socio-spatial relations are generated in campsites at multiple-day music festivals. The data are drawn from ethnographic observations at music festivals around Melbourne, Australia; interviews with 18–23 year olds; and participant-written diaries. Results Through the analysis, the campsite is revealed as a space in process, the making of which is bound up in how drug use unfolds. Campsite relations mediate the formation of drug knowledge and norms, informal harm reduction practices, access to and exchange of drugs, and rest and recovery following drug use. Conclusions Greater attendance to socio-spatial relations affords new insights regarding how festival spaces and their social effects are generated, and how they give rise to particular drug use practices. These findings also point to how festival harm reduction strategies might be enhanced through the promotion of enabling socio-spatial relations.
Keywords: Drug use; Enabling places; Ethnography; Music festivals; Social context; Socio-spatial relations

Nightlife Ethnography, Violence, Policing and Security - Tomsen, Stephen; Wadds, Phillip (2016)

Post-postfeminism? New feminist visibilities in postfeminist times - Gill, R. (Feminist Media Studies, 2016)
This article contributes to debates about the value and utility of the notion of postfeminism for a seemingly “new” moment marked by a resurgence of interest in feminism in the media and among young women. The paper reviews current understandings of postfeminism and criticisms of the term’s failure to speak to or connect with contemporary feminism. It offers a defence of the continued importance of a critical notion of postfeminism, used as an analytical category to capture a distinctive contradictory-but-patterned sensibility intimately connected to neoliberalism. The paper raises questions about the meaning of the apparent new visibility of feminism and highlights the multiplicity of different feminisms currently circulating in mainstream media culture – which exist in tension with each other. I argue for the importance of being able to “think together” the rise of popular feminism alongside and in tandem with intensified misogyny. I further show how a postfeminist sensibility informs even those media productions that ostensibly celebrate the new feminism. Ultimately, the paper argues that claims that we have moved “beyond” postfeminism are (sadly) premature, and the notion still has much to offer feminist cultural critics.
Number: 4

Cultural value and cultural policy: some evidence from the world of live music - Behr, Adam; Brennan, Matt; Cloonan, Martin (International Journal of Cultural Policy, 2016)
This article considers live music policy in relation to wider debates on the cultural (as opposed to instrumental) value of the arts. The findings are based on research into amateur/enthusiast, state-funded and commercial concerts across a range of genres – classical, traditional folk, jazz, singer–songwriter and indie – using the Edinburgh Queen’s Hall venue as a case study. We argue that (1) articulations of the cultural or intrinsic value of live music across genres tend to lapse back into descriptions of instrumental value; (2) although explanations vary from audiences, artists and promoters as to why they participate in live music, they also share certain characteristics across genres and sometimes challenge stereotypes about genre-specific behaviours; and (3) there are lessons to be learned for live music policy from examining a venue that plays host to a range of genres and promotional practices.
Publisher: Routledge _eprint: https://doi.org/10.1080/10286632.2014.987668
Keywords: audience research; cultural value; live music; music policy; regulation

How can the music industry tackle its diversity issues? (Music Business Worldwide, 2016)
Kieron Faller from CI reveals best-practice for diverse businesses…

LGBT People and the UK Cultural Sector: The Response of Libraries, Museums, Archives and Heritage since 1950 - Vincent, John (Routledge, 2016)
This book examines the complex and conflicting relationships between LGBT people and our cultural and heritage organisations including libraries, museums and
Keywords: Bibliographie; Nettoyer

Taking time between g-string changes to educate ourselves: Sinéad O’Connor, Miley Cyrus, and celebrity feminism - Brady, Anita (Feminist Media Studies, 2016)
This article examines the feminist response to a 2013 online “feud” between singers Miley Cyrus and Sinéad O’Connor that began when Cyrus connected the video for her single “Wrecking Ball” to O’Connor’s video for “Nothing Compares 2 U.” O’Connor’s response criticised Cyrus’ sexualised image, and the exchanges that followed sparked debate among feminists over the limits of sexual “agency,” and the sexual politics of feminism. This took place within a wider media context that has seen an apparent increase in female celebrities explicitly identifying themselves as feminist. Critics of this “celebrity feminism” argue that the sexualised star systems of its proponents are at odds with the aims of feminist politics. This article draws on post-structuralist feminist theory to question the positioning of celebrity feminism as exterior to an imagined “feminist movement.” Using the Cyrus/O’Connor feud, I argue that such a binary potentially reaffirms the structures of power that feminism seeks to oppose, and ignores the ways celebrity culture and contemporary media practice might combine to produce new understandings of the field of feminism.
Publisher: Routledge _eprint: https://doi.org/10.1080/14680777.2015.1137960
Keywords: Celebrity feminism; Miley Cyrus; Sinéad O’Connor; feminist post-structuralism; third-wave feminism

Damaging and daunting: female journalists’ experiences of sexual harassment in the newsroom - North, Louise (Feminist Media Studies, 2016)
Female journalists’ experiences of sexual harassment are barely documented in the literature about Australian news journalism despite evidence of its ongoing prevalence. There have been some stories of harassment detailed in autobiographies by female journalists and the occasional article in the mainstream media about individual incidents, but it wasn’t until 1996 that a union survey provided statistical evidence of an industry-wide problem. That Media, Entertainment and Arts Alliance survey found that more than half of the 368 female participants had experienced sexual harassment at work. In 2012, I conducted the largest survey of female journalists in Australia finding that there was an increased number of respondents who had experienced sexual harassment in their workplaces. In a bid to better understand female journalists’ experiences of sexual harassment, this paper analyses written comments made by survey participants in relation to key questions about harassment. It finds that most downplay its seriousness and do not make formal reports because they fear victimisation or retaliation. As a consequence, a culture of secrecy hides a major industry problem where many women believe they should work it out themselves and that harassment is the price they have to pay for working in a male-dominated industry.
Publisher: Routledge _eprint: https://doi.org/10.1080/14680777.2015.1105275
Keywords: Myriam; Sexual harassment; female journalists; gender and work; gendered newsrooms; survey of Australian female journalists

Risky Pleasures?: Club Cultures and Feminine Identities - Hutton, Fiona (Routledge, 2016)
In this book Fiona Hutton provides a fascinating insight into women's experiences of clubbing. Based on a rich ethnographic account of the Manchester club scene, Risky Pleasures? is set within the context of the theoretical literature on youth subcultures, female friendship, consumption, risk and the city. The work highlights both the producers of club scenes - promoters, DJs, dealers - and the consumers - women negotiating pleasure and risk in club spaces and in the city at night. It explores the range of club spaces, developing a typology of 'mainstream' and 'underground' clubs, and considers how different types of participants are attracted to different 'scenes'. It examines women's recreational drug-use within a club context and discusses issues of sexuality, tolerance and the importance of 'attitude' in terms of women's feelings of safety. Revealing the important role of different spaces and different atmospheres in how women participate in club scenes, Fiona Hutton argues that drug taking and sexual pleasure are always contextualized within the environments created in different spaces, and that the risk and danger negotiated by women clubbers are counterbalanced by fun and pleasure - and ultimately empowerment.

Jian Ghomeshi est acquitté - Radio-Canada (Radio-Canada, 2016)
Jian Ghomeshi est acquitté de toutes les accusations qui pesaient contre lui. Le juge William B. Horkins a rendu sa décision, jeudi matin, à Toronto.
Publisher: Radio-Canada.ca
Keywords: Bibliographie; Nettoyer

Challenging the Myth of Gender Equality in Sweden - Lena, Martinsson; Gabriele, Griffin (Policy Press, 2016)
Sweden is often considered one of the most gender-equal countries in the world and held up as a model to follow, but the reality is more complex. This is the first book to explode the myth of Swedish gender equality, both offering a new perspective for an international audience, and suggesting how equality might be rethought more generally. While the authors argue that the gender-equality mantra in Sweden has led to a society with increased opportunities for some, they also assert that the dominant norm of gender equality has become nationalistic and builds upon heteronormative and racial principles. Examining the changing meanings and parameters of gender equality against the country's social-democratic tradition and in the light of contemporary neoliberal ideologies, the book constitutes an urgent contribution to the debates about gender-equality policies and politics.
Keywords: Social Science / Gender Studies; Social Science / Sociology / General

Women Harassment at Workplace: A Study of Pakistani Television Channels - Zia, Anjum; Batool, Sumera; Yasin, Zaeem (2016)
The present study explores the contemporary status of women harassment in Pakistani media industry taking alongside theoretical consideration of liberal feminism theory. An empirical method was adopted and in-depth interviews were conducted with media employees of both genders at television channels of the country. The study examined six core dimensions of harassment including working environment of the organization, male dominance, women harassment at workplaces, stereotype thinking patterns about women, offensive remarks on appearance of female colleagues and reporting of harassment issues to explore the current situation of women harassment in television channels of high repute. Findings of the study revealed that regardless of their ample role in thriving Pakistani media, women journalists are facing harassment at their workplaces but majority of them lesser likely to report harassment issues. Existence of stereotype thinking patterns about women and offensive remarks about appearance of women point towards severity of situation about women harassment at Pakistani media industry. Interestingly, despite male domination in media industry, general environment of media organizations is reported as satisfactory at large, whereas research concludes with highlighting areas for people working within and outside media organizations to eradicate harassment at workplaces. Keywords: Women harassment, male dominance, stereotype thinking patterns, Pakistani media, reporting of harassment.
Keywords: Myriam; Television

Valuing Musical Participation - Pitts, Stephanie (Routledge, 2016)
Increasingly, it is becoming evident that those involved in socio-musical studies must focus their investigative lens on musical practice and articulation of the self, on music and community involvement and on music as a social medium for social relationships. What motivates people to be involved in musical performance, and how do they articulate these needs and drives? What do performers gain from their involvement in musical activities? How do audience members perceive their relationship to the performer, the music and the event? These questions and many more are addressed here with the benefit of detailed empirical work, including case studies of a chamber music festival and a contemporary music summer school. Pitts investigates the value of musical participation for performers and audience members in a range of contexts, using a multi-disciplinary approach to place new empirical data in the framework of existing theory and literature. Themes examined include: the shared musical experience; the social structures of performing societies; how people identify with music; the values implicit in musical preferences; the social responsibilities of the performer; the audience view of concerts and festivals; the social power of music and educational implications and responsibilities. Pitts draws upon literature from musicology, sociology and psychology of music, ethnomusicology, music education and community music to demonstrate the diversity of enquiry about musical behaviours. The conclusions of the book are based upon empirical evidence gleaned through case studies, with the data integrated thematically throughout, to enable a greater depth of discussion than individual studies usually permit.

Who are the most powerful people in music? Jay Z? Kanye? Beyoncé? No, it’s old white men (the Guardian, 2016)
The 2016 Billboard Power 100 is dominated by white men born before Elvis had a hit. This isn’t only a problem of representation – it’s also bad for the industry
Section: Music

Learning to labour unequally: Understanding the relationship between cultural production, cultural consumption and inequality - Oakley, Kate; O'Brien, Dave (Social Identities, 2016)
Inequality has become essential to understanding contemporary society and is at the forefront of media, political and practice discussions of the future of the arts, particularly in the UK. Whilst there is a wealth of work on traditional areas of inequality, such as those associated with income or gender, the relationship between culture, specifically cultural value, and inequality is comparatively under-researched. The article considers inequality and cultural value from two points of view: how cultural value is consumed and how it is produced. The paper argues that these two activities are absolutely essential to understanding the relationship between culture and social inequality, but that the two activities have traditionally been considered separately in both academic research and public policy, despite the importance of culture to British and thus international policy agendas. The article uses the example of higher education in the UK to think through the relationship between cultural consumption and production. In doing, so the article maps out a productive possibility for a new research agenda, by sketching where and how research might link cultural consumption and production to better understand inequality.

Centre de Ressources et d'intervention pour homme (Criphase, 2016)
Keywords: Coffre à outils; À ajouter

Ressources d’aide (Fondation Marie-Vincent, 2016)
La Fondation Marie-Vincent aide les enfants et les adolescent·e·s victimes de violence. Elle contribue à prévenir la violence sexuelle.
Keywords: Coffre à outils; À ajouter

Navigating the boys’ club: Debra DiGiovanni and the performative strategy of comic self-deprecation - Deveau, Danielle Jeanine (International Journal of Cultural Studies, 2016)
This article considers Canadian comedian Debra DiGiovanni’s self-deprecatory humour as a performative strategy. In keeping with a performance tradition of self-deprecation as established by women like Phyllis Diller and Joan Rivers, DiGiovanni offers ‘failure’ as a comic strategy. Her comedy is heavily reliant upon the framing of her lack in relationships, in self-control and in body image (in relation to normative gender standards and expectations). At the same time, however, DiGiovanni also engages critically with gendered expectations of heteronormative desirability, lampooning thin women, superficial men and celebrity culture. Although her comedy is generally characterized by self-deprecation, her humour also leaves space for an ambivalent politics of gender.
Keywords: Sophie-Anne

Reclaiming the Night-Time Economy - Fileborn, Bianca (Palgrave Macmillan UK, 2016)
Keywords: Alcohol; Assemblage; Camille; Community; Crime prevention; Criminology; Culture; Drugs; Environmental design; Gender; LGBTIQ; Licensed venues; Safety; Sexual consent; Sexual ethics; Sexual offending; Sexual violence; Sexuality; Space; Young people

Gender, Metal and the Media: An Introduction - Hill, Rosemary Lucy (Gender, Metal and the Media: Women Fans and the Gendered Experience of Music, 2016)
Hill offers a much needed discussion of the lack of consideration given to gender in academic discussions of hard rock and metal music and the media. Drawing on her own experience as a musician and fan, the author argues that orthodoxies—e.g., the genre is inclusive, the music asexual and sexism non-existent—are only able to persist within the literature because scholars have neglected to understand how musical experiences are gendered. Within the context of feminist popular music scholarship, work on fandom and feminist methodological work, Hill outlines the need to study hard rock, metal and the media with close attention to the influence of gender.
Keywords: Black Metal; Hard Rock; Metal Music; Rock Music; Social Expression

Hard Rock and Metal as an Imaginary Community - Hill, Rosemary Lucy (Gender, Metal and the Media: Women Fans and the Gendered Experience of Music, 2016)
Hill examines the differing theoretical frameworks, e.g., subculture and scene, used to examine hard rock and metal fans, arguing that these have worked to the detriment of understanding the gendered experience of music, including taking pleasure in the music. She proposes a new way of thinking about fandom that incorporates fans’ feelings of community. Drawing on Anderson’s (Imagined Communities: Reflections on the Origin and Spread of Nationalism. Verso, 1991) theory of the nation, and feminist writings on community (Weiss and Friedman, Feminism and Community. Temple University Press, 1995), she argues that ‘imaginary community’ better reflects fans’ sense of community, whilst allowing deep consideration of the ideology of the community with particular reference to values, beliefs, traditions and myths. She argues that these are deployed to create a sense of cohesion in spite of inequalities and unacknowledged privileges.
Keywords: Extreme Metal; Gender Construction; Hard Rock; Metal Community; Moral Panic

Listening to Hard Rock and Metal Music - Hill, Rosemary Lucy (Gender, Metal and the Media: Women Fans and the Gendered Experience of Music, 2016)
This chapter challenges readings of hard rock and metal as masculine music. Hill examines women’s accounts of their experiences of musical pleasure. Through analysis of women fans’ descriptions of their favourite bands, she argues that, pace Kahn-Harris (2007), fans can be very articulate about what they like. Work of feminist writers on rock music is enlisted to argue that considering women’s listening pleasure gives new insights into the meaning of hard rock and metal music. The assumption that hard rock and metal is a masculine genre neglects important aspects of women’s fandom which diverge from the dominant myths.
Keywords: False Consciousness; Hard Rock; Heavy Metal; Musical Experience; Rock Music

Metal and Sexism - Hill, Rosemary Lucy (Gender, Metal and the Media: Women Fans and the Gendered Experience of Music, 2016)
Chapter 6 considers the allegations that hard rock and metal is sexist. Talking to British women fans reveals that in their experiences, hard rock and metal is less sexist than the ‘mainstream’. Using research on sexism across a range of fields, Hill argues that understanding what counts as sexism is complex and requires critical work by fans when sexism is normalised. Listening to what fans say about the context of their experiences within their broader lives is vital for better understanding. The author argues that the genre provides moments in which women fans may gain a feeling of genderlessness. Ultimately, however, the feeling of liberation only comes through assimilation into the culture, a culture that ignores women as much as possible. Nevertheless, that temporary feeling is a valuable one.
Keywords: Hard Rock; Metal Event; Music Video; Sexual Harassment; Unwanted Sexual Attention

The Gendered Experience of Music - Hill, Rosemary Lucy (Gender, Metal and the Media: Women Fans and the Gendered Experience of Music, 2016)
The final chapter argues that close examination of the specific experiences of women in their engagements with the hard rock and metal media, the music, and musical events reveals how the experience of music is shaped by sexist assumptions about women and about how music should be listened to. Musical pleasure does not exist on a universal, transcendental plane. It is informed and shaped by the socio-cultural circumstances of the listener. Hill maintains that it is vital to acknowledge how these circumstances make for differing experiences: it is an important first step for countering sexism. The chapter concludes with a short plan for how hard rock and metal may imagine a genderless future, and how this imagined community might work towards it.
Keywords: Hard Rock; Metal Musician; Music Culture; Normative Femininity; Science Fiction

The Media and the Imaginary Community - Hill, Rosemary Lucy (Gender, Metal and the Media: Women Fans and the Gendered Experience of Music, 2016)
This chapter investigates how Kerrang! magazine, a key part of the metal media, creates an imaginary community of hard rock and metal fans. Using semiotic analysis, the author extrapolates four myths that are forged in the letters pages: two that are presented by the magazine as being common sense values of the community (equality and authenticity) and two that are less obvious, the groupie and the warrior, which determine how women and men are portrayed. These myths work together to depict the imaginary community as ideologically invested in maintaining the masculinity of the genre at the expense of femininity. Hill argues that dominant representations of women in the imaginary community render them as adjuncts to the real members of the community—the men—and this has damaging consequences.
Keywords: Hard Rock; Hegemonic Masculinity; Horror Film; Letter Writer; Metal Community

Women Fans and the Myth of the Groupie - Hill, Rosemary Lucy (Gender, Metal and the Media: Women Fans and the Gendered Experience of Music, 2016)
Chapter 4 scrutinises the impact that the myth that women fans are groupies has on British hard rock and metal women fans. Women fans must negotiate the stereotype without accepting the title if they want their fandom to be respected, this results in a defensiveness about sexual and fannish reputations, which is an overtly gendered experience. Hill moves to examine the ways in which women’s desire for musicians and the complicated ways in which it must be negotiated impact on fans’ ability to express their fandom and their sexuality. The problem of the groupie myth lies not just with the expectations it places upon women but also in the ways in which it prevents discussion of more sensual and embodied experiences of musical pleasure.
Keywords: Hard Rock; Music Industry; Physical Attraction; Sexual Attraction; Sexual Pleasure

Irish Equity Survey 2016 - Irish Equity (2016)
Keywords: Bibliographie; Nettoyer; Raphaël

Une victime de Claude Jutra témoigne: des attouchements dès 6 ans - Pilon-Larose, Hugo (La Presse, 2016)
Keywords: Bibliographie; Nettoyer

"Yeah, We Serve Alcohol, but … We Are Here to Help": A Qualitative Analysis of Bar Staff's Perceptions of Sexual Violence - Powers, Ráchael A.; Leili, Jennifer (Violence and Victims, 2016)
This study is an exploratory analysis of how bar staff perceive their role in preventing sexual harassment and assault. In particular, through qualitative focus group interviews, this study explores bar staff's attitudes surrounding sexual harassment/assault, how they currently handle these situations, and their opinions regarding programs and policies that currently mandate responsibility. Six major themes emerged including their hesitation to discuss sexual violence, their unique position as a service provider, their lack of knowledge (but eagerness to learn), and their reliance on stereotypical scenarios of sexual violence and interventions. These findings are situated in a framework for understanding barriers to bystander intervention and implications for community-based bystander programs are discussed.
Keywords: Adult; Camille; Female; Focus Groups; Helping Behavior; Humans; Interpersonal Relations; Male; Rape; Restaurants; Sex Offenses

Unwanted Sexual Attention in Licensed Venues: Considering LGBTIQ Young Adults' Experiences and Perceptions - Fileborn, Bianca (2015)
English Abstract: Sexual violence within the lesbian, gay, bisexual, transgender/transsexual, intersex and queer (LGBTIQ) communities remains largely under-researched and under-theorised. Yet, emerging research suggests that sexual violence is a significant issue within the LGBTIQ communities. Additionally, the occurrence of sexual violence and unwanted sexual attention within specific social and cultural contexts is, for the most part, insufficiently examined. This article draws on research exploring young LGBTIQ adults’ perceptions and experiences of unwanted sexual attention in licensed venues. Firstly, I consider the theoretical and conceptual underpinnings of ‘unwanted sexual attention’ as a category of analysis. I then move on to consider participants’ use of licensed venues, the particular significance of pubs and clubs to LGBTIQ young people, and their perceptions and experiences of unwanted sexual attention. Finally, I discuss the implications of these findings for theoretical and conceptual understandings of unwanted sexual attention and sexual violence.
Keywords: Camille; Gender; Género; LGBTIQ; economía nocturna; licensed venues; locales con licencia; night time economy; orientación sexual; sexual orientation; sexual violence; violencia sexual

‘Safe Spaces’: Experiences of Feminist Women-Only Space - Lewis, Ruth; Sharp, Elizabeth; Remnant, Jenni; Redpath, Rhiannon (Sociological Research Online, 2015)
The gendered nature of safety has been explored empirically and theoretically as awareness has grown of the pervasive challenges to women's safety. Notions of ‘safe space’ are frequently invoked in wider feminist environments (particularly, recently, in relation to debates about trans people's access to women's spaces), but are relatively neglected in academia. Indeed, despite a body of scholarship which looks at questions of gender, safety and space, relatively little attention has been paid to exploring the meaning of ‘safety’ for women and, particularly, the meaning and experience of spaces they consider to be ‘safe.’ Drawing on focus group data with 30 women who attended a two-day, women-only feminist gathering in the UK, this paper analyses experiences of what they describe as ‘safe space’ to explore the significance and meaning of ‘safety’ in their lives. Using their accounts, we distinguish between safe from and safe to, demonstrating that once women are safe from harassment, abuse and misogyny, they feel safe to be cognitively, intellectually and emotionally expressive. We argue that this sense of being ‘safe to’ denotes fundamental aspects of civic engagement, personhood and freedom.
Publisher: SAGE Publications Ltd
Keywords: Activism; Feminism; Safety; Space; Women; Women-Only

Victoria Sets Up Taskforce To Tackle Harassment Of Women At Gigs (Tone Deaf, 2015)
Following a meeting of the Victorian Live Music Roundtable yesterday, Victorian Minister for Consumer Affairs, Gaming and Liquor Regulation Jane Garrett

All the girls in town: The missing women of Australian rock, cultural memory and coverage of the death of Chrissy Amphlett - Strong, Catherine (Perfect Beat, 2015)
This article will use the cultural and media materials produced around the death of Chrissy Amphlett as a way of interrogating the fact that surprisingly few resources exist that document or commemorate the contribution of women to the rock music scene in Australia. As Amphlett is unusual in being a woman who has, even before her death, claimed a place in the Australian rock canon, examining materials that are designed to construct her legacy upon her passing will provide examples of how women in Australian rock are discussed. It will be demonstrated that Amphlett’s gender is central to these discussions, and that she is used to both obscure the contributions of other women performers and to deny a need for women musicians to even be an object of discussion at all. These indings will be analysed using Aleida Assmann’s concepts of functional and storage memory, and it will be argued that the lack of information that we have about past female rockers makes it harder for women in Australia to see this ield as one they can participate in, and also makes the retention of memories about currently successful women musicians less likely.

Pathways to Help: Adolescent Sexual Assault Victims’ Disclosure and Help-Seeking Experiences - Campbell, Rebecca; Greeson, Megan R.; Fehler-Cabral, Giannina; Kennedy, Angie C. (Violence Against Women, 2015)
In this study, we conducted semistructured interviews with N = 20 adolescent sexual assault victims who sought postassault help from the medical and legal system to understand young survivors’ disclosure and help-seeking processes. Results revealed three distinct disclosure patterns and pathways to help-seeking. First, in the voluntary disclosure group, victims told their friends, who encouraged them to tell an adult, who then encouraged—and assisted—the survivors in seeking help. Throughout this process, the survivors’ disclosures at each step were within their control and reflected their choices for how to proceed. Second, in the involuntary disclosure pattern, victims also first disclosed to friends, but then those friends told adults about the assault, against the survivors’ wishes; the adults made the victims seek help, which was also against the survivors’ preferences. Third, in situational disclosures, the survivors were unconscious at the time of the assault, and their friends disclosed and sought help on their behalf. We also examined how these initial disclosure patterns related to victims’ continued engagement with these systems.
Publisher: SAGE Publications Inc
Keywords: adolescents; disclosure; help-seeking; rape; sexual assault

‘I Think Women are Possibly Judged More Harshly with Comedy’: Women and British Television Comedy Production - Mills, Brett; Ralph, Sarah (Critical Studies in Television, 2015)
Critics and creative workers have recently highlighted the lack of women working in British television comedy. Through thematic analysis of interviews with British television comedy professionals, this article explores how women talk about their work and their position within the industry. Outlining the specific industrial contexts within which female comedy professionals work, the article examines institutionalised gender norms and practical impediments which the interviewees' responses reveal, while also exploring the institutional and personal initiatives which they have developed to address these problems.
Publisher: SAGE Publications

Cultural Value and Inequality: A Critical Literature Review - Oakley, K; O'Brien, D (2015)
Inequality has become essential to understanding contemporary British society and is at the forefront of media, political and practice discussions of the future of the arts in the UK. Whilst there is a wealth of work on traditional areas of inequality, such as those associated with income or gender, the relationship between culture, specifically cultural value, and inequality is comparatively under-researched. The literature review considers inequality and cultural value from two points of view: how cultural value is consumed and how it is produced. The review argues that these two activities are absolutely essential to understanding the relationship between culture and social inequality, but that the two activities have traditionally been considered separately in both academic research and public policy. The review concentrates on the ‘big three’ issues of inequality – race, class and gender, where most of the literature is to be found, but also touches on disability, sexuality and spatial inequality. All of the research reviewed suggests an undeniable connection between cultural value and inequality. Understanding that connection is currently impeded by problems with data. The report suggests the political saliency of this topic means that public policy must do more to provide robust research, particularly about cultural production.

Sex, Gender and Work Segregation in the Cultural Industries - Hesmondhalgh, David; Baker, Sarah (The Sociological Review, 2015)
This chapter addresses work ‘segregation’ by sex in the cultural industries. We outline some of the main forms this takes, according to our observations: the high presence of women in marketing and public relations roles; the high numbers of women in production co-ordination and similar roles; the domination of men of more prestigious creative roles; and the domination by men of technical jobs. We then turn to explanation: what gender dynamics drive such patterns of work segregation according to sex? Drawing on interviews, we claim that the following stereotypes or prevailing discourses, concerning the distinctive attributes of women and men, may influence such segregation: that women are more caring, supportive and nurturing; that women are better communicators; that women are ‘better organized’; and that men are more creative because they are less bound by rules.
Publisher: SAGE Publications Ltd
Keywords: cultural industries; sexual division of labour; stereotypes; work segregation

Resilience & Melancholy: Pop Music, Feminism, Neoliberalism - James, Robin (John Hunt Publishing, 2015)
When most people think that “little girls should be seen and not heard,” a noisy, riotous scream can be revolutionary. But that’s not the case anymore. (Cis/Het/White) Girls aren’t supposed to be virginal, passive objects, but Poly-Styrene-like sirens who scream back in spectacularly noisy and transgressive ways as they “Lean In.” Resilience is the new, neoliberal feminine ideal: real women overcome all the objectification and silencing that impeded their foremothers. Resilience discourse incites noisy damage, like screams, so that it can be recycled for a profit. It turns the crises posed by avant-garde noise, feminist critique, and black aesthetics into opportunities for strengthening the vitality of multi-racial white supremacist patriarchy (MRWaSP). Reading contemporary pop music – Lady Gaga, Beyonce, Calvin Harris – with and against political philosophers like Michel Foucault, feminists like Patricia Hill Collins, and media theorists like Steven Shaviro, /Resilience & Melancholy/ shows how resilience discourse manifests in both pop music and in feminist politics. In particular, it argues that resilient femininity is a post-feminist strategy for producing post-race white supremacy. Resilience discourse allows women to “Lean In” to MRWaSP privilege because their overcoming and leaning-in actively produce blackness as exception, as pathology, as death. The book also considers alternatives to resilience found in the work of Beyonce, Rihanna, and Atari Teenage Riot. Updating Freud, James calls these pathological, diseased iterations of resilience “melancholy.” Melancholy makes resilience unprofitable, that is, incapable of generating enough surplus value to keep MRWaSP capitalism healthy. Investing in the things that resilience discourse renders exceptional, melancholic siren songs like Rihanna’s “Diamonds” steer us off course, away from resilient “life” and into the death.
Keywords: Bibliographie; Music / History & Criticism; Nettoyer; Philosophy / Social

Le mouvement masculiniste au Québec. L'antiféminisme démasqué - Blais, Mélissa; Dupuis-Déri, Francis (Les Éditions du remue-ménage, 2015)

What Makes a Lesbian Salsa Space Comfortable? Reconceptualising Safety and Homophobia - Boulila, Stefanie Claudine (Lesbian Geographies: Gender, place and power, 2015)
This chapter explores the sexual spatialisation of salsa dance spaces through the narratives of lesbian salsa dancers. It draws on conversations with seven
Num Pages: 20
Keywords: Bibliographie; Nettoyer

The Economic and Cultural Value of Live Music in Australia 2014 - Carter, D. (2015)
The Economic and Cultural Value of Live Music in Australia 2014

Gender and creative labour - Conor, B; Gill, R; Taylor S (The Sociological Review, 2015)
Keywords: gender inequality; neoliberalism; precariousness; self-representation; sexism

"for People Who Aren't Sure Who They Are, Theatre is a Great Place to Be": Narratives of Actors and their Sexual Identities - McCadden, Theodore Edward (Pennsylvania State University, 2015)
Keywords: Bibliographie; Nettoyer; Raphaël

Ghomeshi, l’avant et l’après - Deglise, Fabien (Le Devoir, 2014)
L’ex-animateur-vedette emporte aussi dans sa chute la loi du silence envers les abus sexuels.
Keywords: Bibliographie; Nettoyer

Unspeakable Inequalities: Post Feminism, Entrepreneurial Subjectivity, and the Repudiation of Sexism among Cultural Workers - Gill, Rosalind (Social Politics: International Studies in Gender, State & Society, 2014)
Work in the cultural and creative fields is marked by stark and growing inequalities relating to gender, class, and race/ethnicity. Yet, the same industries are also characterised by an ethos that celebrates openness, egalitarianism, and meritocracy. This paper explores this paradox, focusing in particular on gender inequalities. It argues that there is a need to move beyond the standard conventional explanations for women's under-representation within the creative workforce, which point to female childbearing and childcare as central. Whilst not disputing the significance of motherhood to women's career trajectories, the paper suggests that the repeated focus on maternity is problematic and may close down other areas of potential investigation and critique. The paper suggests that three alternative foci would repay attention in understanding inequalities in the CCI. First, the new, mobile, subtle, and revitalised forms of sexism in circulation urgently require further examination. Secondly, the power of the dominant post feminist sensibility which, in suggesting that “all the battles have been won,” renders inequality increasingly difficult to voice or speak about, demands critique. Thirdly, the new forms of labouring subjectivity required to survive in the field of cultural work may themselves be contributing to the inequalities in the field, by favouring an entrepreneurial individualistic mode that disavows structural power relations. These three aspects of life in the field of cultural work merit further attention and suggest that gender inequality has a variety of different causes, not all located in women's childbearing abilities. Moreover, the paper argues that the very myth of egalitarianism at work in the CCI may itself be a key mechanism through which inequality is reproduced.

Gay men in the performing arts: Performing sexualities within ‘gay-friendly’ work contexts - Rumens, Nick; Broomfield, John (Organization, 2014)
Building on emerging research on ‘gay-friendly’ organizations, this article examines if and how work contexts understood and experienced as ‘gay-friendly’ can be characterized as exhibiting a serious breakdown in heteronormativity. Taking the performing arts as a research setting, one that is often stereotyped as ‘gay-friendly’, and drawing on in-depth interview data with 20 gay male performers in the UK, this article examines how everyday activities and encounters involving drama school educators, casters and peers are shaped by heteronormative standards of gay male sexuality. Adopting a queer theory perspective and connecting with an emergent queer theory literature in organization studies, one concern articulated in this article is that heteronormative constructions of gay male sexualities constrain participants’ access to work; suggesting limits to the abilities and roles gay men possess and are able to play. Another concern is that when gay male sexualities become normalized in performing work contexts, they reinforce organizational heteronormativity and the heterosexual/homosexual binary upon which it relies. This study contributes towards theorizing the heteronormative dynamics of ‘gay-friendly’ places of work, arguing that gay male sexualities are performatively instituted according to localized heteronormativities which reinforce contextually contingent, restrictive heteronormative standards of gay male sexuality which performers are encouraged to embody and perform both professionally and personally.
Keywords: Bibliographie; Nettoyer; Raphaël

“Blurred Lines?” Sexual Aggression and Barroom Culture - Graham, Kathryn; Bernards, Sharon; Osgood, D. Wayne; Abbey, Antonia; Parks, Michael; Flynn, Andrea; Dumas, Tara; Wells, Samantha (Alcoholism, clinical and experimental research, 2014)
Background Meeting potential sexual/romantic partners for mutual pleasure is one of the main reasons young adults go to bars. However, not all sexual contacts are positive and consensual, and aggression related to sexual advances is a common experience. Sometimes such aggression is related to misperceptions in making and receiving sexual advances while other times aggression reflects intentional harassment or other sexually aggressive acts. The present study uses objective observational research to assess quantitatively gender of initiators and targets and the extent that sexual aggression involves intentional aggression by the initiator, the nature of responses by targets, and the role of third parties and intoxication. Methods We analyzed 258 aggressive incidents involving sexual advances observed as part of a larger study on aggression in large capacity bars and clubs, using variables collected as part of the original research (gender, intoxication, intent) and variables coded from narrative descriptions (invasiveness, persistence, targets’ responses, role of third parties). Hierarchical Linear Modeling (HLM) analyses were used to account for nesting on incidents in evening and bars. Results 90% of incidents involved male initiators and female targets, with almost all incidents involving intentional or probably intentional aggression. Targets mostly responded nonaggressively, usually using evasion to end the incident. Staff rarely intervened; patron third parties intervened in 21% of incidents, usually to help the target but sometimes to encourage the initiator. Initiators’ level of invasiveness was related to intoxication of the targets but not their own intoxication, suggesting intoxicated women were being targeted. Conclusions Sexual aggression is a major problem in bars often reflecting intentional sexual invasiveness and unwanted persistence rather than misperceptions in sexual advances. Prevention needs to focus on addressing masculinity norms of male patrons and staff that support sexual aggression and better management of the highly sexualized and sexist environments of most bars.
Keywords: Camille

Fortunes of feminism: from state-managed capitalism to neoliberal crisis - Guest, Carly (European Journal of Cultural and Political Sociology, 2014)
Publisher: Routledge _eprint: https://doi.org/10.1080/23254823.2014.948028

Gender then, gender now: surveying women's participation in Australian film and television industries - French, Lisa (Continuum : Journal of Media and Cultural Studies, 2014)
In the Australian audiovisual industries, women are a minority of the personnel in a large number of key creative roles and have considerably lower representation than in the Australian workforce generally. Despite the decline in their participation across several fields, the under-representation of women is not being addressed by these industries. Using findings from current research that includes a major survey of Victorian activity, this article engages with the urgent need for new approaches to thinking about the contribution and innovation of women: culturally, creatively and economically. Benchmarked against the last major study in 1992 (Cox and Laura), pivotal issues examined include barriers to progression, representation by job type and workplace/organizational cultures, along with a consideration of the current successes (relative to other areas) of women in television. Business, cultural and social arguments are made for the importance of gender equity, and an understanding of the contribution and value of women to these industries.
Publisher: Routledge _eprint: https://doi.org/10.1080/10304312.2014.888040
Keywords: Bibliographie; Irina; Nettoyer

Accounting for Space, Place and Identity: GLBTIQ Young Adults’ Experiences and Understandings of Unwanted Sexual Attention in Clubs and Pubs - Fileborn, Bianca (Critical Criminology, 2014)
This article considers the role of space, place and identity in influencing gay, lesbian, bisexual, transgender/transsexual, intersex and queer (GLBTIQ) young adults’ experiences of unwanted sexual attention in licensed venues. It is argued in this article that the roles of space, place and identity are largely absent from theoretical understandings of sexual violence. Gender-based accounts of sexual violence, while important, are unable to fully account for sexual violence that is perpetrated within and against GLBTIQ communities. Drawing on data obtained through a mixed-methods study, in the first half of the article I establish the manner in which GLBTIQ young adults’ unique relationship with licensed venues appears to mediate the ways in which unwanted sexual attention occurring in these spaces is experienced and understood. The second half of this article is concerned with exploring the intersections between unwanted sexual attention and heterosexist violence and abuse in clubs and pubs. I conclude by considering the implications of these findings for theoretical understandings of sexual violence and unwanted sexual attention.
Keywords: Gender Identity; Intimate Partner Violence; Sexual Identity; Sexual Orientation; Sexual Violence

Safe Space: Towards a Reconceptualization (Antipode, 2014)
The term “safe space” dates to the late twentieth century women's movement, but it has since been used in many different contexts. In this paper, we review and analyze historical and contemporary “safe spaces”. These include “separatist” safe spaces in women's, anti-racist, and feminist communities, “inclusive” safe space classrooms, and safe spaces in which (non-human) objects are central. We argue that safe spaces should be understood not through static and acontextual notions of “safe” or “unsafe”, but rather through the relational work of cultivating them. Such an understanding reveals several tendencies. Namely, safe spaces are inherently paradoxical. Cultivating them includes foregrounding social differences and binaries (safe–unsafe, inclusive–exclusive) as well as recognizing the porosity of such binaries. Renegotiating these binaries is necessarily incomplete; a safe space is never completely safe. Even so, we encourage the critical cultivation of safe space as a site for negotiating difference and challenging oppression.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/anti.12089
Keywords: activism; intersectionality; paradoxical space; porosity; safe space; safety

Making Media Work: Cultures of Management in the Entertainment Industries - Johnson, Derek; Kompare, Derek; Santo, Avi (NYU Press, 2014)
In popular culture, management in the media industry is frequently understood as the work of network executives, studio developers, and market researchers-"the suits"-who oppose the more productive forces of creative talent and subject that labor to the inefficiencies and risk aversion of bureaucratic hierarchies. However, such portrayals belie the reality of how media management operates as a culture of shifting discourses, dispositions, and tactics that create meaning, generate value, and shape media work throughout each moment of production and consumption. Making Media Work aims to provide a deeper and more nuanced understanding of management within the entertainment industries. Drawing from work in critical sociology and cultural studies, the collection theorizes management as a pervasive, yet flexible set of principlesdrawn upon by a wide range of practitioners-artists, talent scouts, performers, directors, show runners, and more-in their ongoing efforts to articulate relationships and bridge potentially discordant forces within the media industries. The contributors interrogate managerial labor and identity, shine a light on how management understands its roles within cultural and creative contexts, and reconfigure the complex relationship between labor and managerial authority as productive rather than solely prohibitive. Engaging with primary evidence gathered through interviews, archives, and trade materials, the essays offer tremendous insight into how management is understood and performed within media industry contexts. The volume as a whole traces the changing roles of management both historically and in the contemporary moment within US and international contexts, and across a range of media forms, from film and television to video games and social media.

Putting gender in the mix: employment, participation, and role expectations in the music industries - LEONARD, MARION (The Routledge Companion to Media & Gender, 2014)
Eﬀorts to map women’s participation in the music industries have been hampered by a lack of data. However, available statistics point to a continuing underrepresentation of women in the music industries; and the disparity is particularly acute within certain areas of practice. In 2010 the Performing Rights Society for Music (PRS), the UK’s leading collection society, revealed that women accounted for only 14 percent of their registered music creators and writers. This statistic prompted the PRS Foundation to fund the “Women Make Music” initiative as a way to raise awareness of the gender gap, correct stereotypes, encourage participation, and increase the proﬁle of women creating new music. Research commissioned in 2008 by the Cultural Leadership Programme and publishedas a substantial report, found that in the UK music sector “only 20% of businesses have any form of female representation on the management team and only 10% have an all female team” (Cultural Leadership Programme 2008: 29). According to the report, women in the music sector were generally very underrepresented within positions of responsibility: the average number of female executives per ﬁrm was as low as 0.2. Such evidence of gender inequality in leadership positions within the music industries is by no means unique to the UK. In 2012 the editorial team of the Australasian Music Industry Directory (AMID), in consultation with other industry professionals, ranked for the ﬁrst time the most powerful people in the Australian music industry. The criteria included who has the greatest “ability to ‘shape’ the scene,” along with “their involvement in industry initiatives, overall career accomplishment, economic impact and public proﬁle” (Fitzsimons 2012). The “power list” included 50 places and 56 people (some business partners held joint positions). Only six women appeared on the list, two of whom shared their place with a male colleague; overall, then, women were just under 11 percent. While the list can be critiqued for its partiality, it indicates the music industries’ gender gap. Books on women working in the music industries usually focus on women musiciansand performers, often with the aim of celebrating women’s contribution to the history of popular music (see, for example, Dahl 1984; Gaar 1993; Hirshey 2001; Downes 2012). In documenting women’s experience, ﬁeld research with musicians has shownhow women have established their music careers, from acquiring instruments and learning to play, to performing and navigating the music business (see, e.g., Bayton 1998; Tucker 2000; Reddington 2007; Leonard 2007). A few speciﬁcally highlight women involved in music production and sound engineering (Sandstrom 2000; Smith 2009). Some recent work on women’s changing relationship with music technologies examines how artist-producers (Wolfe 2012) and women involved in the electronic dance music scene (Farrugia 2012) have navigated a gendered sphere of practice which has historically and discursively been associated with masculinity. Music journalism has also been a focus, with critical accounts addressing the work of women music journalists and the gendered discourse of music journalism (McDonnell 1995; Davies 2001; McLeod 2001). While the literature on women musicians, journalists, DJs, and music engineers is growing, the experience of women working in other roles within the music sector is much less well documented. Indeed, Smith (2009: 308) remarks that, except for musicianship, “scholarship on gender segregation in other music industry roles has been meagre. Because of this, the gendered division of labour in the music industry is not yet adequately understood.” This chapter explores how gendered attitudes circulate within the workplace andin what ways they frame work in diﬀerent sectors of the music industries. The plural term “music industries” suggests the chapter is not engaging with a uniﬁed ﬁeld of practice, nor is it concerned only with the recording industry (Williamson and Cloonan 2007). I will draw on interviews with eight women who have worked in artist management, tour management, A&R (artist and repertoire), and concert promotion, although ﬁrst I discuss the contexts in which these women work as a way to establish the extent to which their occupations can be broadly characterized as sex segregated. These women work in largely under-studied but particularly sex-segregated areasof music employment. All eight were based in London, England and ranged in levels of seniority from a booking agent’s assistant to a general manager of a record company. Many of the women had established portfolio careers, having worked in different roles, including radio promotion, international relations, music publishing, and marketing, so had diﬀerent levels of experience in management, A&R, and concert promotion. For example, one participant worked for two years at a junior level in A&R before moving on to develop expertise in other areas, eventually becoming a general manager of a record company. Another participant began as a regional A&R scout and was promoted to A&R manager, where she stayed ten years. Therefore, they could oﬀer a broad perspective: collectively they were engaged with international professional networks, international tour management, and the management and career development of artists building international proﬁles. The majority of them worked with rock bands and artists but some had worked with artists in other genres. The participants could also reﬂect on their experience of working with artists at diﬀerent stages of career development, from new and developing bands through to major international recording stars. Seven of the approximately hour-long interviews were conducted by telephone; their responses to the open-ended questions were recorded and transcribed. One respondent oﬀered a written response to the research questions via email. The women all seemed candid in their responses. Their comments have been anonymized; references to particular record labels, bands, or named individuals have been omitted.
Num Pages: 10

A Music Room of One's Own: Discursive Constructions of Girls-only Spaces for Learning Popular Music - Björck, Cecilia (Girlhood Studies, 2013)
This article elaborates on discursive constructions of girls-only settings through the spatial metaphor of a room of one's own, as articulated in round-table discussions among staff and participants from girl-centered music programs in Sweden. The idea of a separate room refers to spaces for collective female empowerment as well as for individual knowledge acquisition and creativity. These spaces are constructed so as to provide the possibility for exploration, subjectivity, and focus, by offering (partial and temporary) escape from competition and control, from a gendered and gendering gaze, and from distraction. Girl-centered programs are also discussed as paradoxical because they function as gender-neutral when seen from the inside, but gender-specific when seen from the outside.
Publisher: Berghahn Journals Section: Girlhood Studies

From victim to survivor - and from survivor to victim: Reconceptualising the survivor journey - Jordan, Jan (Sexual Abuse in Australia and New Zealand, 2013)
Being recognized as a rape survivor has often been interpreted as implying a linear progression from the negative state of victimisation, experienced in the presence of the offender, to a stronger, more positive state, typically facilitated by external support mechanisms. Drawing primarily on interviews conducted with women victimised by New Zealand serial rapist, Malcolm Rewa, this article challenges the concept of a journey 'from victim to survivor' by considering the multiple ways in which these women sought to protect themselves and survive during the attack while also experiencing aspects of their postattack involvement with individuals and agencies as further victimisation. The article concludes by outlining some initial implications regarding what this may mean for professionals working with victim/survivors of sexual violence.
Publisher: Australian and New Zealand Association for the Treatment of Sexual Abuse
Keywords: Bibliographie; Nettoyer

Safe Space: The Riot Grrrl Collection - Keenan, Elizabeth K.; Darms, Lisa (Archivaria, 2013)
Riot Grrrl, an early-1990s teen feminist movement, adopted punk’s DIY modes of expression to encourage girls to address their shared oppression. The Riot Grrrl Collection, held at New York University’s Fales Library & Special Collections, documents the movement through the personal papers of those who were active in its formative years. This article uses the lens of feminist “safe space” to look at the collection from two perspectives: that of its founder, Lisa Darms, who is senior archivist at Fales, and that of ethnomusicologist Elizabeth Keenan, a scholar who has worked extensively with the collection. The concept of safe space was crucial to the all-girl meetings, dance parties, and bands that formed the foundation of Riot Grrrl. The authors argue that the safe space of Riot Grrrl created an intimate counter-public – that is, a space where girls established a feminist community through shared texts – but one that sometimes worked against its own intentions: boundaries erected for safety sometimes led to exclusion along lines of race, class, or gender identity. The authors extend the idea of safe space to issues of collection building from and within activist communities; to ideas of intimacy and privacy as they play out for donors, for researchers, and in the special collections reading room; and to the tension between the desire for access to activist history versus the requirements of archival preservation. The article examines how iterations of safe space are enacted across the personal papers in the Riot Grrrl archive, through both the materials themselves and their place in the archive. RÉSUMÉ Riot Grrrl, un mouvement du début des années 1990 pour adolescentes féministes, s’est inspiré du mouvement punk pour adopter les modes d’expression du « Do it yourself (DIY) », dans le but d’encourager les adolescentes à aborder leur oppression commune. La collection Riot Grrrl, détenue par la Fales Library & Special Collections de l’University New York, documente le mouvement grâce aux documents personnels de celles qui en étaient actives durant ses premières années. Cet article se sert du concept féministe du « lieu sûr » (« safe space ») afin d’examiner la collection à partir de deux perspectives : celle de sa fondatrice, Lisa Darms, qui est archiviste supérieure à Fales, et celle de l’ethnomusicologue Elizabeth Keenan, une spécialiste qui a travaillé en profondeur avec cette collection. Le concept du lieu sûr était crucial pour les adolescentes lors de leurs réunions et soirées dansantes et pour leurs groupes musicaux qui ensemble ont contribué à la fondation de Riot Grrrl. Les auteurs soutiennent que le lieu sûr de Riot Grrrl a créé un « contre-public intime » – c’est-à-dire un espace dans lequel les adolescentes ont pu établir une communauté féministe par l’entremise de textes partagés – mais un contre-public qui opérait parfois contre ses propres intentions : les limites imposées pour délimiter le lieu sûr ont parfois mené vers des exclusions basées sur la race, les classes sociales ou l’identité de genre. Les auteures élargissent le concept du lieu sûr aux questions liées à la création de collections par des communautés militantes et dans ces milieux; aux idées de l’intimité et de la vie privée auxquelles sont confrontés les donateurs et les chercheurs dans la salle de lecture des collections spéciales; et à la tension entre le désir d’avoir accès à l’histoire militante et les besoins liés à la conservation archivistique. Cet article examine comment l’itération du lieu sûr se fait par rapport aux documents personnels des archives Riot Grrrl, tant du côté des documents eux-mêmes que de leur place dans les archives.

Female, Mosher, Transgressor: A 'Moshography' of Transgressive Practices within the Leeds Extreme Metal Scene - Riches, Gabrielle; Lashua, Brett; Spracklen, Karl (IASPM Journal, 2013)
This paper examines and reconceptualises transgression in the Leeds extreme metal music subculture through theories of performance, embodiment and spectacle. The spectacle, for Debord (1967), is a social relation that is alienating and mediated by images, visuals, and technology. At a live extreme metal concert fans subvert social norms, challenge gendered expectations, and disregard norms of etiquette and decency. Moshing is the most visible and sensuous example of transgression within the extreme metal scene. It is an aggressive, physically demanding performance which embodies resistance to the impersonal and disillusioning world of the spectacle (Halnon, 2004). The pit is a transgressive space that is itself transgressed by women who participate in this masculine, chaotic space, disrupting the homosocial bonds of male solidarity (Gruzelier, 2007). This paper offers an ethnographic account of a female metal fan participating in the transgressive practice of moshing within the Leeds metal music scene – a moshography.
Number: 1
Keywords: Moshpits; embodiment; extreme metal music; performance ethnography; spectacle; transgression

Why producers of music use discourses of consumption (and why we shouldn't think that makes them prosumers) - Cluley, Robert (Arts Marketing: An International Journal, 2013)
Purpose ‐ The purpose of this paper is to demonstrate how people making music represent their production activities using images of consumption. Design/methodology/approach ‐ Supporting evidence is based on in-depth interviews with musicians and support personnel. The data are structured through a thematic analysis. Findings ‐ The paper argues that consumption serves as a discursive resource that allows cultural producers to make sense of production activities which do not conform to an image of production as an alienated form of labour. Originality/value ‐ Relating the analysis to the ongoing attempts to conceptualise cultural producers through the concept of prosumption, the paper concludes that there are limits to cultural producers' abilities to represent their production activities as production rather than a structural change in social or economic organisation, as suggested by some consumer researchers.

Why unpaid interns are bad for the music industry (the Guardian, 2013)
Helienne Lindvall: Big US record labels are being sued by former interns who worked for free – how do their UK counterparts measure up?
Section: Media

“A Different Kind of Man”: Mediated Transgendered Subjectivity, Chaz Bono on Dancing With the Stars - Mocarski, Richard; Butler, Sim; Emmons, Betsy; Smallwood, Rachael (Journal of Communication Inquiry, 2013)
Chaz Bono’s appearance on Dancing with the Stars (DWTS) marks one of the first primetime, network appearances of a postoperative transgender person. This article deconstructs the mediated gender subjectivities of Bono as constructed by the show itself via prerecorded segments, costume and song choices, dance partner interaction, and judges’ commentaries as well as those projected by Bono during the live, unscripted portions of the show. Combining notions of the normalization of taboo sexual subjectivities through mediated contexts with lens of gender performativity, we demonstrate how transgender subjectivities are presented to a mainstream audience via such mediated choices, but also how Bono welds some agency to resist such normalization through his live performances. Bono’s appearance on DWTS stands as an important step toward acceptance of transgendered persons in mainstream society, however through a neutered, sex-free rhetoric as projected by the mediated portions of the show, his appearance is not without controversy. Additionally, we posit that Bono represents a transnormativity of a White, upper-class postoperative heterosexual male, which others all transgendered persons who fall outside of those hegemonic parallels of safe subjectivities.
Keywords: Bibliographie; Nettoyer

Q&A: Veteran Music Video Director Diane Martel on Her Controversial Videos for Robin Thicke and Miley Cyrus - Ducker, Eric (Grantland, 2013)
Heads up: NSFW videos and websites are occasionally linked to throughout this post, so watch who’s watching your monitor. Robin Thicke’s “Blurred Lines” and Miley Cyrus’s “We Can’t Stop…

Why Music Matters - Hesmondhalgh, David (John Wiley & Sons, 2013)
Listen to David Hesmondhalgh discuss the arguments at the core of 'Why Music Matters' with Laurie Taylor on BBC Radio 4's Thinking Allowed here. In what ways might music enrich the lives of people and of societies? What prevents it from doing so? Why Music Matters explores the role of music in our lives, and investigates the social and political significance of music in modern societies. First book of its kind to explore music through a variety of theories and approaches and unite these theories using one authoritative voice Combines a broad yet theoretically sophisticated approach to music and society with real clarity and accessibility A historically and sociologically informed understanding of music in relation to questions of social power and inequality By drawing on both popular and academic talk about a range of musical forms and practices, readers will engage with a wide musical terrain and a wealth of case studies
Google-Books-ID: lDL4rKLCHmgC
Keywords: Music / General; Music / History & Criticism

Looking for Something New: The Provision of Popular Music Studies Degrees in the UK - Cloonan, Martin; Hulstedt, Lauren (IASPM Journal, 2013)
This article reports the findings of some commissioned research, which was conducted by the authors in 2012. The research sought to examine the extent of Popular Music Studies (PMS) undergraduate programmes in the United Kingdom, determine their key differences, report the findings and make recommendations to the funders about its future policies for PMS practitioners. We report our findings and the implications for PMS practitioners.
Number: 2
Keywords: Popular Music; Teaching; UK; Undergradute

Dark Side of the Tune: Popular Music and Violence - Johnson, Professor Bruce; Cloonan, Professor Martin (Ashgate Publishing, Ltd., 2013)
Written against the academically dominant but simplistic romanticization of popular music as a positive force, this book focuses on the 'dark side' of the subject. It is a pioneering examination of the ways in which popular music has been deployed in association with violence, ranging from what appears to be an incidental relationship, to one in which music is explicitly applied as an instrument of violence. A preliminary overview of the physiological and cognitive foundations of sounding/hearing which are distinctive within the sensorium, discloses in particular their potential for organic and psychic violence. The study then elaborates working definitions of key terms (including the vexed idea of the 'popular') for the purposes of this investigation, and provides a historical survey of examples of the nexus between music and violence, from (pre)Biblical times to the late nineteenth century.The second half of the book concentrates on the modern era, marked in this case by the emergence of technologies by which music can be electronically augmented, generated, and disseminated, beginning with the advent of sound recording from the 1870s, and proceeding to audio-internet and other contemporary audio-technologies. Johnson and Cloonan argue that these technologies have transformed the potential of music to mediate cultural confrontations from the local to the global, particularly through violence. The authors present a taxonomy of case histories in the connection between popular music and violence, through increasingly intense forms of that relationship, culminating in the topical examples of music and torture, including those in Bosnia, Darfur, and by US forces in Iraq and Guantánamo Bay. This, however, is not simply a succession of data, but an argumentative synthesis. Thus, the final section debates the implications of this nexus both for popular music studies itself, and also in cultural policy and regulation, the ethics of citizenship, and arguments about human rights.
Keywords: Music / Ethnomusicology; Music / Instruction & Study / Theory

The Continuum of Sexual Violence: Women’s Accounts of Victimization in Urban Nightlife - Kavanaugh, Philip R. (Feminist Criminology, 2013)
Despite the fact that a substantial amount of research has been conducted on sexual victimization among youth and young adults with active night lives, few of these studies have provided an analysis of the varied types of victimization that have occurred. I attempt to fill this gap with a qualitative analysis of women’s accounts of sexual victimization. Based on the substantive content of these women’s accounts, a three-part typology was generated, comprised of: (a) competing definitions of the situation, (b) opportunistic predation, and (c) involuntary incapacitation. Implications of the findings are discussed.
Publisher: SAGE Publications
Keywords: accounts; sexual assault; sexual victimization; unwanted sexual contact

Sexual Orientation & Gender Identity Diversity in Entertainment: Experiences & Perspectives of SAG-AFTRA Members - Badgett, M.V. Lee; Herman, Jody L. (SAG-AFTRA et The Williams Institute, 2013)
Keywords: Bibliographie; Nettoyer; Raphaël

Music, Style, and Aging: Growing Old Disgracefully? - Bennett, Andy (Temple University Press, 2013)
The image of the aging rock-and-roller is not just Paul McCartney and Mick Jagger on stage in their sixties. In his timely book Music, Style, and Aging , cultural sociologist Andy Bennett explains how people move on from youth and effectively grow older with popular music.For many aging followers of rock, punk, and other contemporary popular genres, music is ingrained in their identities. Its meaning is highly personal and intertwined with the individual's biographical development. Bennett studies these fans and how they have changed over time–through fashions, hairstyles, body modification, career paths, political orientations, and perceptions of and by the next generation.The significance of popular music for these fans is no longer tied exclusively to their youth. Bennett illustrates how the music? that "mattered" to most people in their youth continues to play an important role in their adult lives–a role that goes well beyond nostalgia.

Agression sexuelle : L'écrivain Maxime Roussy remis en liberté - Helmlinger, Julien (ActuaLitté, 2013)
Keywords: Bibliographie; Nettoyer

A woman's worth: Analyzing the sexual objectification of Black women in music videos - Ward, L. Monique; Rivadeneyra, Rocio; Thomas, Khia; Day, Kyla; Epstein, Marina (The sexualization of girls and girlhood: Causes, consequences, and resistance, 2013)
One arena where images of sexually objectified women are especially prevalent is the world of music videos. Music videos represent an important area of study, both because of their popularity with younger viewers (Ashby & Rich, 2005) and because love and sex predominate as themes (Andsager & Roe, 1999; Arnett, 2002). What we seek to do here is to take a closer look at the nature and impact of the portrayal of women in music videos, focusing, in particular, on sexually objectifying images. How frequently do objectifying images occur? What messages about femininity do these images convey to girls? What is their demonstrated impact on girls and young women? Given the current popularity of rap and hip-hop music, we focus our attention on their portrayals of African American women. We address these issues via four pathways. First, we summarize findings from existing research concerning the nature of gender portrayals in music videos. Second, we turn our attention to African American artists and summarize findings about the images of black women in music videos. Third, we present new data from an analysis we conducted of the sexual content in black music videos, providing both quantitative and thematic analyses. Finally, we summarize findings about the demonstrated impact of music video exposure on young viewers' gender beliefs and body image concerns. (PsycInfo Database Record (c) 2022 APA, all rights reserved)
Keywords: Blacks; Human Females; Music; Myriam; Objectification; Sex Roles

Sex and the City: Exploring Young Women's Perceptions and Experiences of Unwanted Sexual Attention in Licensed Venues - Fileborn, Bianca (Current Issues in Criminal Justice, 2012)
Recent research has highlighted the need to explore how specific social contexts influence the occurrence of sexual violence and sexually harassing behaviours. This article considers the occurrence of unwanted sexual attention towards young women within the social context of licensed venues in Melbourne, Victoria. Using focus group data from a small qualitative study, three ‘characteristics’ of unwanted sexual attention are considered: the forms this behaviour takes and how it impacts young women; the nature of the relationship between victim and perpetrator; and the role of venue culture in facilitating this behaviour. It is argued throughout this article that an intersection of broader social norms and the specific social norms and cultural mores of licensed venues creates a social environment that can facilitate the occurrence of unwanted sexual attention, and that restrains the ways in which young women are able to respond to these experiences.
Keywords: Camille

Democratising the popular: the case of pop music in France and Britain - Looseley, David L. (International Journal of Cultural Policy, 2012)
The article represents the second phase of a comparative project on French and British cultural policy. The project's guiding hypothesis is that conceptualisations of the popular have been a crucial driver of policy change in France and Britain, raising complex issues about the nature of cultural democracy. The second phase, including this article, takes pop music as a case study for that hypothesis. The article explores three major issues. It asks how and why, in their attempts to rethink cultural democracy for the twenty-first century, French and British policy agencies have recognised pop music as a ‘democratic' form worthy of state support. It critically examines some of the theoretical issues this has raised, comparing and contrasting the ways in which the two national policy sets have variously represented pop as having symbolic, economic and social meanings. And it argues that what has been less adequately addressed is its aesthetic meaning.
Publisher: Routledge _eprint: https://doi.org/10.1080/10286632.2012.718917
Keywords: France and the UK; cultural democracy; pop music

Beyond the Dance Floor: Female DJs, Technology and Electronic Dance Music Culture - Farrugia, Rebekah (Intellect Books, 2012)
A pathbreaking study of the women who create electronic dance music, Beyond the Dance Floor focuses on the largely neglected relationship between these women and the conceptions of gender and technology that continue to inform the male-dominated culture surrounding electronic music. In this volume, Rebekah Farrugia explores a number of important issues, including the politics of identity and representation, the bonds formed by women within the DJ community and the role female DJs and producers play in this dance music culture as well as in the larger public sphere. Though Farrugia primarily focuses on women's relationship to music-related technologies – including vinyl, mp3s and digital production software – she also deftly extends her argument to the strategic use of the Internet and web design skills for purposes tied to publicity, networking and music distribution.
Google-Books-ID: L7qrDwAAQBAJ
Keywords: Music / Genres & Styles / Electronic; Performing Arts / Dance / General; Social Science / Popular Culture; Social Science / Women's Studies; Technology & Engineering / General

Don't Act, Don't Tell: Discrimination Based on Gender Nonconformity in the Entertainment Industry and the Clinical Setting - O’Connell, Mark (Journal of Gay & Lesbian Mental Health, 2012)
The author describes anti-homosexual attitudes in the entertainment industry. Effeminate male actors generally have a hard time being cast, whether for gay or straight roles. Attitudes in the performing arts mirror those in society as a whole. Case reports are interspersed in the discussion to illustrate the points.
Publisher: Routledge _eprint: https://doi.org/10.1080/19359705.2012.658013
Keywords: Bibliographie; Nettoyer; Raphaël; acting; anti-gay; discrimination; gender nonconformity; homophobia; performing arts

The Expansion of Punk Rock: Riot Grrrl Challenges to Gender Power Relations in British Indie Music Subcultures - DOWNES, JULIA (Women's Studies, 2012)
Publisher: Routledge _eprint: https://doi.org/10.1080/00497878.2012.636572

Black Women and Black Men in Hip Hop Music: Misogyny, Violence and the Negotiation of (White-Owned) Space - Rebollo-Gil, Guillermo; Moras, Amanda (Sociology Faculty Publications, 2012)

'Rock On': Women, ageing and popular music - Jennings, R.; Gardner, Abigail ('Rock On': Women, Ageing and Popular Music, 2012)
For female pop stars, whose star bodies and star performances are undisputedly the objects of a sexualized external gaze, the process of ageing in public poses particular challenges. Taking a broadly feminist perspective, 'Rock On': women, ageing and popular music shifts popular music studies in a new direction. Focussing on British, American and Latina women performers and ageing, the collection investigates the cultural work performed by artists such as Shirley Bassey, Petula Clark, Madonna, Celia Cruz, Grace Jones and Courtney Love. The study crosses generations of performers and audiences enabling an examination of changing socio-historical contexts and an exploration of the relationships at play between performance strategies, star persona and the popular music press. For instance, the strategies employed by Madonna and Grace Jones to engage with the processes and issues related to public ageing are not the same as those employed by Courtney Love or Celia Cruz. The essays in this insightful collection reflect on the ways that artists and fans destabilise both the linear trajectories and the compelling weight of expectations regarding ageing by employing different modalities of resistance through persona re-invention, nostalgia, postmodern intertextuality and even early death as the ultimate denial of age.

Workplace Sexual Harassment 30 Years on: A Review of the Literature - McDonald, Paula (International Journal of Management Reviews, 2012)
Despite its proscription in legal jurisdictions around the world, workplace sexual harassment (SH) continues to be experienced by many women and some men in a variety of organizational settings. The aims of this review article are threefold: first, with a focus on workplace SH as it pertains to management and organizations, to synthesize the accumulated state of knowledge in the field; second, to evaluate this evidence, highlighting competing perspectives; and third, to canvass areas in need of further investigation. Variously ascribed through individual (psychological or legal consciousness) frameworks, sociocultural explanations and organizational perspectives, research consistently demonstrates that, like other forms of sexual violence, individuals who experience workplace SH suffer significant psychological, health- and job-related consequences. Yet they often do not make formal complaints through internal organizational procedures or to outside bodies. Laws, structural reforms and policy initiatives have had some success in raising awareness of the problem and have shaped rules and norms in the employment context. However, there is an imperative to target further workplace actions to effectively prevent and respond to SH.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/j.1468-2370.2011.00300.x
Keywords: Bibliographie; Nettoyer

The Lost Women of Rock Music: Female Musicians of the Punk Era - Reddington, Helen (Equinox Pub., 2012)
In the late 1970s and early 1980s a new phenomenon emerged in UK popular music - female guitarists, bass-players, keyboard-players and drummers began playing in bands. Before this time, women's presence in rock bands, with a few notable exceptions, had always been as vocalists. This sudden influx of female musicians into the male domain of rock music was brought about by the enabling ethic of punk rock ('anybody can do it ') and by the impact of the Sex Discrimination Act. With the demise of the punk scene, interest in these musicians evaporated and other priorities became important to music audiences. This book investigates the social and commercial reasons why these women became lost from the rock music record, and rewrites this period of popular music history. In addition to a wealth of original interview material with key protagonists, including the late John Peel, Geoff Travis, The Raincoats and Poison Girls, this new edition has been updated to include interviews with members of Birmingham-based band The Au Pairs, Leeds-based band Delta 5 and Viv Albertine of The Slits. Lucy Whitman (aka Lucy Toothpaste), who started the fanzine Jolt and later wrote for Spare Rib, also provides enlightening words on the relationship between female punk band members and feminism. The author also draws on her own experience as bass-player in a punk band.
Google-Books-ID: blSWuAAACAAJ
Keywords: Music / Genres & Styles / Punk; Music / History & Criticism; Social Science / Women's Studies

Notions of popular culture in cultural policy: a comparative history of France and Britain - Looseley, David (International Journal of Cultural Policy, 2011)
The Devlin and Hoyle report, Committing to culture: arts funding in France and Britain, argues that the cultural policies of these two European neighbours have been steadily converging since the mid‐1990s but that their social and economic contexts are now quite different (e.g. youth unemployment, GDP, disposable income). The paper addresses this convergence‐within‐divergence by comparing how policy discourses have conceptualised popular culture in the two countries. It investigates the hypothesis that, in both, an engagement with popular culture has in fact been an important driver of change, albeit at different times and with different taxonomies. And it asks what light this comparison might shed on cultural policy thinking in the twenty‐first century.
Publisher: Routledge _eprint: https://doi.org/10.1080/10286632.2010.541907
Keywords: France; UK; cultural policy; history; popular culture

‘Guys! Stop Doing It!’: Young Women's Adoption and Rejection of Safety Advice when Socializing in Bars, Pubs and Clubs - Brooks, Oona (The British Journal of Criminology, 2011)
Concern about the increase in alcohol consumption amongst young women, drink spiking and drug-assisted sexual assault have culminated in a renewed focus on safety advice for young women. This paper examines young women's responses to safety advice, and their associated safety behaviours, by drawing upon interview and focus group data from a qualitative study with 35 young women (18–25 years) in relation to their safety in bars, pubs and clubs. The findings reveal that young women's behaviours were complex and contradictory in that they resisted, adopted and transgressed recommended safety behaviours. This raises interesting questions about both the practical and the theoretical implications of contemporary safety campaigns, challenging the prevailing focus on women's behaviour and the gendered discourse invoked by such campaigns.

Negotiating the gay male stereotype in ballet and modern dance - Polasek, Katherine M.; Roper, Emily A. (Research in Dance Education, 2011)
Dance, ballet and modern in particular, is culturally defined as a feminine activity in the United States. The purpose of the present study was to examine the experiences of professional male modern and ballet dancers in the United States. Semi-structured interviews were conducted with 12 current professional ballet and modern dancers. We examined the ways in which the dancers initially became involved in dance, any support or opposition they may have confronted, and the ways in which they negotiated the stereotypical assumptions surrounding men’s involvement in dance. Four emergent themes are discussed: (1) exposure to and entrance into dance; (2) the gay stereotype; (3) negotiating the gay stereotype; and (4) homophobia within the dance community. The social significance of this study is rooted in the ways in which our culture constructs gender, the body, and movement, restricting both males and females from using and exploring their bodies in ways not deemed gender-appropriate. Attention is also given to the ways in which we can create and nurture meaningful experiences for a greater number of individuals.
Keywords: Bibliographie; Nettoyer; gay men; homophobia; male dancers; masculinity

A Safe Education for All: Recognizing and Stemming Harassment in Music Classes and Ensembles - Carter, Bruce Allen (Music Educators Journal, 2011)
This article addresses the pervasiveness of harassment in schools in the United States and presents ways to recognize and stem bullying in music classrooms. Music educators are in a unique position to recognize atypical behaviors in their students. Music educators who teach middle and high school ensembles often retain the same students in their classrooms over the course of many years. Because of the unique nature of the ensemble experience, coupled with the opportunity for extended instruction, music teachers can closely monitor the well-being of their students. However, music teachers should understand how difficult it may be for students who have been harassed to come forward with information about harassment. Sometimes harassment is overt and easy to recognize (e.g., name-calling, inappropriate gestures, graffiti). However, harassment can also occur in contexts that are not readily recognized but are just as hurtful. When students observe teachers taking a stand against bullying and harassment, they recognize the intention for a safe classroom. When students feel safe, they are more likely to ask questions and engage in class in dynamic and meaningful ways—both musically and nonmusically. Only when students feel safe can they learn. Music teachers need to gain a further understanding of various forms of harassment and further consider their role in creating a welcoming and secure environment.
Publisher: SAGE Publications Inc
Keywords: Bullying; Harassment; Music classrooms; Myriam

Attouchements sexuels sur une élève : Romuald Pavy plaide coupable (Radio-Canada, 2011)
Le professeur de danse Romuald Pavy a plaidé coupable mardi matin à des accusations d'attouchements sexuels sur l'une de ses élèves.
Publisher: Radio-Canada.ca
Keywords: Bibliographie; Nettoyer

Music festival sponsorship: between commerce and carnival - Anderton, Chris (Arts Marketing: An International Journal, 2011)
Purpose – This paper aims to examine the cultural heritage of outdoor rock and pop music festivals in Britain since the mid‐1960s, and relates it to developments in, and critiques of, corporate sponsorship in the contemporary music festival sector. Design/methodology/approach – The paper uses extant research materials to construct an account of British music festival history since the mid‐1960s. It then draws upon Bakhtin's concept of the carnivalesque and the literature on sponsorship, experiential marketing and branding, in order to understand critiques of corporate sponsorship and the changing nature of the sector. Findings – Outdoor rock and pop music festivals were dominated by the ideologies of a “countercultural carnivalesque” from the late 1960s until the mid‐1990s. In the 1990s, changes in legislation began a process of professionalization, corporatization, and a reliance on brand sponsorships. Two broad trajectories are identified within the contemporary sector: one is strongly rooted in the heritage of the countercultural carnivalesque, while the other is more overtly commercial. Research limitations/implications – It is argued that experiential marketing and brand activation are key methods for achieving a balance between the competing aspects of commerce and carnival. Hence, festival organisers and sponsors need to understand the history of the sector and of their own events and attendees in order to use corporate sponsorship more effectively. Originality/value – This paper adds historical and theoretical depth to the debate between commerce and carnival within the music festival sector, and makes connections between cultural theory and the literature on sponsorship and branding.
Publisher: Emerald Group Publishing Limited
Keywords: Bakhtin; Branding; Carnivalesque; Counterculture; Music festivals; Sponsorship; United Kingdom

Popular Music and the State in the UK. Culture, Trade or Industry? by Martin Cloonan - Laing, Dave (Popular Music, 2011)

Grunge, Riot Grrrl and the Forgetting of Women in Popular Culture - Strong, C. (2011)
Semantic Scholar extracted view of "Grunge, Riot Grrrl and the Forgetting of Women in Popular Culture" by C. Strong

Domestic and Sexual Violence and Abuse: Tackling the Health and Mental Health Effects - Itzin, Catherine; Taket, Ann; Barter-Godfrey, Sarah (Routledge, 2010)
Domestic violence, childhood sexual abuse, rape and sexual assault, and sexual exploitation through prostitution, pornography and trafficking can have many significant adverse impacts on a survivor’s health and wellbeing, in the short, medium and long-term. Taking a life-course approach, the book explores what is known about appropriate treatment responses to those who have experienced, and those who perpetrate, domestic and sexual violence and abuse. The book also examines key factors that are important in understanding how and why different groups experience heightened risks of domestic and sexual violence and abuse, namely: gender and sexuality; race and culture; disability; and abuse by professionals. Drawing together results from specially commissioned research, the views of experts by experience, experts by profession and the published research literature, the book argues that sufficient is already known to delineate an appropriate public health framework, encompassing primary, secondary and tertiary prevention, to successfully tackle the important public health issue represented by domestic and sexual violence and abuse. Domestic and Sexual Violence and Abuse equips health and social care professionals and services to identify and respond to the needs of affected individuals with a view to the prevention and early intervention.
Google-Books-ID: K3peBwAAQBAJ
Keywords: FAMILY & RELATIONSHIPS; Family & Relationships / Abuse / Child Abuse; Family & Relationships / Abuse / General; Health & Fitness / Women's Health; Medical / Allied Health Services / General; Medical / Health Care Delivery; Psychology / Mental Health; Social Science / Sexual Abuse & Harassment; Social Science / Social Work; Social Science / Violence in Society

Music Education in the 21st Century in the United Kingdom: Achievements, Analysis and Aspirations - Hallam, Susan; Creech, Andrea Ed (Institute of Education - London, 2010)
The landscape of music education in the UK is constantly shifting and developing. This book provides a timely and unique overview of this restless sector by considering the achievements of music education, analysing its current performance and setting out aspirations for the future. "Music Education in the 21st Century in the United Kingdom" addresses the power of music to influence and change human behaviour, analyses current and future issues in music education and casts a spotlight on particular areas of education, including early years, the primary school, the secondary school, further education, universities and conservatoires, music services, the music studio and the role of music leaders and community musicians. Written by experts in the field of music education, the book provides an authoritative account of the current status of music education in the UK. While essential to understand the current and future context in the UK, the book will be invaluable to those involved in music education internationally, as it includes chapters on the provision of music education for all children, listening, the role of singing, playing an instrument, creativity, the role of technology, issues of performance and assessment, learning through the lifespan and the initial and ongoing education of music teachers. It also includes a range of case study examples and evaluations of practice. The book is a landmark publication in the field of music education and will be essential reading for policy-makers, practitioners, music students, trainee music teachers and those who provide music services in the UK and internationally. This book contains three parts. Part I, "Introduction", contains: (1) The power of music: its impact on the intellectual, personal and social development of children and young people (Susan Hallam); and (2) Contextualising music education in the UK (Pauline Adams, Hilary McQueen, and Susan Hallam). Part 2, "Current Issues in Music Education", contains: (3) Music for all (Graham Welch and Adam Ockelford); (4) Listening (Susan Hallam); (5) The role of singing (Jo Saunders, Maria Varvarigou and Graham Welch); (6) Learning to play an instrument (Susan Hallam and Andrea Creech); (7) Creativity (Susan Hallam and Lynne Rogers); (8) The role of technology (Evangelos Himonides and Ross Purves); (9) Issues of assessment and performance (Ioulia Papageorgi and Susan Hallam); (10) Learning through life (Hilary McQueen and Maria Varvarigou); and (11) The initial and ongoing education of music teachers (Colin Durrant and Kate Laurence). Part 3, "Contexts of Learning", contains: (12) Music in the early years (Andrea Creech and Jessica Ellison); (13) Music in the primary school (Jessica Ellison and Andrea Creech); (14) Music in the secondary school (Hilary McQueen and Susan Hallam); (15) Music in further education colleges (John Conlon and Lynne Rogers); (16) Music in universities and conservatoires (Helena Gaunt and Ioulia Papageorgi); (17) Music Services (Lynne Rogers and Susan Hallam); (18) The music studio (Andrea Creech); (19) The role of music leaders and community musicians (Andrea Creech); and (20) Where now? (Susan Hallam and Andrea Creech). This book also contains: Acknowledgements; Preface; Notes on contributors; and Index.
Publication Title: Institute of Education - London
Keywords: Adult Education; Creativity; Early Childhood Education; Educational Trends; Elementary Education; Evaluation; Foreign Countries; Futures (of Society); Higher Education; Individual Development; Inservice Teacher Education; Intellectual Development; Leaders; Lifelong Learning; Listening; Music Education; Music Teachers; Musical Instruments; Musicians; Performance; Preservice Teacher Education; Secondary Education; Singing; Social Development; Technology Uses in Education

“Yes, I Do but Not with You”: Qualitative Analyses of Sexual/romantic Overture-Related Aggression in Bars and Clubs - Graham, Kathryn; Wells, Samantha; Bernards, Sharon; Dennison, Susan (Contemporary Drug Problems, 2010)
Assaultive and aggressive behaviors related to sexual overtures are common in commercial drinking establishments (bars, pubs, and clubs). In this article, we examined the thematic content of 251 incidents of verbal and physical aggression related to sexual/romantic overtures documented by researcher-observers in a study of Toronto bars and clubs. Aggression was examined as it emerged in the following stages of the social interaction process: (a) sexual/romantic overtures that began aggressively; (b) initiators of sexual/romantic overtures who became aggressive later in the social interaction process; (c) aggression by targets of overtures; and (d) aggression by third parties. From these thematic analyses we identify the distinctions between predatory and genuine overtures and explore the potential role of the effects of alcohol.
Publisher: SAGE Publications Inc

Comparative Gender and Institutions: Directions for Research - Chappell, Louise (Perspectives on Politics, 2010)
A comparative politics of gender offers an opportunity to consider in detail the operation of gender within political institutions. As such, it contributes to a deeper understanding of the roles and experiences of men and women within political institutions, of the policies, laws and norms that are the outcomes of these institutions, and of the relationship between these institutions and social actors. This essay proposes a multi-directional strategy for undertaking comparative gender and institutional research that includes taking account of similarities and differences within and across states, between states and international institutions, across space as well as across time. It argues that through this research strategy it is possible to gain a more nuanced understanding of gender processes and outcomes, which is valuable to those working both inside and outside political institutions to advance a women's equality agenda.
Publisher: Cambridge University Press

Managing Physical and Sexual Assault Risk in Urban Nightlife: Individual- and Environmental-Level Influences - Kavanaugh, Philip R.; Anderson, Tammy L. (Deviant Behavior, 2009)
In this article we use interview and direct observation data to examine the experiences of young people in two Philadelphia nightlife scenes, and the ways in which they manage risk of physical and sexual assault. Our analysis reveals several environmental-level factors that shape risk exposure, as well as a number of individual-level tactics used to manage risk. Our observations are discussed in terms of their implications for developing a risk management framework that accounts for the role of individual- and environmental-level factors in shaping victimization.
Publisher: Routledge _eprint: https://doi.org/10.1080/01639620902854639

The Promise and Pitfalls of Gender Mainstreaming - Sainsbury, Diane; Bergqvist, Christina (International Feminist Journal of Politics, 2009)
This article examines gender mainstreaming in Sweden, which is an interesting case because several favorable conditions make its implementation likely. It addresses two main questions: (1) to what extent has gender mainstreaming been implemented and (2) what are the consequences? The article first discusses the pros and cons of gender mainstreaming as reflected in the international feminist debate. It then briefly describes the favorable conditions of the Swedish case and subsequently maps out the introduction of gender mainstreaming since 1994, focusing on the process and its politics. It concludes with a discussion of the Swedish experience in terms of the promise and pitfalls of gender mainstreaming identified in the feminist debate and the implications of the Swedish case for feminist theorizing on gender mainstreaming.
Publisher: Routledge _eprint: https://doi.org/10.1080/14616740902789575
Keywords: Sweden; feminist theory; gender equality policies; gender mainstreaming; gender politics

The Aftermath of Feminism: Gender, Culture and Social Change - McRobbie, Angela (SAGE Publications, 2009)
Congratulations to Dr. McRobbie! This book has been named to the list of books for the 2009 Critics Choice Book Award of the American Educational Studies Association (AESA).These essays show Angela McRobbie reflecting on a range of issues which have political consequence for women, particularly young women, in a context where it is frequently assumed that progress has been made in the last 30 years, and that with gender issues now 'mainstreamed' in cultural and social life, the moment of feminism per se is now passed. McRobbie trenchantly argues that it is precisely on these grounds that invidious forms of gender -re-stabilisation are able to be re-established. Consumer culture, she argues, encroaches on the terrain of so called female freedom, appears supportive of female success only to tie women into new post-feminist neurotic dependencies. These nine essays span a wide range of topics, including - the UK government's 'new sexual contract' to young women, - popular TV makeover programmes, - feminist theories of backlash and the 'undoing' of sexual politics, - feminism in a global frame- the 'illegible rage' underlying contemporary femininities.
Google-Books-ID: jmMREuksN10C
Keywords: Social Science / Essays; Social Science / Feminism & Feminist Theory; Social Science / Sociology / General; Social Science / Women's Studies

Loyalty and Longevity in Audience Listening: Investigating Experiences of Attendance at a Chamber Music Festival - Pitts, Stephanie E.; Spencer, Christopher P. (Music and Letters, 2008)
There is currently much concern among arts organizations and their marketing departments that audiences for classical music are in decline, yet there has been little investigation so far of the experiences of long-term listeners that might yield insights into audience development and retention. This paper presents a case study of the Music in the Round chamber music festival, conducted over a three-year period that included the retirement of the host string quartet, the appointment of a new resident ensemble, and associated changes in audience attitudes and priorities. Questionnaire and interview data revealed the challenges faced by audience members in shifting their loyalty to a new ensemble and reappraising their own listening habits and stamina. The interaction between individual listening and collective membership of an audience is discussed, and the potential considered for understanding classical concert-goers as ‘fans’ or ‘consumers’.

The Experiences of Canadian Women in Popular Music: “even on the worst sick no gas freezing canadian middle of january rockie mountain or halifax breakdown there is nothing better to do for a living” - MacKay, Robbie (Université Queen’s, 2008)
Keywords: Bibliographie; Nettoyer

[POSITIF: à ajouter ?|The Social Construction of Female Sexuality in a Sexualized Work Environment (SWE): The Case of a Comedy Club - Philaretou, Andreas G.; Young, Christi L. (Sexual Addiction & Compulsivity, 2007)
This qualitative investigation seeks to identify the sociocultural determinants and psychoemotional ramifications of essentialist gender scripting on female employees in a sexualized work environment (SWE), such as a comedy club. Sexualized work environments incorporate work and sexuality and exist on a continuum according to the frequency and intensity of the sexual economic exchange that takes place within them. In this study, interviews were conducted with 13 female employees at a comedy club in Southwest Michigan to explore the social construction of female sexuality in such an environment.
Publisher: Routledge _eprint: https://doi.org/10.1080/10720160601150139
Keywords: Sophie-Anne

The Girl Hunt: Urban Nightlife and the Performance of Masculinity as Collective Activity - Grazian, David (Symbolic Interaction, 2007)
The purpose of this article is to document the collective nature of gender performance and sexual pursuit, activities typically associated with individual rather than group behavior. Drawing on narrative accounts, I analyze how young heterosexual male students employ the power of collective rituals of homosociality to perform sexual competence and masculine identity by “girl hunting” in the context of urban nightlife. These rituals are designed to reinforce dominant sexual myths and expectations of masculine behavior, boost confidence in one's performance of masculinity and heterosexual power, and assist in the performance of masculinity in the presence of women. This analysis illustrates how contemporary courtship rituals operate as collective strategies of impression management that men perform not only for women but for other men. In doing so, interaction rituals associated with the girl hunt reproduce structures of inequality within as well as across the socially constructed gender divide between women and men.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1525/si.2007.30.2.221

‘Loaded’: indie guitar rock, canonism, white masculinities - Bannister, Matthew (Popular Music, 2006)
Indie alternative rock in the 1980s is often presented as authentically autonomous, produced in local scenes, uncaptured by ideology, free of commercial pressures, but also of high culture elitism. In claiming that the music is avant-garde, postmodern and subversive, such accounts simplify indie's historical, social and cultural context. Indie did not simply arise organically out of developing postpunk music networks, but was shaped by media, and was not just collective, but also stratified, hierarchical and traditional. Canon (articulated through practices of archivalism and connoisseurship) is a key means of stratification within indie scenes, produced by and serving particular social and cultural needs for dominant social groups (journalists, scenemakers, tastemakers, etc.). These groups and individuals were mainly masculine, and thus gender in indie scenes is an important means for deconstructing the discourse of indie independence. I suggest re-envisioning indie as a history of record collectors, emphasising the importance of rock ‘tradition’, of male rock ‘intellectuals’, second-hand record shops, and of an alternative canon as a form of pedagogy. I also consider such activities as models of rational organisation and points of symbolic identification.
Publisher: Cambridge University Press

The Study of Gender in Culture - Cragin, Becca; Simonds, Wendy (Handbook of the Sociology of Gender, 2006)
Keywords: Critical Dialogue; Cultural Study; Feminist Study; Popular Culture; Soap Opera

Sexism and misogyny in American hip-hop culture - Larsen, Jane Kathrine (2006)
The proliferation of hip-hop culture today is so great that we may speak of a modern-day pop-cultural phenomenon. This phenomenon has found its way from the ghetto areas in the Bronx to white suburbia in the U.S. and Europe over the last thirty years. The specific subject for my study is the overt sexism that is present in this culture. Sexism can take on a variety of forms and expressions, as there are various degrees and definitions of this concept. Hence, my aim is to locate some of these definitions and relate them to hip-hop’s expression. The development from a black sub-culture to an immensely successful genre in music is of great interest to my study, in terms of hip-hop as a pop-cultural and sociological phenomenon. There are also cultural, gender, and racial concerns to be considered in this respect, and my account of these includes an exploration of the time and place for the birth and development of hip-hop. The extent of sexism, and even outright misogyny, in hip-hop today is so pervasive, that protests have started to come from every direction of America’s pop-cultural, feminist, and academic sphere. The sociological and pop-cultural factors that are present in this discussion, is related to the topic of gender roles and relationships in African American culture. In my discussion on the hip-hop industry’s responsibility for distributing these negative depictions of women in hip-hop videos and lyrics, I have included some examples from studies that focus on the racial stereotypes in connection to gangsta-rap. The concept of image and authenticity is important in this respect, and there is a level of deliberate marketing strategies behind the lifestyle-oriented aliases of the rap artists. Since hip-hop and rap music traditionally have been overwhelmingly masculine expressions, it is necessary to take a look at the role of female artists within the hip-hop community. In this respect, I find that women have traditionally been rejected or hindered to participate in hip-hop’s brotherhood. Women in hip-hop have thus either tried to make careers for themselves, or adapt into the mass-marketed and male-defined stereotype that in many ways relate to the sexist images that are currently so pervasive. The sexist attitudes represent a point of view that I believe is derived from popularised representations in the media. These representations tally well with the already existing prejudiced opinions that have been created in terms of race discrimination and patriarchal values. Part of the problem with these representations is the lack of alternative images. If there are no counter-images that will speak against the existing sexist depictions, then there will be no progress in terms of addressing sexism directly. The constructed images of African Americans that the media are chiefly responsible for distributing, are what many non-black citizens believe to be the truth about black people. As long as people do not interact socially across ethnic borders, these representations will continue to circulate. In hip-hop culture, this is still ubiquitous in terms of the stereotyping of race. An interesting, and perhaps surprising aspect to some, is the fact that most of hip-hop’s buying audience is white. The negative stereotyping in hip-hop which was initiated by the gangsta-era, was displayed mainly by African American men who acted as criminal gangsters (hence the name), and who lived up to their role as “bad”, thus confirming the stereotyped conception that many non-blacks had of black people. The badness is then articulated within hip-hop’s boundaries through violence and as a glorification of the “thug life” by the men, whereas for women it is commonly expressed as commodified sexuality. Contemporary hip-hop resembles the minstrel shows of the 19th century in this respect, where working class white men dressed up as plantation slaves.
Accepted: 2013-03-12T11:40:46Z
Keywords: Hip-hop culture; Myriam; Perfoming arts

La fondation de Nathalie Simard voit le jour - Radio-Canada (Radio-Canada, 2005)
« Il faut briser le silence », a déclaré Nathalie Simard lors du lancement de sa fondation qui viendra en aide aux organismes supportant les victimes de pédophilie.
Publisher: Radio-Canada.ca
Keywords: Bibliographie; Nettoyer

Véronique Cloutier condamne les gestes de son père - Radio-Canada (Radio-Canada, 2005)
Commentant pour la première fois les agressions sexuelles commises par Guy Cloutier, l'animatrice dit trouver « inacceptables » les gestes posés par son père à l'endroit de Nathalie Simard et de l'autre victime.
Keywords: Bibliographie; Nettoyer

Lesbian Lacunae: Invisible Spaces in Dance Education - Mozingo, Karen A. (Journal of Dance Education, 2005)
Recent research about sexuality and dance has begun to address the needs of gay male dancers, yet the needs of lesbian dancers have remained mostly absent from scholarly discourse. Exploring the lesbian lacunae, or invisible spaces of dance education, reveals the personal, political, and pedagogical implications of their existence within the dance community. The experiences of lesbian dancers “on the fringe” combined with new approaches to acknowledging lesbian artists and perspectives within dance history suggest the need for re-envisioning lesbian invisibility as a “liminal presence” within dance. In addition, ways dance educators can reduce the effects of heterocentrism within their institutions and celebrate the contributions of lesbian artists and educators to the field are proposed. By reconfiguring the invisibility of lesbian dancers as a liminal presence, we make visible the borders and limits of the dance profession's notions of sexuality and gender, acceptance and equality, and thereby strengthen our potential for dancing beyond them.
Publisher: Routledge _eprint: https://doi.org/10.1080/15290824.2005.10387286
Keywords: Bibliographie; Nettoyer

Briser le silence: Nathalie - Vastel, Michel (Éditions Libre Expression, 2005)
Keywords: Bibliographie; Nettoyer

Guy Cloutier écope de trois ans et demi - Radio-Canada (Radio-Canada, 2004)
Le producteur et impresario Guy Cloutier a été condamné ce matin à 42 mois de prison par le juge Robert Sansfaçon. Cloutier avait avoué en novembre avoir agressé sexuellement deux enfants pendant de nombreuses années.
Publisher: Radio-Canada.ca
Keywords: Bibliographie; Nettoyer

The Story of Jane Doe: A Book About Rape - Doe, Jane (Vintage Canada, 2004)
Keywords: Bibliographie; Nettoyer

Bouncers: Violence and Governance in the Night-time Economy - Hobbs, Dick; Hadfield, Philip; Lister, Stuart; Winlow, Simon (Oxford University Press, 2003)
"In recent years, the expansion of night-time leisure has emerged as a key indicator of post-industrial urban prosperity, attracting investment, creating employment and re-generating the built environment. These leisure economies are youth-dominated, focusing upon the sale and consumption of alcohol. Unprecedented numbers of young people now flock to town centres that are crammed with bars, pubs and clubs, and the resulting violent disorder has over-run police resources that remain geared to the drinking patterns and alcohol cultures of previous generations. Post-industrial re-structuring has spawned an increasingly complex mass of night-time leisure options through which numerous licit and illicit commercial opportunities flow. Yet, regardless of the fashionable and romantic notions of many contemporary urban theorists, it is alcohol, mass intoxication and profit rather than 'cultural regeneration,' which lies at the heart of this rapidly expanding dimension of post-industrial urbanism. Private security in the bulky form of bouncers fills the void left by the public police. These men (only 7% are women), whose activities are barely regulated by the State, are dominated by a powerful subculture rooted in routine violence and intimidation. Using ethnography, participant observation and extensive interviews with all the main players, this book charts the emergence of the bouncer as one of the most graphic symbols in the iconography of post-industrial Britain." Argumentaire de l'ouvrage.
Google-Books-ID: fTOC5gcecWYC
Keywords: Law / International

Rehearsing Heterosexuality: "Unspoken" Truths in Dance Education - Risner, Doug (Dance Research Journal, 2002)
Keywords: Bibliographie; Nettoyer

All rock and roll is homosocial: the representation of women in the British rock music press - Davies, Helen (Popular Music, 2001)
The British rock music press prides itself on its liberalism and radicalism, yet the discourses employed in music journalism exclude women from serious discussion both as musicians and as fans. In particular, the notion of credibility, which is of vital importance to the ‘serious’ rock music press, is constructed in such a way that it is almost completely unattainable for women.The most important and influential part of the British music press was until recently its two weekly music papers, Melody Maker (MM) and the New Musical Express (NME), both published by IPC magazines. The NME, launched in 1949, contains reviews, concert information and interviews with performers and describes itself as ‘a unique blend of irreverent journalism and musical expertise’ (www.ipc.co.uk). MM, which started life in 1926 as a paper for jazz musicians, had similar content but a greater emphasis on rock, as opposed to pop, music. It was relaunched in 1999 as a glossy magazine, before ceasing publication or, as IPC put it, merging with the NME, in December 2000.
Publisher: Cambridge University Press

Pretty in Punk: Girls' Gender Resistance in a Boys' Subculture - Leblanc, Lauraine (Rutgers University Press, 1999)
Pretty in Punk combines autobiography, interviews, and sophisticated analysis to create the first insider's examination of the ways punk girls resist gender roles and create strong identities.Why would an articulate, intelligent, thoughtful young women shave off most of her hair, dye the remainder green, shape it into a mohawk, and glue it onto her head? What attracts girls to male-dominated youth subcultures like the punk movement? What role does the subculture play in their perceptions of themselves, and in their self-esteem? How do girls reconcile a subcultural identity that is deliberately coded “masculine” with the demands of femininity?Research has focused on the ways media and cultural messages victimize young women, but little attention has been paid to the ways they resist these messages. In Pretty in Punk, Lauraine Leblanc examines what happens when girls ignore these cultural messages, parody ideas of beauty, and refuse to play the games of teenage femininity. She explores the origins and development of the punk subculture, the processes by which girls decide to “go punk,” patterns of resistance to gender norms, and tactics girls use to deal with violence and harassment.Pretty in Punk takes readers into the lives of girls living on the margins of contemporary culture. Drawing on interviews with 40 girls and women between the ages of 14-37, Leblanc examines the lives of her subjects, illuminating their forms of rebellion and survival. Pretty in Punk lets readers hear the voices of these women as they describe the ways their constructions of femininity—from black lipstick to slamdancing—allow them to reject damaging cultural messages and build strong identities. The price they pay for resisting femininity can be steep—girls tell of parental rejection, school expulsion, institutionalization, and harassment. Leblanc illuminates punk girls' resistance to adversity, their triumphs over tough challenges, and their work to create individual identities in a masculine world.
Google-Books-ID: m8Lz1S9v4d8C
Keywords: Family & Relationships / Life Stages / Adolescence; Social Science / Popular Culture; Social Science / Women's Studies

Vanishing in Your Face: Embodiment and Representation in Lesbian Dance Performance - Kuppers, Petra (Journal of Lesbian Studies, 1998)
Lesbian dance performance has to come to terms with the cultural invisibility of the lesbian body, and the dichotomy of traditional gender representation. This paper charts strategies for the play with the invisible, the grotesque and the liminal in the dance performance of three UK-based choreographers: Emilyn Claid, Yael Flexer and Kate Lawrence. Their performances create tension between the role and the body, between the public and the private, and it is this tension that points towards alternative representational strategies.
Publisher: Routledge _eprint: https://doi.org/10.1300/J155v02n02_04

Racial Harassment, Sexual Harassment, and the Expressive Function of Law Case - Mullender, Richard (Modern Law Review, 1998)
Keywords: Sophie-Anne

A TOP NIGHT: Social Protest, Masculinity and the Culture of Drinking Violence - TOMSEN, STEPHEN (The British Journal of Criminology, 1997)
Although a wide research literature suggests a regular connection between drinking, violence and social disorder, much doubt remains as to the actual nature and significance of this link. Some strong insights into this are provided by a dual consideration of the tie between masculine social identity and heavy group drinking, and the importance of issues of male honour in the social interaction that leads to much violent behaviour. But as well as this, information from the author's detailed ethnographic study of assaults in public drinking venues illuminates the subjective experience of participation in acts of disorder and violence. This is filtered through understandings of certain forms and aspects of popular leisure as entailing social protest and resistance to middle class morality. Although masculinist and frequently destructive, this violence is interpreted by many drinkers as providing a liberating and attractive sense of release, group pleasure and carnival.

Sexual Harassment of Women Journalists - Walsh-Childers, Kim; Chance, Jean; Herzog, Kristin (Journalism & Mass Communication Quarterly, 1996)
A survey of 227 women newspaper journalists revealed that more than 60 percent believe sexual harassment is at least somewhat a problem for women journalists; more than one-third said harassment has been at least somewhat a problem for them personally. Two-thirds experience nonphysical sexual harassment at least sometimes, and about 17 percent experience physical sexual harassment at least sometimes. News sources were the most frequent harassers, and harassment ranged from degrading comments to sexual assault._
Publisher: SAGE Publications Inc
Keywords: Journalisme; Myriam; journalism

Beyond Victim or Survivor: Sexual Violence, Identity and Feminist Theory and Practice - Kelly, Liz; Burton, Sheila; Regan, Linda (Sexualizing the Social, 1996)
Keywords: Bibliographie; Nettoyer

Cultures of Consumption: Masculinities and Social Space in Late Twentieth-century Britain - Mort, Frank (Psychology Press, 1996)
Examines the construction of images of masculinity and the effect they have on identity, sexuality and sexual politics. Influences from black and white culture are explored as well as the ironies of class, colour and sexuality.
Google-Books-ID: _TiOIhE1NeEC
Keywords: Art / Popular Culture

The Sex Revolts: Gender, Rebellion, and Rock 'n' Roll - Reynolds, Simon; Press, Joy (Harvard University Press, 1996)
Iggy Pop once said of women: "However close they come I'll always pull the rug from under them. That's where my music is made." For so long, rock 'n' roll has been fueled by this fear and loathing of the feminine. The first book to look at rock rebellion through the lens of gender, The Sex Revolts captures the paradox at rock's dark heart–the music is often most thrilling when it is most misogynist and macho. And, looking at music made by female artists, it asks: must it always be this way?Provocative and passionately argued, the book walks the edgy line between a rock fan's excitement and a critic's awareness of the music's murky undercurrents. Here are the angry young men like the Stones and Sex Pistols, cutting free from home and mother; here are the warriors and crusaders, The Clash, Public Enemy, and U2 taking refuge in a brotherhood-in-arms; and here are the would-be supermen, with their man-machine fantasies and delusions of grandeur, from Led Zeppelin and Jim Morrison to Nick Cave and gangsta rap. The authors unravel the mystical, back-to-the-womb longings of the psychedelic tradition, from Pink Floyd, Jimi Hendrix, and Van Morrison to Brian Eno, My Bloody Valentine, and ambient techno. Alongside the story of male rock, The Sex Revolts traces the secret history of female rebellion in rock: the masquerade and mystique of Kate Bush, Siouxie, and Grace Jones, the demystifiers of femininity, like the Slits and Riot Grrl, tomboy rockers like L7 and P. J. Harvey, and confessional artists like Janis Joplin, Joni Mitchell, and Courtney Love.A heady blend of music criticism, cultural studies, and gender theory by two of rock's keenest observers, The Sex Revolts is set to become the key text in the women-in-rock debate.
Google-Books-ID: Acq7ZOYd_AcC
Keywords: Music / History & Criticism

Farinelli (1994)
Keywords: Bibliographie; Nettoyer

Freedom and Outrage in Art Education - Lankford, E. Louis (Journal of Aesthetic Education, 1994)
Publisher: University of Illinois Press
Keywords: Myriam

Backlash: the undeclared war against American women - Faludi, Susan (Anchor books, 1991)
Keywords: Bibliographie; Nettoyer

Settling Accounts with Subculture: A Feminist Critique - McRobbie, Angela (Feminism and Youth Culture: From ‘Jackie’ to ‘Just Seventeen’, 1991)
Although ‘youth culture’ and the ‘sociology of youth’ — and particularly critical and Marxist perspectives on them — have been central strands in the development of cultural studies over the past fifteen years, the emphasis from the earliest work of the National Deviancy Conference (NDC) onwards has remained consistently on male youth cultural forms.1 There have been studies of the relation of male youth to class and class culture, to the machinery of the State, and to the school, community and workplace. Football has been analysed as a male sport, drinking as a male form of leisure, the law and the police as patriarchal structures concerned with young male (potential) offenders. I do not know of a study that considers, never mind prioritises, youth and the family. This failure by subcultural theorists to dislodge the male connotations of ‘youth’ inevitably poses problems for those who are involved in teaching about those questions. As they cannot use the existing texts ‘straight,’ what other options do they have?
Keywords: Class Culture; Feminist Critique; Moral Panic; Sexual Double Standard; Youth Culture

The changing role of women executives in the recording industry - Parsons, Patrick R. (Popular Music and Society, 1988)
Publisher: Routledge _eprint: https://doi.org/10.1080/03007768808591332

The Continuum of Sexual Violence - Kelly, Liz (Women, Violence and Social Control, 1987)
This chapter discusses the application of the concept of the continuum of sexual violence to research on, and discussion of, the issue of sexual violence. Two of the original aims of the research were to explore the links between the different forms of sexual violence and to investigate the idea, which arose whilst working in a refuge for battered women, that most women have experience of sexual violence in their lifetime.1 Whilst analysing the in-depth interviews carried out with women, I begin to use the concept of a continuum of sexual violence to describe the findings in the two areas.

Women and Rock Music - Harding, Deborah; Nett, Emily (Atlantis: Critical Studies in Gender, Culture & Social Justice, 1984)
Rock music is the most misogynistic and aggressive form of music currently listened to. Women's place in it since the 1950's is described and analyzed in this article. Rock music was originally a working-class male challenge to the established symbolic order. In terms of the revenue generated by the industry thirty years later, it is the most important cultural expression of popular music. The enterprise is almost exclusively male, the majority of listeners are male, and even though women singers contributed in the early 1960's, there have been only a few female performers. An analysis of feminine representations in rock music lyrics and album covers in 1981 reveals a variety of male-identified images of women. In view of the cultural context in which rock music originated and the industry developed, the recent penetration by a few more women into the industry raises questions about whether numbers will continue to increase and, even if they do, whether rock music constitutes an appropriate voice in which women can authentically express themselves.
Number: 1
Keywords: Music; Myriam; Rock Music

* Prud'homme c. Prud'homme, 2002 CSC 85 (CanLII), [2002] 4 RCS 663
Keywords: Bibliographie; Nettoyer

Agir ensemble contre les agressions à caractère sexuel (Programme Empreinte)
« Empreinte – Agir ensemble contre les agressions à caractère sexuel est un nouveau programme de prévention des agressions à caractère sexuel destiné aux jeunes de niveau secondaire, à leurs parents et au personnel scolaire. Ce programme a été développé conjointement par les professeures Manon Bergeron et Martine Hébert, du département de sexologie de l’UQAM ainsi que par le Regroupement québécois des centres d’aide et de lutte contre les agressions à caractère sexuel (RQCALACS). Ce projet se réalise avec le Service aux collectivités de l'UQAM.»
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Agression sexuelle : L'écrivain Maxime Roussy remis en liberté (ActuaLitté.com)
Arrivé menottes aux poignets en Cour du Québec, mercredi dernier, détenu depuis une semaine pour non-respect de conditions de remise en liberté, l'auteur jeunesse à succès Maxime Roussy a finalement retrouvé sa liberté, ce 13 décembre. Une décision accueillie avec soulagement par l'écrivain et sa conjointe, tandis que celui-ci fait encore face à six accusations à caractère sexuel ainsi que de leurre informatique à l'endroit d'une jeune lectrice.

Avant Coup (Avant Coup)
https://avantcoup.ca/
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Balance Ton Éditeur : “Il fallait que ça sorte” (ActuaLitté.com)
Quatre publications en l’espace d’une semaine, près de 250 abonnés constatés ce 14 avril… 1134, au 15. Balance ton éditeur est un collectif réuni pour lutter « contre le harcèlement, les discriminations et les mauvaises pratiques dans le monde de l’édition ». Mais avant toute chose, une précision d’importance : les fameuses pratiques dénoncées ne sont pas que le fait des hommes. Utile à rappeler…
Keywords: Irina

Blurred Lines: Does pop have a misogyny problem? | Complete Music Update

Brit Awards record labels face the music on unpaid interns (GOV.UK)
Major record labels involved in this year’s Brit Awards are among the latest targets of HMRC's continued crackdown on unpaid internships.

Capsule sur le GRIP, projet Spotlight - YouTube

CEHP (CEHP)
Soutenir et accompagner les organisations dans une saine gestion du harcèlement psychologique au travail
Keywords: Bibliographie; Nettoyer

chambre d'écho - Recherche Google

Committees (ACTRA Montreal)
Committees are formed of groups of ACTRA Montreal members who represent and voice the concerns of specific industry and/or social topics.

Cyberintimidation chez les adultes (CDÉACF)
Keywords: Bibliographie

Définition de l’agression sexuelle (INSPQ)
Il n’existe pas de définition universelle de l’agression sexuelle, et différentes perspectives peuvent être utilisées pour la définir. Dans toutes les formes d’agression sexuelle, une condition nécessaire est que la victime n’ait pas consenti aux gestes sexuels commis, qu’elle était incapable d’y consentir ou de les refuser, ou encore qu’elle n’avait pas l’âge de consentir.

Dialogues - Conférences - CNAC
Keywords: Sophie-Anne

Différences et inégalités de genre dans la musique au Québec (DIG! Musique Québec)
DIG! est un réseau interdisciplinaire et intersectoriel visant la mutualisation des savoirs liés aux différences et aux inégalités de genre dans la musique au Québec.
Keywords: Bibliographie; Nettoyer

Dis Son Nom - Liste officielle des abuseuses et abuseurs présumés du Québec
Keywords: Bibliographie; Nettoyer

Harcèlement sexuel dans l'édition : “Ouvrir les yeux sur cette violence” (ActuaLitté.com)
La « culture du silence », selon l'expression consacrée, prendrait-elle fin ? Le témoignage des actrices qui ont précipité la chute du producteur américain Harvey Weinstein, entraînant une libération – une libéralisation ? – de la parole. Logiquement, ce sont les réseaux sociaux qui s'en sont fait l'écho, amplifiant les messages de colère, tristesse ou de soulagement. #MeToo, autant que le plus virulent #BalanceTonPorc, ont marqué profondément, jaillissant de toutes parts, et dénonçant le harcèlement sexuel vécu sous toutes ses formes. Alors, dans l'édition ?
Keywords: Irina

Jouer sur le banc | Éditions Somme toute

Le délicat retour d’Éric Lapointe | La Presse

Les mots de trop

Médiation citoyenne (Équijustice)
Équijustice offre des services de médiation citoyenne pour toute personne qui souhaite entamer une démarche de dialogue, en marge des procédures traditionnelles. Gratuit et confidentiel, le service est accessible à tous.
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

#MeToo dans l’édition : tout le monde savait (Libération)
Plus d’une centaine de femmes travaillant dans le livre signent un texte dénonçant un climat délétère et des inégalités flagrantes. Elles demandent que les entreprises de l’édition prennent leur responsabilité.
Section: Tribunes
Keywords: Irina

Not In Our Space (Canadian Actors' Equity Association)

Nouvelle Accueil (Unison)
Unison a été formé en 2010 avec un objectif simple mais important en tête : pour s’assurer que les personnes qui composent l’industrie musicale canadienne ne soient jamais seules en période de crise. Créés par l’industrie, pour l’industrie, nous offrons des services financiers d’urgence et des conseils professionnels qui sauvent des vies et offrent un […]
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Observatoire 2024 de l'égalité entre femmes et hommes dans la culture et la communication

Paradise Abyss: The Exploration of Intersectional Feminism in Video Games - ProQuest
Explore millions of resources from scholarly journals, books, newspapers, videos and more, on the ProQuest Platform.
Keywords: Irina

Politique harcèlement » Théâtre de la LNI
Keywords: Sophie-Anne

Politique sur le respect des personnes, la prévention et l’intervention en matière de harcèlement

Politique sur le respect des personnes, la prévention et l’intervention en matière de harcèlement

Presentation foire feministe SAM (Google Docs)
« C’est juste une blague ! » : Détecter, analyser et répondre à l’humour sexiste et antiféministe au Québec Sophie-Anne Morency, doctorat en sociologie Conférence pour le Collège Montmorency

Prévention des violences à caractère sexuel en milieu festif (Scène & Sauve)
Scène & Sauve est un organisme à but non lucratif œuvrant dans la prévention des violences à caractère sexuel avant, pendant et après des événements festifs.

Prévention du harcèlement et de la violence - UNEQ
Prévention du harcèlement et de la violence L’UNEQ tient à apporter son soutien à tout·e écrivain·e qui estime avoir été victime de violence ou de harcèlement, à caractère sexuel ou non. En juillet 2020, le milieu littéraire québécois a été littéralement submergé par un mouvement rassemblant plusieurs centaines de femmes et de personnes issues de

Québec, un modèle de « safe space » ? (Livres Hebdo)
Face au #metoo qui a secoué l'édition québécoise à l'été 2020, le milieu littéraire a posé des premiers jalons garantissant des rapports exempts de harcèlement et de violences sexuelles. Une réponse rapide, organisée, qui témoigne de la longueur d'avance prise par le Québec sur les enjeux liés au féminisme et à l'inclusion. De quoi séduire les autrices, françaises notamment. Et donner des idées à la France ?

Querying Consent
Querying Consent examines the ways in which the concept of consent is used to map and regulate sexual desire, gender relationships, global positions, technological interfaces, relationships of production and consumption, and literary and artistic interactions. From philosophy to literature, psychoanalysis to the art world, the contributors to Querying Consent address the most uncomfortable questions about consent today. Grounded in theoretical explorations of the entanglement of consent and subjectivity across a range of textual, visual, multi- and digital media, Querying Consent considers the relationships between consent and agency before moving on to trace the concept’s outcomes through a range of investigations of the mutual implication of personhood and self-ownership.

Rapport de réunion des filles joueuses de la NI

Ressources harcèlement (Guilde des musiciens et musiciennes du Québec)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Ressources publicitaires | Milieux de travail respectueux dans les arts

Rudesse - Regroupement contre la violence sexuelle en improvisation | Facebook
Keywords: Sophie-Anne

Sexual harassment and violence at Australian music festivals: Reporting practices and experiences of festival attendees - Bianca Fileborn, Phillip Wadds, Stephen Tomsen, 2020

shesaid.so Montreal: Project Crescendo (shesaid.so)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

SOS violence conjugale (SOS violence conjugale)
Au service de l’ensemble de la population du Québec, SOS violence conjugale offre des services d’accueil, d’information, de sensibilisation, de soutien et de référence bilingues, gratuits, anonymes et confidentiels 24h sur 24.
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Swimming with Sharks: Sexual Predators in the Music Industry
I thought getting a job in music meant sitting in the boardroom of Columbia with Beyonce. What I encountered was much darker.

Témoigner de son agression à caractère sexuel sur Internet

The art of Jane Orleman: childhood trauma and the discourse of sexual violence
ISSN: 0958-9236

The Challenge Of Organising A Gender-Balanced Conference In The Music Industry | HuffPost UK

THE STATUS OF WOMEN IN THE CANADIAN ARTS AND CULTURAL INDUSTRIES - RESEARCH REVIEW 2010-2018

Why the #MeToo Movement Could Have Chilling Effect for Women in Music Industry (Billboard)
As allegations of sexual misconduct continue to rock the entertainment industry, lawyers predict there could be one unintended consequence: less opportunities for women in music.

Why We're Talking About Music and Mental Health This Week
Introducing a new series on Noisey.

Services - Action travail des femmes (ATF)
Depuis plus de 30 ans, ATF défend les droits des femmes en emploi et leur permet d'accéder à des postes bien rémunérés.
Keywords: Coffre à outils; À ajouter

ethique@adisq.com - ADISQ
Keywords: Coffre à outils; Dans le rapport

The Changing Roles of Female Visual Artists in Morocco - Azhar, Samir El
Female artists are actively participating in the development and growth of visual arts in Morocco. This article seeks to highlight their important contribution in the Moroccan visual arts. It deals with the access of women to the field of visual art, delineates successive categories for understanding the types of work female artists have engaged in since the independence of the country in 1956, and the challenges that these artists have been facing. It focuses on the artistic experiences of specific artists, believed to be, representative of some historical era or artistic trend. Moreover, it tries to put these artists into a cultural and historical framework to contextualize their artistic production.

Haven Helpline - Canadian Actors' Equity Association
Keywords: Coffre à outils; Dans le rapport; Sophie-Anne

LGBTQ2+ Inclusion in Canadian museums - Canadian Museums Association
Keywords: Bibliographie; Nettoyer

The Women of Publishing Say #MeToo - Deahl, Rachel; Maher, John; Milliot |, Jim (PublishersWeekly.com)
Despite its image as a bastion of liberal thinking and its unusually high percentage of female workers, the publishing industry still has a significant sexual harassment problem.
Keywords: Irina

Planning and Management for Public Health Impacts at Outdoor Music Festivals: An International Study - Earl, Cameron; Parker, Elizabeth; Capra, Mike (Environmental Health)
In 2000 the Glastonbury Festival in England experienced an unprecedented invasion of gatecrashers that severely compromised public health and safety. This incident identified the need for a comprehensive review of planning and management procedures for that event. In order to undertake this review, the 2001 event was cancelled. Upon its return in 2002, the event demonstrated considerable improvements in health and safety with the main features being tighter security and a more secure perimeter fence. Advancements such as these have continued at each subsequent event, with the 2004 festival considered the safest to date. The Glastonbury Festival provides a model for successful management of health and safety issues for large public events. This success was made possible by the collaborative efforts of the event organiser and government agencies, in particular the Mendip District Council. This event demonstrates how the licensing process can be a useful tool to encourage good practice in public health and safety issues for large outdoor music festivals.
Publisher: Environmental Health Australia (EHA)
Keywords: Glastonbury Festival; Music festival programs; Music festivals–Management; Outdoor music festivals (OMF); Public health; Risk assessment; Social movements; Special events–Management

Service des relations de travail | 514 842-2866, poste 241 - GMMQ - Guilde des musiciens et musiciennes du Québec
Keywords: Nettoyer; À ajouter

*Charte canadienne des droits et libertés - Gouvernement du Canada
Les ressources en ligne des lois et reglements codifiés du Canada
Last Modified: 2024-04-09
Keywords: Bibliographie; Nettoyer

Ligne-ressource pour les victimess d'agressions sexuelles, bilingue, sans frais, en tout temps Sans frais : 1 888 933-9007 Montréal : 514 933-9007 - Gouvernement du Québec
Keywords: Coffre à outils; À ajouter

The #E-Too Movement: Fighting Back Against Sexual Harassment in Electronic Sports - Holden, John T; Iii, Thomas A Baker; Edelman, Marc (ARIZONA STATE LAW JOURNAL)
Competitive video gaming or esports has captured the attention of hundredsof millions ofpeople acrossthe globe. With that attentionhas come billions of dollars' worth of investment and promotion. But, it has also exposed an underlying toxic environment that features widespreadsexual andgender harassment. This pervasive culture of harassment threatens to derailthe esports industry and mars the promise of gender equity in one of the few competitive "sports"where physical strength, agility and body size do not dictate success. In this Article, we examine the rise of competitive gaming, and provide an in-depth analysis of the pervasive issue of harassment that permeates esports. We then propose a series of tangible reforms that would hold harassers and their corporate accomplices accountablefor their harassingbehavior.
Keywords: Irina

Vague de dénonciations : un groupe de soutien est créé dans le milieu littéraire - ICI.Radio-Canada.ca, Zone Arts- (Radio-Canada)
Une centaine de femmes du milieu littéraire québécois se sont donné un espace virtuel privé pour dénoncer.
Publisher: Radio-Canada.ca

Des allégations d'inconduite sexuelle contre le chef d'orchestre Charles Dutoit - ICI.Radio-Canada.ca, Zone Justice et faits divers- (Radio-Canada.ca)
Trois chanteuses d'opéra et une musicienne soutiennent que le chef d'orchestre Charles Dutoit les a agressées sexuellement, de 1985 à 2010.
Publisher: Radio-Canada.ca

Optique culture – Numéro 93. Février 2024 – Les professions de la culture et des communications au Québec en 2021 - Marc-Andy Lubin

Gendered Precarity and Labor Organizing in the South Indian Film Industries - Mini, Darshana Sreedhar
Keywords: Irina

Tomber : Michel Brûlé - Radio-Canada
30 mai 2022
Keywords: Bibliographie; Nettoyer

Vague de dénonciations dans le milieu de l'improvisation - Radio-Canada

Une révolution culturelle en France ? - Ritland, Sara Prytz
Keywords: Irina

Critical Analysis of Sexual Harassment at Work Place (Prevention, Prohibition and Redressal) Act, 2013 with Special Emphasis to Film Industry - S', Anjana; George, Meera Elsa
Gone are the days where only men were the breadwinners of a family. With opportunities expanding and people moving forward into a contemporary world, gender disparity regardingemployment has become a thin line. We are in an era where both men and women workfor a living and contribute to theirfamily. Women are now coming forward and stepping into powerful positions and leaving their marks in various industries. However, there are many issues that demotivate women from coming forward. One such major issue is the absence of a healthy and safe working environment. Sexual Harassmentat Workplace is a violation of a woman's fundamental rights under Article 15, 19 and 21. It makes a woman insecure and causes severe mental trauma which in turn makes her quit the job or affects her self-confidence. Women are not sex toys for pleasure or the weak vulnerable section of humankind, but years of the patriarchalsystem that silenced women have resultedin women being subject to such exploitation.
Keywords: Irina

Code de conduite - Salon du livre de Montréal
Keywords: Bibliographie; Coffre à outils; Nettoyer

Cadre de l'édition. Des inégalités femmes-hommes toujours fortes - Serry, Hervé
Keywords: Irina

harcelement@uda.ca - Union des artistes
Pour toute question sur le harcèlement psychologique (y compris le harcèlement sexuel) ou encore sur la santé et la sécurité au travail à l’UDA, écrivez à l’adresse harcelement@uda.ca ou communiquez avec les conseillères et conseillers en relations du travail suivants : Karine Hervieux-Michaud 514-288-7150, poste 1339 , Émilie Lachance 514-288-7150, poste 1252 Catherine Leszkiewicz 514-288-7150, poste 1264 Bruno Massicotte-Picard 514-288-7150, poste 1338 Rémi Garon 514-288-7150, poste 1235 Marie Fisette 514-288-7150, poste 1254
Keywords: Bibliographie; Nettoyer

Valuing live music: The UK Live Music Census 2017 report - Webster, Emma; Brennan, Matt; Behr, Adam